Quels sont les effets des recettes pétrolières sur le capital humain en zone CEMAC ? - Fompehou, Amadou (MPRA Paper, 2026)
This article examines the effects of oil revenues on human capital in CEMAC countries over the period 1995–2020. The study is based on a dynamic panel of five countries (Cameroon, Congo, Gabon, Equatorial Guinea and Chad). The data are sourced from the IMF, the World Bank (WDI), the UNDP and the Worldwide Governance Indicators (WGI). The author employs the Blundell and Bond (1998) GMM system estimator to address the endogeneity and persistence of human capital, supplemented by interaction term models and robustness tests (stationarity, cross-sectional dependence). The analyses reveal a negative or non-significant effect of oil revenues on human capital indicators (school enrolment, life expectancy, HDI-education). Institutional quality acts as a powerful positive moderator, whilst revenue volatility has a detrimental effect. These results highlight the need for better governance, stabilisation funds and a more efficient allocation of oil revenues towards education and health.
Number: 129352
Keywords: Human capital; Institution; Oil revenue

An evaluation of China’s securitization regulatory system - Cao, Lei (Université de Montréal, 2025)
Since its innovation as a modern financial product in the 1970s, securitization has swept the global financial market. In 2000s, in order to ease China’s concentrated debt risks in the banking system and to improve the country’s imbalanced financial system, the Chinese government started to promote a trial program of securitization. An associated regulatory system was then created to facilitate the development of the Chinese securitization markets. Unlike regulations drafted and applied in North America, where an ex-ante regulatory analysis procedure and an ex-post evaluation system are installed, the current Chinese securitization regulation system is built mainly upon a basis of trial and interim rules. In other words, Chinese regulations regarding securitization were not comprehensively assessed before their adoption and there has been no systemic ex-post evaluation of the current securitization regulatory system in the past 20 years. This raises the question of whether the Chinese securitization regulation system facilitates the achievement of its regulatory objectives. The author purports to answer this question using three tools: The theory of regulation, legal historical analysis of law, and comparative law. To begin the analysis, the author designs an analytical framework based on the theory of regulation to evaluate Chinese regulations on securitization. In this evaluative framework, perspectives and criteria are stipulated to guide and draw the boundary of the evaluation. While applying the analytical framework, the author reviews the development of the Chinese securitization regulatory system over the past 20 years. The author studies the historical context of regulations established and regulatory modifications adopted in order to assess whether the logic embedded in the current Chinese securitization regulatory system is still valid. To better evaluate the Chinese securitization regulatory system, the author also applies a micro comparison of certain Chinese securitization regulations with their counterparts in North America. The purpose of this comparison is also to understand whether the Chinese characteristics in Chinese securitization regulations facilitate the achievement of its regulatory objectives. At the end of this assessment, the author provides a report to find the merits and disadvantages of Chinese securitization regulatory system. Due to the evaluative nature of this research, no demonstrated solutions are proposed in this report. Depuis sa création dans les années 1970, la titrisation s’est répandue à travers le marché financier mondial. Dans les années 2000, le gouvernement chinois a commencé à promouvoir le programme de titrisation afin d'atténuer les risques liés à la concentration de la dette dans le système bancaire et d'améliorer un système financier déséquilibré. La règlementation associée a été mise en place pour faciliter le développement du marché chinois de la titrisation. Contrairement aux régles créées et appliquées en Amérique du Nord, qui suivent une analyse ex ante —c’est-à-dire avant leur adoption — et une évaluation ex post — soit après leur application pendant une certaine période, le système de réglementation de la titrisation actuellement en vigueur en Chine a été élaboré sur la base d’essais et de mesures provisoires. Autrement dit, la Chine ne s’est pas fondée sur une analyse ex ante approfondie, et n’a mené aucune évaluation systémique ex post de ses réglementations de la titrisation au cours des vingt dernières années. Ce système chinois de réglementation de la titrisation facilite-t-il ou non la réalisation de ses objectifs réglementaires ? L'auteur tente de répondre à cette question à partir de trois outils : la théorie de la réglementation, l’analyse historique du droit et le droit comparé. Pour commencer, l’auteur conçoit un cadre analytique basé sur la théorie de la réglementation pour évaluer les dispositions chinoises en matière de titrisation. Dans ce cadre d’évaluation, des perspectives et des critères sont proposés pour guider et délimiter l’évaluation. À la lumière de ce cadre analytique, l’auteur replace la réglementation chinoise de la titrisation dans son contexte historique et retrace les modifications apportées au cours de deux dernières décennies. Il s’agit ainsi d’évaluer si la logique qui a présidé à l’adoption de ces règles reste valide dans le contexte actuel. Mais pour mieux saisir les caractéristiques de la réglementation chinoise de la titrisation, l’auteur ajoute à cette analyse historique interne à la Chine des micro-comparaisons de la titrisation chinoise et de ses règles avec leurs homologues nord-américains dans différentes sections de cette thèse. C’est ainsi qu’il sera possible de voir si les caractéristiques chinoises de la réglementation en matière de titrisation facilitent ou non la réalisation de ses objectifs. Au terme de cette recherche évaluative, l’on proposera un rapport qui mettra en lumière les avantages et les inconvénients du système chinois. En raison de sa nature évaluative, cette thèse ne proposera aucune solution aux inconvénients repérés.
Keywords: China; Chine; Evaluation of Chinese; Financial Regulation; Marchés chinois; Réglementation financière; Securitization; Securitization Markets; Securitization Regulation; Titrisation; Titrisation (réglementation)

A framework for bank resolution in Namibia - Eiseb, Bryan Karl Gunther (University of Pretoria, 2025)
Banks are regarded as special financial institutions because, apart from the various critical intermediary and other functions they fulfil in a financial system, the hallmark of their business models is receiving deposits from the public and using such deposits for extending loans against interest from which they make profit. Unlike other companies, banks are however vulnerable to loss of public confidence and remain exposed to various risks and failure. Banks are thus critically important actors in domestic and global financial systems, - thus their safety is critical to the maintenance of financial stability. As a result, banks are subject to stringent regulation and supervision to ensure their safety. Despite prudential regulation, the failure of banks remains a reality. If the risk of bank failure is not adequately addressed through appropriate regulation and supervision, , it may result in a financial crisis like the 2008 Global Financial Crisis (2008 GFC). Because banks play a special role in an economy and their failure may have an adverse impact on financial stability and depositors, this thesis aligns with the view expressed by academics and international organisations that there is a need for a special regime (lex specialis) to deal with the failure of banks since normal insolvency procedures are not suitable for this purpose. f. This is because bank failures require swift, timely intervention by a supervisor to resolve failing banks in an orderly and optimal manner to ensure the maintenance of financial stability, depositor protection and relegating bailouts with taxpayers’ money as a last resort. A very notable lesson that emanated from the 2008 GFC is the criticality of special resolution frameworks for banks; the need to balance the interests of shareholders, creditors, and depositors, while promoting financial stability objectives. As a result, the need for special resolution frameworks for banks which empowers Resolution Authorities with adequate resolution tools and powers to resolve a failing bank timeous and orderly , has become a legislative imperative in contemporary financial systems. To deal with bank failures in Namibia, the Banking Institutions Act, 2 of 1998 (the BIA 1998) contained provisions that allowed for the assumption of control and liquidation of a failed bank. However, the newly enacted Banking Institution Act 13 of 2023 (the BIA 2023 which repealed the BIA 1998) has changed that position and introduced a single provision in section 70 that provides for bank resolution. Until now, prior to the introduction of this very new statutory provision, all bank failures in Namibia were dealt with under the limited supervisory tools of the BIA 1998. This study seeks to determine whether section 70 of the BIA 2023, is sufficiently aligned with international best practice as captured in the Financial Stability Board’s Key Attributes of Effective Resolution Regimes for Financial Institutions (FSB KAs), issued in 2011, as updated in 2014 and 2024. Alternatively, if the regime introduced by the BIA 2023 does not adequately align with the FSB KAs it is then considered whether the new Namibian bank resolution framework requires to be strengthened further to better align it with the FSB KAs. To consider possible further reforms to the new Namibian bank resolution regime, this thesis considers the resolution frameworks in Germany and Nigeria by way of comparative studies to observe best practices.
Keywords: Bank; Financial stability; Key Attributes; Namibia; Resolution

Impact of Blockchain Adoption, Regulatory Environment, and Institutional Investor Participation on FinTech Innovation - Almestarehi, Ahmad Abdel Rahim; Al-Ababneh, Hassan Ali; Malkaw, Eyad Mohammad (Theoretical and Practical Research in Economic Fields, 2025)
This study investigates how blockchain integration, regulatory policies, and the participation of institutional investors impact fintech innovation in Jordanian fintech companies. A descriptive analytical approach was used to evaluate and summarize the effects of these factors on innovation in the sector. An electronic survey was conducted among 125 administrative personnel working in Jordan's fintech industry. The results indicate a strong presence of blockchain adoption, involvement of institutional investors, and overall fintech innovation in these companies. However, the regulatory landscape in Jordan's fintech sector was found to be moderate. Furthermore, the analysis reveals that both blockchain integration and the regulatory framework significantly influence fintech innovation, with a significance level of 0.05. In light of these findings, the study suggests the creation of strategies to promote blockchain adoption, aiming to enhance efficiency and innovation in the industry.
Number: 2

Tax Reform and Investment Decision Effects in an Emerging Economy: Insights from Ghana - Yeboah, Michael; Danquah, Benjamin Adjei; Bawuah, Jonas; Nkwantabisa, Agyeiwaa Owusu (Theoretical and Practical Research in Economic Fields, 2025)
This study focuses on both domestic and foreign investment as indicators of economic growth in an emerging market context, examining the effects of tax reforms on investment decisions in Ghana from 1985 to 2020. The research employs a time-series analysis to integrate control variables like inflation, gross capital formation, and base rate, revealing their significant influence on investment activity in tandem with tax policy changes. Unlike previous research that mostly uses gross fixed capital formation as a proxy for investment, this study includes a wider range of investment types, giving a more complete picture of how the economy works. We did unit root and co-integration tests, which showed that the variables were first-order co-integrated. We performed the model estimate using a Vector Error Correction Model (VECM) and Granger causality tests. Results reveal that tax reforms have a measurable impact on investment patterns, underscoring the importance of adaptive tax policies in promoting sustainable economic development. The findings contribute to the broader literature on investment and fiscal policy in emerging economies, offering insights for policy-makers on optimizing tax strategies to encourage investment and drive economic growth.

A comparative statutory analysis of the causes of bank failures in Zimbabwe - Tsaura, Oscar (North-West University, 2025)
Zimbabwean financial sector has experienced significant periods of financial distress as depicted by numerous bank failures since 1980. Bank failure occurs when a financial institution experiences significant financial distress, rendering it incapable of fulfilling its obligations to depositors, shareholders and other stakeholders. In other words, bank failure is when a financial institution undergoes substantial financial distress rendering it unable to meet its obligations as they become due. In this thesis, the researcher adopted the definition of bank failure which refers to a situation where a bank is in financial distress and is recapitalised either by the central bank or a strategic investor, acquired by another institution, surrenders its license or the license is suspended, or it closes its operations altogether. This thesis reveals that in Zimbabwe bank failures can be attributed to various factors including the failure of regulatory and supervisory systems to detect irregularities in the operations of banking institutions. In addition, poor corporate governance practices such as inadequate oversight, inexperienced management, undue influence by dominant shareholders, nonperforming loans, excessive risk-taking, abusive related party transactions and noncompliance with laws are commonly cited as causes of bank failures in Zimbabwe. Bank failures often pose negative implications to the banking sector and banking stakeholders such as depositors and investors. This owes to the fact that banks serve as intermediaries that facilitate the avenues for deposits and extend credit services to individuals and the production sector of the economy. It is submitted that the proper functioning of banks requires effective and adequate regulatory supervision. Failure to provide robust and effective regulation of banks could lead to bank failures. This thesis presents a comparative analysis of the banking statutory framework of Zimbabwe and those of the UK and South Africa to determine if the banking laws in Zimbabwe are robust enough to prevent bank failures. The thesis reveals that the banking statutory framework in Zimbabwe is not robust enough to curb bank failures in times of stress because it lacks effective regulatory oversight. This thesis further reveals that poor banking regulation, inconsistent enforcement, weak regulatory insolvency procedures, and inadequate supervision framework are some of the weaknesses in the current banking statutory framework which needs to be rectified in order to combat bank failures effectively in Zimbabwe. The Banking Act does not fully incorporate the international best standards on bank supervision to prevent bank failures. Consequently, the banking statutory framework in Zimbabwe does not comprehensively and effectively provide for the prevention of bank failures like those of the UK and South Africa. The robustness of the banking statutory framework is in providing adequate and effective regulatory provisions and enforcement mechanisms that curb bank failures in Zimbabwe. The researcher proposes the adoption of a new model, the Zimbabwean twin peaks model, comprising the Zimbabwean Prudential Regulatory Authority and the Zimbabwean Financial Sector Conduct Authority. It is argued that if the adoption of the twin peaks model is considered and robustly implemented, it can prevent the causes of bank failures in Zimbabwe.
Keywords: Bank failure; Banking legislation; Banking statutory framework; Banks; Curatorship; Financial regulations; Financial stability; Fraud; Money laundering; Political instability; Zimbabwe

The Protection of E-Banking Services Against Cybercrimes in Cameroon: Prospects and Challenges - Ghaseh, Nkambeh Allen (International Multilingual Journal of Science and Technology, 2025)
This article seeks to examine the extent to which users of e-banking services are protected in Cameroon. Over the past decades financial transactions have gradually emerged from traditional methods to modern forms of banking. The Information and Communication Technology (ICT) has transformed the banking system into a digital arena. With e-banking, customers can access their bank accounts, transfer funds, pay bills, and check their accounts balances. Banks serve as the backbone of every modern economy and should be protected. The development of e-banking in the 1980s with the aid of ICT has rendered banks and their customers vulnerable to cybercrimes. As an effort to combat cybercrimes and ensure cyber security in Cameroon, the 2010 Cyber Law provides both substantive and procedural rules. It is rather unfortunate that, the measures put in place to ensure cyber security and protect bank customers against cybercrimes are to a greater extent ineffective. The main objective of this article is to determine the protection accorded to banks and their customers against cybercrimes. The method adopted in the course of this work is doctrinal wherein, both primary and secondary sources of data were collected. The findings reveal among others that, the measures put in place to combat cybercrimes within the banking sphere in Cameroon are not effective. There is lack of explicit definitions for cyber offences. Most of the offences provided by the 2010 Cyber Law are vague and ambiguous. We therefore recommend that, the 2010 Cyber Law should be amended to address the current issues of ICT. This amendment should include explicit definitions for the different forms of cybercrimes with severe sanctions. Banks are advised to put in place effective monitoring machineries to mitigate cybercrimes.

The regulation of crypto-assets in South Africa with particular regard to crypto-asset market manipulation - Mgijima, Lwandiso (University of Pretoria, 2025)
Market manipulation is one of the dishonest means used by unscrupulous investors to make unjustified profits. It is conduct which unlawfully interferes with the normal operations of the markets in order to create false appearances with respect to the trading activity or the price of a financial asset. Market abuse is one of the various challenges plaguing the crypto-assets market, and is one of the financial regulators’ priority concerns. This study examines and discusses the problem of market manipulation in crypto-assets, and the need for the enactment of an effective regulatory framework in order to combat this problem and to promote investor protection and safeguard the integrity of the markets. The study finds that South Africa and other countries need to introduce rules in crypto-assets market which aim at regulating the activities of crypto-asset service providers. Currently South Africa has not enacted a comprehensive regulatory framework to address the various illegal uses of crypto-assets. The general approach adopted by South Africa to regulate crypto-assets activities involves subjecting crypto-asset service providers and their activities under the various financial sector laws established to regulate the traditional financial markets. This approach has been criticised as being inefficient in light of the unique risks presented by crypto-assets. The study discusses some of these arguments in detail and concludes by highlighting the need for the adoption of innovative regulations, in the long term, which comprehensively and effectively addressed the various risks presented by crypto-assets which also include market manipulation.
Keywords: Crypto-asset; Crypto-assets; Framework; Manipulation; Markets; Misconduct; Regulation; Service provider

Essays on banking and society - Heyert, Axelle (Université de Strasbourg, 2025)
This dissertation examines the relationship between banking and society. It contributes to a better understanding of how banking affects society and, in turn on how society shapes banking practices. The first chapter studies the impact of inflation on trust in banks. Chapter two deals with the effect of trust in banks on financial inclusion. The third chapter investigates whether financial inclusion influences life satisfaction. Chapter four delves into how female bank leadership affects firm credit. The final chapter focuses on the influence of bank leaders’ age on sustainable lending. Overall, this dissertation highlights the important role of banks in societal development and the major influence of society in shaping banking practices.
Keywords: ACCESS TO CREDIT; Accès au crédit; Banking; Banks; Banques; Bonheur; Confiance; Financial inclusion; Gender; Genre; Inclusion financière; Inflation; Life satisfaction; Prêts durables; Sustainable lending; Trust in banks

Financial regulation and risk management: addressing risk challenges in a changing financial environment - Ojo, Marianne (Munich Personal RePEc Archive, 2025)
Will the April 2nd Announcement generate its intended objectives? It’s still early days – however, it appears increasingly likely that negotiation outcomes – particularly between those significantly impacted by the Announcement, will be a major determinant in deciding whether the tariff hikes resulting from the April 2nd Announcement, will be short or long term. As of the 11th April, 2025, President Trump’s universal tariffs on China had amounted to 145% whilst China announced tariffs of 125% on U.S imports. Amongst other things, this paper aims to address complexities and challenges faced by regulators in identifying and assessing risk, problems arising from different perceptions of risk, and solutions aimed at countering problems of risk regulation. It will approach these issues through an assessment of explanations put forward to justify the growing importance of risks, well known risk theories such as cultural theory, risk society theory and governmentality theory. In addressing the problems posed as a result of the difficulty in quantifying risks, it will consider a means whereby risks can be quantified reasonably without the consequential effects which result from the dual nature of risk that is, risks emanating from the management of institutional risks.
Keywords: Financial Forecasting and Simulation; General Financial Markets; International Financial Markets; Regulation and Business Law

A trans-border African crypto asset licence to promote economic growth and deepen financial inclusion - Van der Lith, Johann Daniel (University of Pretoria, 2025)
Financial technology (Fintech) is a rapidly growing industry, both locally and globally. In various ways, Fintech is undeniably transforming financial services and products in every possible part of the financial sector by changing how people access and use financial services. By using innovative technologies, such as distributed ledger technology and cloud technology, and combining large data sets, including alternative data sets, better products can be provided that can be hyper-personalised for market segments and improve access and participation in respect of financial services. Fintech is solving issues that touch the consumer, through a bottom-up approach, considering the retail consumer as a starting point, in contrast to the common traditional finance evolution from the institutional investors to the retail consumer in a top-to-bottom approach. What is exciting about what Fintech can do for Africa, is that it can move inefficiencies in services and product life cycles to become efficiencies and move the frontiers for already efficient products and services. Fintech, therefore, provides an opportunity to improve the archaic and pave the way for the future. This study focuses mainly on crypto assets to limit its scope. It first examines the Fintech landscape in Africa, more specifically, the activity level in each selected comparative country, namely Mauritius, Kenya, Zambia, Namibia and South Africa, and how the activity benefits or can potentially benefit the economy in the host country and lead to the deepening of financial inclusion. It further examines the regulatory frameworks in those countries. The study examines the regulatory approach taken and the local activity, exploring some of the risks identified in each country, and considers the requirements that regulators chose to implement to mitigate these risks, as well as the current state of regulatory frameworks. Consideration is given as to whether similarities in both the risks and the mitigation requirements exist and how this can be aligned across jurisdictions. Recently, international standard-setting bodies have increased their focus on ensuring the alignment and cooperation of regulatory approaches globally. In light of the call for alignment and increased collaboration through policy recommendations and guidance, and or regulators to provide comprehensive and effective regulatory approaches without stifling innovation, this study considers the theoretical possibility of allowing certain Fintech companies, specifically crypto asset service providers (subject to specified conditions) to operate across jurisdictions with a trans-border licence. This study examines Europe’s Markets in Crypto Assets Regulation, as it was the first of its kind continental-wide framework for crypto assets, offering numerous lessons to be learned from this framework. The Commonwealth Model Law on Virtual Assets is also considered, as it is intended to assist member countries in implementing Virtual Asset and Virtual Asset Service Provider regimes in their respective jurisdictions, as they deem appropriate. Lastly, the study will explore what a theoretical trans-border regulatory framework containing prudential and market conduct requirements could look like and what embedded supervision tools, for instance, through forensic nodes or zero-knowledge proofs, could be utilised to ensure that all the regulators participating as part of a licencing panel receive real-time data and have a full view of the level of compliance with the requirements imposed by the joint framework and can proactively and intrusively act, when needed. The proposed trans-border regulatory framework aims to support crypto asset service providers with multi-jurisdictional strategies in Africa in scaling their operations, with a focus on building Africa as a global Fintech hub. The proposed framework aims to achieve this through a harmonised regulatory framework that simplifies compliance, increases efficiencies, enhances innovation, allows for scalability, and better risk management. In addition to the goal of positioning Africa as a globally recognised Fintech hub, the harmonised framework aims to realise the purported benefits of the technologies utilised by crypto asset service providers, thereby deepening financial inclusion and promoting inclusive economic growth through increased access and participation, as well as lower costs.
Keywords: Crypto assets; Embedded supervision; Financial inclusion; Financial technology; Regulatory frameworks

Artificial Intelligence in Accounting: Revolutionizing Financial Management in the Digital Landscape - Alnaimat, Mohammad Ahmad; Korsun, Inna; Lutsenko, Kostiantyn; Khodorkovskyi, Oleksandr; Artemchuk, Mykyta (Theoretical and Practical Research in Economic Fields, 2025)
The use of artificial intelligence (AI) builds up the accounting system efficiency, increases data entry accuracy and simplifying the accounting process. The aim of the study is to prove the effectiveness of modern AI-based information technologies (IT) in accounting and the possibilities of AI application for process optimization. The effectiveness and efficiency were proven using comparison methods, statistical analysis, graphical cause-and-effect analysis, modelling using the linear regression method. The assessment was carried out using quantitative and qualitative indicators of labour productivity and process optimization. The results of the study showed that 18 accounting department employees on average are needed to perform standard transactions in the companies studied without AI. With AI, 1 person can handle such a volume of work. Accordingly, with the implementation of AI, the average reduction in Transaction Processing Time per Week is 696.26 hours. Regression analysis confirmed that the implementation of AI increases the companies’ productivity in terms of Transaction Processing Time. Reducing the Data Processing Complexity by one unit leads to a reduction in transaction processing time by 592.69 seconds. Each percent increase in Data Entry Accuracy contributes to a reduction in processing time by 5135.51 seconds. The prospects for implementing AI in accounting include further improving algorithms to increase the accuracy and speed of transaction processing, optimizing material and time consumed.
Keywords: Accounting; Artificial Intelligence; Automation; Data analytics; Digital environment; Financial management; Inteligência artificial; Intelligence Artificielle; Machine learning

Money Laundering: New Technologies and Control Challenges (Cryptocurrencies, Blockchain) - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Tackling corruption is a global issue and tackling it effectively requires determination, cooperation and specialised technological knowledge. A significant proportion of global GDP is the sum of the money associated with corruption and fraud. The main objective of this article is to assess how new technologies such as cryptocurrencies and blockchain can combat corruption. The methodology of this article is a literature review. Specifically, scientific articles from databases and international organizations with expertise in new technologies are studied. This article deals with the new ways of corruption and money laundering. New technologies and the knowledge of them are a very important element in order to deal effectively with corruption. Perpetrators of financial crimes are usually ahead of the auditing authorities in terms of techniques and therefore knowledge of the new technology and the possibilities it offers is essential to effectively combat corruption and fraud globally. Cryptocurrencies and blockchain can combat corruption primarily due to their key characteristics of transparency, security, and decentralization. A key prerequisite for the transparency of cryptocurrencies is the application of supervision rules by the responsible authorities and the implementation of blockchain technology. In practice this is often not the case and cryptocurrencies are used as a money laundering tool.
Keywords: Corruption; Cryptocurrencies; Fraud; Money laundering; New technologies

Effects of Dynamic Capabilities and Multichannel Integration Quality on Bank Performance; A Moderated Role of Environmental Dynamism : A Moderated Mediation Model Analysis - Geleta, Negash; Amentie, Chalchissa; Getahun, Misganu (African Journal of Economic and Business Research, 2025)
This study investigates the effects of dynamic capabilities (DCs) and multichannel integration quality (MCIQ) on the performance of banks (BP). It also explores the moderating role of environmental dynamism in the banking industry, using a moderated mediation model. Quantitative analyses were employed to examine data collected from multiple banks. Structural equation modeling (SEM) was used to test the relationships between variables, while moderation and mediation effects were analyzed using SEM-AMOS. The findings reveal that dynamic capabilities and MCIQ significantly enhance bank performance. Furthermore, environmental dynamism (ED) moderates the relationship between these variables, intensifying their effects on performance under high levels of dynamism. The mediation analysis shows that MCIQ partially mediates the impact of dynamic capabilities on bank performance. The study is limited by its cross-sectional design, which restricts causal inferences. Additionally, the findings may not be generalizable to non-banking industries or regions with distinct regulatory frameworks. The results provide actionable insights for bank managers, emphasizing the importance of fostering DCs and enhancing MCIQ to sustain performance in rapidly changing environments. The findings highlight significant social benefits, as improved dynamic capabilities (DCs) and critical information quality (MCIQ) enhance bank performance, fostering economic stability, financial inclusion, and customer trust. By enabling resilience and innovation in dynamic environments, banks contribute to broader societal goals, including sustainable development and socio-economic growth. This research contributes to the literature by integrating DCs and MCIQ in a moderated mediation framework, offering a novel perspective on their interplay with environmental dynamism in the banking sector.
Keywords: Dynamic Capabilities; Environmental Dynamism; Moderated Mediation Model; Multichannel integration quality

An analysis of the challenges in combatting money laundering within Bureaux de Change establishments in Botswana - Mokone, Philadelphia Pontsho (Journal of Money Laundering Control, 2025)
PURPOSE : Financial institutions such as Bureaux de Change are susceptible to money laundering, posing a significant risk to a nation’s financial stability and security if not properly regulated and supervised. Botswana is a member of the Financial Action Task Force (FATF), a global organisation that sets standards, promotes policies to prevent money laundering, terrorist financing and arms proliferation, all to safeguard the global financial system. Efforts have been made to incorporate FATF recommendations on money laundering into the fiscal laws of Botswana. However, some deficiencies still remain. Although there are no recorded cases of money laundering in Botswana, Bureaux de Change entities are susceptible to it as their business involves cash transactions and rapid money transactions. This paper aims to analyse the challenges faced by Bureaux de Change entities in combating money laundering in Botswana. This will be done by assessing the effectiveness of the current regulatory framework and role of the regulatory authorities in combating money laundering within Bureaux de Change entities. DESIGN/METHODOLOGY/APPROACH : This paper provides a comprehensive examination of the obstacles faced by Bureaux de Change entities in Botswana when it comes to combating money laundering. A qualitative research method and doctrinal research method are both used in this context. FINDINGS : It is hoped that policymakers and other relevant persons will adopt the recommendations provided in the paper to enhance the curbing of money laundering in Botswana. RESEARCH LIMITATIONS/IMPLICATIONS : This paper is only limited to the regulation of money laundering within the Bureaux de Change entities in Botswana and does not provide empirical research. PRACTICAL IMPLICATIONS : This paper is useful to policymakers, lawyers, law students and regulatory bodies especially in Botswana. SOCIAL IMPLICATIONS : This paper suggests changes to the Bank of Botswana (Bureaux de Change) Regulations of 2004 to improve their effectiveness, robustness and competitiveness in combating money laundering. ORIGINALITY/VALUE : This paper is original research on the challenges of combating money laundering within Bureaux de Change entities in Botswana.
Emerald Publishing Limited
Keywords: Botswana; Bureaux de Change; Cash transactions; Financial security; Financial stability; Money laundering; Risk; Supervision

The effects of Basel III on the intermediation and market activities of WAEMU banks - Kouakou, Thiédjé Gaudens-Omer (University Library of Munich, Germany, 2025)
This paper analyzes the effect of Basel III adapted to WAEMU on the behavior of banks in the zone (intermediation and market activities). After having developed a model for optimizing the return on bank equity, under various constraints (balance sheet constraints, Basel III regulatory constraints), we resort to linear programming via the Danzig simplex algorithm and to a structure of reasonable rates to obtain the optimal values of the various bank balance sheet items. The results, obtained by comparing these theoretical values with the values observed before Basel III (before January 1, 2018), show an increase in the supply of loans, obtained not only from deposits and bank refinancing but also via resources from the financial markets. We can also observe the intuitive result of an increase of bank reserves in line with the constraint that Basel III imposes on banks to increase their liquidity. In short, Basel III tends to strengthen bank financing in the zone, while improving the soundness of banks through the constitution of larger reserves.
Keywords: Calibration; Credit supply; Linear programming; Prudential regulation

The Artificial Intelligence (AI) framework and the benefits of its use in internal audit - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
AI is well known today as a valuable tool that can improve our daily lives. In addition, it can improve the efficiency and productivity of many professions, such as the internal auditor. The research methodology is literature review. The primary objectives of the article are twofold: Firstly, to provide a comprehensive description of the institutional framework for the operation of AI internationally, and secondly, to examine the benefits that arise from the use of AI in internal audit units and organisations in general. The significance of the research lies in its examination of artificial intelligence (AI) as a valuable instrument in the arsenal of internal auditors. The findings suggest that AI has the potential to enhance the efficacy of internal audits, reduce the time required for their execution, reduce the frequency of internal audits, and, in general, optimise the operations of companies and organisations.
Keywords: AI; Artificial Intelligence; Corruption; Fraud; Inteligência artificial; Intelligence Artificielle; Internal audit; Management

Impact of the basel accords on small indigenous banks in developing countries : the case of Zambia - Rolls II, Douglas Walter (University of Pretoria, 2025)
The purpose of this thesis is to evaluate the impact of the Basel Accords on small indigenous banks in developing countries, with particular concentration on small Zambian banks. The problem statement intends to investigate whether implementing the three Basel Accords is conducive to the growth of small banks in Zambia. The study further aims to determine whether the present approach to legal regulation of small banks in Zambia is appropriate. The methodology is based on desk-bound research and examination of both primary sources and secondary sources of material such as books, journals, and relevant articles. The study is impacted by the dearth of secondary research work and the difficulty of getting information from sources like the Zambian central bank and other information centres. While Basel I and II seem to have stabilised the Zambian financial sector, the Basel III Accord appears to have impacted negatively on many small banks to the extent that they have been forced into merger and acquisition arrangements with larger foreign banks to fund their undercapitalised positions to survive. It also emerges that the Zambian financial system is strongly linked to the international global economy; regionalisation with organisations like SADC and COMESA being the first stages in the process. This situation is likely to introduce increased instability in the Zambian financial sector by making banks more vulnerable to the vagaries of the international financial markets. It is thus recommended that the Zambian central bank should be more proactive in lobbying for better conditions for small banks from the Basel Committee for Banking Supervision and other international financial regulatory bodies; it should also avoid “cutting and pasting” rules from other jurisdictions to avoid possible distortions in the banking sector. It should also encourage further development of primary and secondary markets in low-cost paper and provide small banks with long-term, low-interest loans to support their growth. The Bank of Zambia, the Zambian central bank, should consider establishing a separate Act financial services Act for small banks to better regulate them. The central bank should also seek out non-Basel Accord solutions for small banks including re-examining the positive aspects of the infant-industry argument. Lastly, it should introduce a formal system for classifying banks in Zambia. At the international level, it is suggested that the global standard-setting bodies should undergo radical reforms to ensure that they are in tandem with the problems that banks in developing countries face as well as allow them to have a say in global standard setting. It is recommended that global standard-setting bodies apply simpler rules for smaller banks. The impact of the Basel Accords on small indigenous banks in developing countries and Zambia, in particular, is important because of the role that small banks play in developing economies in growing small and medium-sized businesses that are often ignored by large foreign banks. It is also important that small banks are allowed to grow into large and medium-sized banks to effectively compete against foreign multinational banks. Institutions based on neoliberal ideals appear to only serve Western businesses’ interests despite their call for all countries to create a level playing field. Due to the dearth of empirical research, there are several gaps in the work that may provide opportunities for further research in this important area of the law.
Keywords: Banking supervision; Basel accords; Basel committee; Developing countries; Financial regulatory framework; Small banks

Editorial: Special Edition on Banking, Competition & Corporate Law: Confronting Contemporary Challenges of Banking, Competition & Corporate Law to Enhance Consumer Protection - Chitimira, Howard (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Banking; Competition; Financial crimes; Financial markets; Securities

Impact of the Revision of the OHADA Accounting System on the Decision to Grant Bank Credit to Cameroonian Companies: An Interview with Credit Analysts - Sekadjie, Dedy Christelle; Mbohwa, Charles (Journal of Accounting and Finance in Emerging Economies, 2024)
Purpose: The objective of this study is to evaluate the impact of accounting data produced after the revision of the OHADA accounting system on the decision to grant bank credit to Cameroonian companies. Methodology: qualitative approach was used in this study. We conducted semi-structured interviews with eight credit analysts in eight banks based in Cameroon. We used the Nvivo 10 software to carry out the content analysis. Findings: It emerges from the analysis of the content of the speeches collected that the most used ratios by credit analysts are: activity ratios, debt ratios, operating ratios, financial structure and autonomy ratios, debt ratios and net cash. In addition, the information provided by the new accounting system is increasingly fluid, detailed, and precise and facilitates decision-making. However, when it comes to the completeness and sincerity of the information provided, analysts remain wary because, companies always provide information subjectively based on their interests Implication: This study reveals that despite the revision of the accounting system, users still remain wary face of informations provided because of its subjective nature. It is therefore recommended that Member States promote unified information for all stakeholders.
Keywords: Accounting system; Bank credit; Decision-making; Revision

The Challenges of Adoption of Eco Single Currency among ECOWAS Member-States - Anele, Livinus; Anuga, Joseph (African Journal of Politics and Administrative Studies, 2024)
The Economic Community of West African States, ECOWAS, had an agreement to adopt the Eco as its single currency for the fifteen member-states of the West African Sub-regional organization. This major objective has failed to materialize after a long period of time. This paper, therefore seeks to highlight the major challenges confronting the Eco currency project. Data were collected from secondary sources, using content analysis. The paper of discusses the challenges facing the proposed Eco single currency in West Africa, discusses the theoretical framework of monetary integration using Mundell’s factors of Mobility Theory and Mundell’s Optimum Currency Area Theory applied. Based on the findings, Some of the challenges facing the proposed Eco currency in ECOWAS include lack of political will, influence of France on its former territories in West Africa, membership of multiple regional blocs by member states of ECOWAS and fear of domination of the smaller states in the bigger ones. Other challenges include; security and political challenges, inadequate legal instruments to enforce treaty obligations, inadequate modern infrastructure among others. To make this proposed Eco currency a success, the paper suggests that West Africa Monetary Zone member states must take concrete action by showing political will towards the creation of Eco currency area in West Africa. There should be clearly spelt out benefits and costs accruing to each member state in the proposed Eco community currency area. All member states of ECOWAS must be treated as equal partners.
Keywords: Adoption; Anglophone-Francophone; Development; ECOWAS; Eco single currency

An Exploration of Selected Anti-Money Laundering Role-Players in Zimbabwe - Chitimira, Howard; Torerai, Elfas; Jana, Vimbai (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Anti-money laundering; Corruption; Financial crimes; Money laundering; Role-players

Essays on Corporate Finance and Corporate Governance - Ding, Zijun (McMaster University, 2024)
This thesis includes three essays that examine the effects of firm policies on labor costs, corporate culture, and stock markets. The first essay studies the impact of major customers on supplier firms’ performance, and I find that supplier firms are willing to collaborate with their major customers while keeping low financial leverages. The cooperation with major customers results in higher productivity and strategic alliance, which could explain the reduction in the labor share of supplier firms. In my study, labor share is defined as the ratio of labor costs to total revenue. Compared to firms without major customers, supplier firms with at least one major customer would reduce labor shares on average by 33% in absolute terms. The findings contribute to the growing literature on the global trend of labor share reduction. The second essay examines the effect of market competition on corporate openness, which is a particular aspect of corporate culture. Corporate openness reflects how open firms are when facing new ideas and experiences, and measures firms’ willingness to innovate and cooperate. I conclude that market competition improves firms’ corporate openness through good corporate governance. Furthermore, corporate social responsibility activities are seen as a positive social outcome of corporate openness. As to economic consequences, less open firms would experience stock return reductions when the market competition is high. The third essay studies the firms listed on Chinese stock exchanges that established an internal whistleblowing mechanism. The results show that the employee whistleblowing system prevents firms from misconducting and leads to reduced stock price crash risk. Furthermore, a cooperative corporate culture helps the internal whistleblowing system decrease crash risk, while an unfair organizational climate exerts the opposite influence. Overall, this study contributes to the emerging literature on the governance role of whistleblowing.

The Impact of Financial Technology (Fin Tech) on Economic Growth: Evidence from Tanzania - Ngeze, Raphael Michael; Seif, Muba (African Journal of Economic and Business Research, 2024)
This research is driven by the rapid spread of fintech, and its contributions to Tanzania’s economic growth. This study uses quantitative quarterly time series data from Tanzania from 2008 to 2022. The Augmented Dicky Fuler (ADF) is used for the stationarity test, Johansen Cointegrations for the hypothesis and Cointegrations test, VAR and VECM for testing both short-run and long-run causality relationships, and Granger Causality for testing variable causality. The Ordinary Least Squares (OLS) regression model is used for parameter estimation, modelling and significance testing. The results show that the model is statistically significant and the independent variables in the regression accounted for around 89% of the overall variation in GDP. Fintech variable subscriptions have a positive impact on Tanzania’s economic growth. Thus, unemployment in Tanzania may be alleviated by the growing sector of financial technology. Fintech has involved many people from all over the world, including Tanzania, and has had a positive impact on both the national economy and per capita growth. Since TTCL and ZANTEL have witnessed a sharp decline in subscriptions, the government, as a fixed-wired broadband service provider, must take the necessary steps to increase the subscriptions.
Keywords: Economic growth; Financial Technology; M-Pesa; OLS; VAR; VECM

Effect of Taxpayer’s Attitudes on Tax Evasion among SMEs in Tanzania: A Case of Singida Tax Region - Chindengwike, James (African Journal of Economic and Business Research, 2024)
Paying taxes is essential to attaining sustainable economic growth and national economic independence, hence tax evasion is a concern for the economies of both wealthy and developing countries. This study examined how tax payer attitudes, particularly in the Singida Tax Region, affect tax evasion in Tanzanian Small and Medium-Sized Enterprises (SMEs). This study employed a survey method in which data collection comprised both qualitative and quantitative research approaches. A multiple regression model was employed in combination with a descriptive study approach to ascertain the outcomes. 145 SMEs taxpayers made up the study's as a sample size. The findings demonstrate that, among SMEs in the Singida Region, peer influence, tax awareness, tax morale, and tax evasion have statistically significant relationships with the taxpayer's attitude. This association is supported by statistics. Consequently, the United Republic of Tanzanian government needs to consider how taxpayer attitudes including peer pressure, tax knowledge, and morale affect tax evasion. This will contribute to the goal of reducing tax avoidance by all taxpayers, including SMEs Taxpayers.
Keywords: SMEs Taxpayers; Tanzania; Tax evasion; Taxpayer’s Attitudes

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

Cross-border banking and bank stability: evidence from Sub-Saharan Africa - Gondwe, Sopani; Gwatidzo, Tendai; Mahonye, Nyasha (Journal of Banking Regulation, 2024)
Based on bank-level data from 29 Sub-Saharan African countries between 2005 and 2019, we apply panel fixed effects (FE) and two-step system GMM estimators to investigate whether increased cross-border banking affects domestic banking sector stability. We find significant evidence that the stability of banks in host countries declines with an increased presence of foreign banks—and the impact is more pronounced on banks that are small and less efficient. The stability impact of foreign banks is also found to depend on the quality of governance institutional factors in the host country. The findings shed some important insights on the downside of financial liberalisation policy in developing countries and the need for increased cross-border collaboration between home and host supervisory authorities in the SSA region—especially in jurisdictions where the foreign bank affiliates are systemically important. The domestic supervisory authorities thus need to effectively manage the inherent trade-off between reaping the benefits from international financial integration while effectively safeguarding domestic banking systems against cross-border contagion and fragility.
Keywords: Bank stability; Consolidated supervision; Cross-border banks; Home-host countries; Systemically important

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
URI: https://repository.up.ac.za/handle/2263/97005
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

Evaluation of Revenue Effect from Tax Components and Economic Growth in Nigeria - Atuma, Emeka; David, Amarachi; Nwibo, Nneamaka; Nkwagu, Chibuike; Udenta, Blessing; Njim, Sunday; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
This research empirically examined the relationship between tax revenue and economic growth in Nigeria for the period 1994-2021. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates long-run and short-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between tax revenue and economic growth in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally showed that both company income tax and value added tax were statistically significant and positively related to economic growth in Nigeria in both shot-run and long-run periods; whereas personal income tax was statistically insignificant and positively related to economic growth in Nigeria in both short-run and long-run. Based on the findings, the study therefore recommended tax authorities responsible for tax administration should upgrade the tax database to capture all potential tax-payers in order to broaden tax income.
Keywords: Autoregressive Distributed Lag Mode; Economic growth; Nigeria; Tax Revenue

Re-Evaluation of the Effectiveness of Exchange Rate Depreciation on Import Demand in Nigeria - Atuma, Emeka; Ebuka, Bright; Nwibo, Fidelia; Nkwagu, Christain; Nancy, Udenta; Njim, Robert; Ogbonna, Nkemdirim; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
The study investigated the impact of exchange rate depreciation on import demand in Nigeria from 1986 to 2021. The data used was sourced from Central Bank of Nigeria. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates short-run and long-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between exchange rate depreciation and import demand in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally found that exchange rate depreciation is statistically not significant and negatively impacted on import demand in Nigeria in the short-run. However, in the long-run, exchange rate depreciation is negatively impacted to import demand and statistically significant. Causal relationship does exist between exchange rate depreciation and import demand in Nigeria with causation running from import demand to exchange rate depreciation. On the basis of the findings, the researcher made the following recommendations among others: Government should consider inward looking to strengthen the imports substitution policies that ensure massive production of goods and services.
Keywords: Autoregressive Distributed Lag; Exchange Rate Depreciation; Import Demand; Mode; Nigeria

Digitalization and Tax Administration in the Gambia - Ogbeta, Oghenekevwe; Ayeni, Oluwadare (African Journal of Politics and Administrative Studies, 2024)
This study extensively explored the potential of digitalization in The Gambia Revenue Authority's tax administration, amidst concerns over the practical application of digital tools and their underutilization, which have hindered the realization of improved revenue mobilization and efficient tax processes in The Gambia. The research, adopting a mixed method design, aimed to understand the intricate relationship between digitalization and tax administration in The Gambia. With specific objectives, including identifying driving factors, examining effects, and evaluating the correlation with GRA's performance, the study adopted quantitative and qualitative analyses. Similarly, the study population is two thousand, one hundred and eighty-eight (2188). Using Krejcie and Morgan (1970) formula, out of 2188 population of the study, three hundred and twenty seven (327) were selected as the sample size. This encompassed individuals drawn from the Ministry of Finance and Economic Affairs, GRA staff, and corporate taxpayers using a stratified and proportionate-to-size sampling approach. Hypotheses analysis revealed a statistically significant and positive effect of digitalization on tax administration, indicating improved efficiency and GRA effectiveness. Also, Spearman's rank-order correlation affirmed a positive relationship between digitalization and tax administration. Furthermore, qualitative insights from stakeholder interviews highlighted drivers such as international financial body stipulations, modernization imperatives, trust-building, accurate record-keeping, and alignment with global standards. Recommendations include training programs for GRA staff, public awareness campaigns, and enhancing user experiences for e-payment systems, among others.
Keywords: Digitalization; Tax Administration; Tax Compliance; Tax Evasion; Taxation

The Relevance of IFRS Accounting Information: Evidence from a Pure IFRS Environment - Abu Alia, Muiz; Amarneh, Khairieh; Abdeljawad, Islam (An-Najah University Journal for Research - B (Humanities), 2024)
The International Financial Reporting Standards (IFRS) are supposed to raise the value relevance of accounting information and thus ensure its usefulness for users. Most of the studies on the relevance of IFRS-based accounting information were conducted in countries that had previous accounting standards before the adoption of IFRS. However, the relevance of accounting information is influenced by the accounting traditions inherited from previous practices. This study provides distinctive evidence on the relevance of IFRS accounting information by examining the association between accounting information prepared by Palestinian companies and share prices. Palestine represents a pure IFRS environment since IFRS is its first financial reporting framework. The study estimates the impact of accounting information, including book value of equity per share, earnings per share, and operating cash flow per share, on the market value of the share. Totally, the results show that the accounting numbers prepared by Palestinian companies are relevant. Precisely, earnings per share and book value of equity per share are the important variables in determining the share market value. Notwithstanding, no significant impact of operating cash flow per share has been observed. Moreover, evidence supporting the existence of conformity and predictive relevance is obtained, but the overall predictive relevance is higher. To enhance the relevance of IFRS information, this paper recommends local regulators and policymakers to work on improving the readiness of the Palestinian environment to fully benefit from the adoption of IFRS. On the other hand, the International Accounting Standards Board should adequately consider the circumstances prevailing in underdeveloped countries when issuing its standards. For future research, larger samples from several countries with different prevailing factors should provide insights into the mechanisms of the relationship between book and market values.
Keywords: Conformity Value; IFRS; Predictive Value; The Palestine Exchange; Value Relevance

Evaluating bank technical efficiency in SADC region - Abel, Sanderson; Mukarati, Julius; Manenge, Robson; Le Roux, Pierre (Heliyon, 2024)
Efficiency is generally defined as the capacity to deliver desirable results with little effort or input. A bank cannot afford to allocate limited resources at random in a competitive market. Only once the efficiency factors have been identified can resources be allocated in a conscious and effective manner. The study investigates the determinants of technical efficiency of banks in the SADC region. The study is significant in the SADC region as the block is trying to create a robust and stable banking system. This is driven by the desire to stay away from the current global financial system volatility and the region is working to develop an integrated banking system. The results show that the banks are relatively inefficient with the level of inefficiency around 40 percent. The efficiency of the banks is determined by the level of capitalisation, size of the bank, research costs and automation of the banks. The results of the study imply that that there is great scope for the banks in the SADC region to increase their efficiency. Improved efficiency will ensure banks provide services at a lower cost to clients. The study recommends adequately capitalizing banks, increasing the asset base of the banks, investing in research and the automation of the banking systems.
Keywords: Banks; Capitalisation; Data envelopment analysis; Technical efficiency; Tobit

Corporate Income Tax (CIT) and Capital - Agossadou, Stanislas Théodule Médard Dèwanou Comlan (International Journal of Accounting, Finance, Auditing, Management and Economics, 2024)
This research consists of verifying whether CIT has an effect on capital given the financing risk incurred. A review of several capital theories has shown that CIT is one of the main determinants of a firm's capital structure. The inclusion of CIT in capital structure models continues to divide the world of corporate finance. Debt interest deduction in computing CIT reinforces the controversy over the question of the capital structure that optimizes the tax savings provided by this deduction. The consequence is the existence of two opposing groups on the optimum capital structure: on the one hand, the group of those who believe that there is one and only one optimal capital structure, and on the other, the group of those who reject out of hand any possibility of an optimal capital structure. The sample starts with a case study of two hypothetical identical firms, one indebted and the other non-indebted, with the same profitable investment project over a period of time, and ends with 101 pairs of identical firms belonging to different classes of financing risk. The hypothesis of non-gratuity of cost and income is used, and capital markets are assumed to be pure and perfect. The results confirm that CIT has no effect on the structure, value, cost and return of capital for a given financing risk, and reveal the existence of a third source of financing called "public capital", whose cost is the corporate capital tax rate (CCTR). There is no longer any question of thinking about the optimum capital structure, which is a pure financial illusion. This paper is one of the first to show that CIT does not affect capital, and to propose a model that explains capital structure behavior in the presence of CIT. Paper type: Empirical Research Stanislas Théodule Médard Dèwanou Comlan AGOSSADOU, (Researcher) Laboratory for Research on Performance and Development of Organizations (LARPEDO) Faculty of Economics and Management (FASEG) University of Abomey-Calavi (UAC) - Benin,
Keywords: Capital structure; Financial integration of corporate tax; Firm value; Return on investment; Weighted average cost of capital (WACC)

Aspects of substantial compliance and strict compliance as applied to demand guarantees - Sikobi, Nkanyiso (University of South Africa, 2024)
Demand guarantees are essential for purposes of commerce and are used to secure the performance of the contractor. South African courts have held that demand guarantees are akin to letters of credit. Despite the independent nature of demand guarantees to the underlying contract, in circumstances where the beneficiary has made a fraudulent claim, the guarantor may dishonour the demand or claim. South African courts have indicated that if the underlying contract is illegal, courts may intervene by granting an interdict to stop payment under the guarantee. The South African law recognises traditional guarantees (often called suretyship) where the beneficiary, when making a demand or claim, must demonstrate liability on the part of the contractor. There are instances where courts have held that guarantees were of a nature akin to suretyship. In South Africa, parties entering into a demand guarantee contract are subject to the common law of contract. The Uniform Rules for Demand Guarantees, adopted by the International Chamber of Commerce, are only applied by explicit reference in the demand guarantee failing which such rules do not apply. Non-implementation of these rules has resulted in rigorous litigation in the recent years on this subject-matter. A demand must be supported by documents and require strict conformity. However, strict compliance with the prerequisites of the demand guarantee has not been applied consistently in South Africa. South African courts have recently been applying substantial compliance, in certain circumstances finding that a term in a guarantee is just directory and not obligatory. Furthermore, on many occasions, courts have deviated from strict compliance holding that a term in a guarantee does not make commercial sense thus such term is not mandatory. In this way, courts apply the most business-sensible interpretation when interpreting demand guarantees.
Keywords: Autonomous; Beneficiary; Contractor; Demand guarantees; Demand or conditional guarantee; Documentary letters of credit; Employer; First written demand; Fraud and illegality exception; Guarantor; Independence; Performance guarantees; Security for performance; Strict compliance; Substantial compliance; Suretyship; Underlying contract; Uniform rules for demand guarantees

A bibliometric review of IFRS adoption and compliance research in Africa - Effah, Nana Adwoa Anokye (Journal of Business and Socio-economic Development, 2024)
Purpose This article aims to identify and review existing studies on the adoption and compliance of Internat ional Financial Reporting Standards (IFRS) in Africa. Design/methodology/approach The methodology involves a sole focus on studies conducted with an African sample, using a bibliometric method and data from the Web of Science (WoS) database. Visualizations from VOSViewer and Biblioshiny software are employed to identify the dominant authors, journals and countries contributing to research in the region. Findings The findings reveal existing collaborations among authors in the field. However, the study emphasizes the need for additional research to enhance the intellectual structure of the research domain, as the majority of related documents are concentrated within twenty articles with at least one citation. Practical implications The practical implications underscore the importance of collaboration in practice, emphasizing the need for cooperation among corporations, experts and regulatory agencies involved in IFRS adoption and compliance in Africa. By fostering collaborative efforts and knowledge-sharing among corporations, experts and regulatory agencies, practitioners can enhance their understanding, streamline implementation processes and improve compliance methods. Originality/value This review is one of the few to explicitly conduct a bibliometric review of IFRS adoption and compliance studies in Africa, providing a foundation for future research to determine the current direction of IFRS studies in this region.
Keywords: Africa; IFRS adoption; IFRS compliance; Web of science database

Tax Behavior and Financing Behavior of Corporate Managers: Case of Banks and Decentralized Financial Systems (DFSs) in Benin - Agossadou, Stanislas T. Médard D. C. (Journal of Economics, Finance and Management, 2024)
This paper aims to analyzing the influence of tax behavior on financing (financial leverage) behavior of corporate managers. The paper applies the generalized method of moments (GMM) to dynamic panel data. The sample used covers 21 firms, i.e. 11 banks for the period from 2011 to 2020 and 10 DFSs for the period from 2016 to 2021. It turns out that financial leverage behavior is influenced more positively by corporate income tax (CIT), then by dividends (DIVIDEND); and negatively by interest on debt (INTEREST), by cash flow (CASH_FLOW) and by past financial leverage (LEVERAGE(‑1)). This paper is one of the first to extend the literature by identifying the main determinants of financing behavior, notably the positive effect of corporate income tax (CIT).
Keywords: Corporate income tax behavior; Corporate income tax savings; Financial objectives; Leverage behavior; Tax objectives

Taxing the digital economy: Options available for African countries - Oluwatuyi, Oluwasikemi (University of Victoria, 2024)
Tax authorities have always assessed and enforced taxes based on the physical address of businesses over the years. Nevertheless, the idea of tax jurisdiction has taken on a new meaning with the development of information and communication technology, and its profound impact on every facet of human existence – including but not restricted to trade and business. This development has undoubtedly increased capital mobility, especially in corporate form, and exposed more the weaknesses in national tax laws by enabling the artificial relocation of important economic components and potential exemption from taxes. Since it is getting harder to separate the digital economy from the rest of the economy for taxation reasons, the process of digitalization has emerged as one of the primary growth drivers. This expansion, together with aggressive tax planning strategies used by multinational enterprises (MNEs) to move revenues to low-tax jurisdictions and the development of business models requiring less physical presence, has increased the workload for tax administrators; furthermore, it has reduced governments’ capacity to raise funds in the traditional manner. In this regard, I assess how “adequate” the selected African countries’ frameworks are vis-à-vis the ongoing OECD and UN negotiations. Beyond the consultations, I call for a more inclusive and Africanised approach and the need for African countries to improve their tax administration mechanisms.
https://hdl.handle.net/1828/20312
Keywords: Digital economy; International taxation; OECD; Tax

A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

The impacts of IFRS 16 on airlines - Ribeiro, José; Ribeiro, Francisco; Ribeiro, Fernando (Accounting and Management Review | Revista de Contabilidade e Gestão, 2023)
This study addresses the effects of the adoption of IFRS 16 on the passenger air transport sector. With practical effects for financial years beginning on or after 1 January 2019, IFRS 16 established the standardisation of a single accounting modelfor all leases, whether operating or financial. With this new adoption, IFRS 16 aims to increase the transparency and quality of the information that is presented in the financial statements for the most diverse stakeholders. This study aimed to assess the effects of adopting this new international standard in a specific sector and to identify whether the changes in some of the financial indicators are felt in the same way by all companies, this being the main focus of this study. Based on a sample of 12 airlines from various countries in Europe and South America, the financial indicators were interpreted by analysing the reports and accounts before and after the application of IFRS 16. The main conclusions obtained are: i) the adoption of IFRS 16 led to an increase in assets, liabilities and EBITDA, however in different proportions for each of these items; ii) companies with negative equity and, therefore, with greater risks of bankruptcy or greater information asymmetry, tend to resort more to leasing as a way of financing their assets; iii) the financial autonomy and solvency ratios showed significant variations for companies that resort more to operating leasing.
Keywords: Airline industry; Finance leases; IFRS 16; Information asymmetry.

Prospects for an African continental model multilateral tax agreement for the co-ordination of cross-border corporate tax challenges - Fehun Aren, Marie-Louise (University of Pretoria, 2023)
This study explores the creation of an African Continental Model Multilateral Tax Agreement (MMTA) to address the limitations of current bilateral tax treaties and enhance existing African Regional Economic Community (REC) frameworks for more effective taxation of cross-border business profits. Focusing on critical international taxation framework issues such as taxing rights allocation, Permanent Establishment criteria, and tax dispute resolution, it compares African REC MMTA provisions with those in non-African agreements to identify key weaknesses and propose improvements. The proposed MMTA aims to ensure equitable taxing rights, update nexus rules to capture both physical and digital businesses, and provide robust dispute resolution mechanisms to foster investment. It advocates for harmonized tax policies and tax agreements across African RECs to minimize tax competition, promote intra-African trade, and support regional economic integration under the African Continental Free Trade Area (AfCFTA). By aligning with the Abuja Treaty’s objectives, the framework seeks to enhance revenue mobilization and sustainable economic development in Africa. This research provides a roadmap for creating a tailored multilateral tax treaty that balances diverse regional interests, addressing Africa’s development financing needs while promoting cross-border taxation efficiency.
Keywords: AfCFTA; African Continental Free Trade Area; Continental model; International taxation frameworks; Multilateral tax agreement; Revenue mobilisation; Tax treaties

Earnings Management and Default Risk - Nguyen, Loan (Victoria University of Wellington, 2023)
This thesis comprehensively investigates the relationship between default risk (DR) and earnings management (EM) by addressing inconsistencies in prior research regarding the level and direction of EM in response to varying levels of DR. The thesis extends beyond severe financial distress to include firms with low and medium levels of distress. It examines the non-monotonic relationship between DR and EM, considering accrual earnings management (AEM), real earnings management (REM), and total earnings management (TEM). The thesis also examines the impact of DR on the relative use of REM versus AEM. The moderating effect of the global financial crisis (GFC) on the relationship between DR and EM is also explored.Using a sample of 29,228 firm-year observations from 4,514 US-listed firms during 2001-2019, the study employs both the traditional two-step and the more recent one-step approaches to identify EM. Sensitivity analysis is conducted, including and excluding mining firms.The findings reveal a non-monotonic relationship between DR and REM, with a concave pattern observed for all measures of REM. Initially, REM increases as DR rises, but it subsequently declines with further increases in DR. AEM, on the other hand, shows a convex or monotonically decreasing relationship with DR, although statistical significance is not consistently observed. The results for TEM align with those of REM, indicating the dominance of REM in TEM. These findings remain consistent when excluding mining industry observations and using different measures for EM and DR.The implications of these findings are significant for managers, firms, regulators, lenders, investors, and other stakeholders. The non-monotonic relationship between DR and REM offers insights for decision-making and determining appropriate levels of EM during varying levels of DR. Regulators can utilise this relationship to identify potential risk areas and develop effective regulations. Lenders can assess financial statements more vigilantly, and investors can make more accurate risk assessments and informed investment decisions. The robustness of the results and the inclusion of different EM measures provide valuable insights to auditors, analysts, and government professionals, enhancing their understanding of the complexities and risks associated with EM during varying levels of DR.The study also uncovers that the relative use of AEM and REM is complimentary, but the impact of DR dampens the increase in REM for a given increase in AEM. This result holds across primary and alternative measures of DR and is of significant interest to managers, firms, regulators, and other stakeholders. It provides insights into the interplay between AEM and REM, enabling informed decisions about EM strategies under different levels of DR. Regulators can leverage this information to identify potential risk areas and develop effective regulations to mitigate EM practices that could lead to financial instability. Lenders and investors benefit from understanding how DR affects the relative use of AEM and REM, enabling them to assess financial statements and manage investment risk more accurately. The study’s findings contribute to a deeper understanding of EM dynamics and have practical implications for various stakeholders in the financial ecosystem.Furthermore, the thesis investigates EM measures during the GFC and the moderating effect of the GFC on the relationship between DR and EM. The inclusion of REM and TEM, in addition to AEM, provides a comprehensive understanding of how firms managed their earnings during the GFC, offering insights into the effectiveness and implications of different EM strategies during a financial crisis. It confirms the decline of AEM during the GFC, reinforcing existing knowledge about the impact of the crisis on EM practices. Additionally, it identifies a negative impact of the GFC on REM and TEM, providing further evidence of the challenges and changes in EM strategies faced by firms during the economic crisis. The study also finds an insignificant moderating effect of the GFC on the relationship between DR and REM, as well as DR and TEM, shedding light on EM variation across different economic stages.Overall, this thesis contributes to the EM literature by examining the non-monotonic impact of DR on EM measures, comparing different approaches to identify EM, exploring the moderating effect of DR on the relative use of AEM and REM, and investigating EM measures during the GFC. The insights from this research assist managers in decision-making, firms in adapting financial management strategies, regulators in developing policies, lenders in risk assessment, and investors in understanding the complexities and risks associated with EM. The findings have practical implications for various stakeholders in the financial realm, guiding decision-making, regulatory efforts, risk assessment, and investment strategies.Keywords: earnings management, accruals earnings management, real earnings management, default risk, global financial crisis, one-step approach, two-step approach.

Corporate Finance, Governance, and Social Responsibility - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers 27 papers published in the Special Issue entitled Corporate Finance, Governance, and Social Responsibility, which examines several topics related to corporate finance, financial modeling, corporate governance, and corporate social responsibility. Corporate finance-related articles (Anton and Afloarei Nucu, 2021; Bae et al., 2023; Kedzior et al., 2020; Lts and Lukason, 2022; Miglo, 2020; Mihail et al., 2021; Mota and Moreira, 2023; Tsolas, 2021; Tudose et al., 2021; and Wen et al., 2021) focus on the drivers of the capital structure and firm performance, the effect of working capital management on profitability, and the link between derivative use and profitability. Regarding financial modeling, stock market volatility was explored during COVID-19 (Gherghina et al., 2021). Corporate governance studies (Aluchna and Kuszewski, 2020; Ararat et al., 2021; Ding and Chea, 2021; Kjrland et al., 2020; Loureno et al., 2021; Lukason and Camacho-Miano, 2020; Maier and Yurtoglu, 2022; Mihail and Dumitrescu, 2021; Mihail et al., 2022; Mihail and Micu, 2021; and Pourmansouri et al., 2022) examine the effect of corporate governance compliance practices, board attributes, or employee stock option plans on bankruptcy risk, performance, firm value, or earnings management. Regarding CSR (Bozos et al., 2022; Rossi et al., 2021; Saeed and Sroufe, 2021; Singh and Hong, 2023; and Tseng and Shih, 2022), the research focuses on how CSR affects financial performance, risk management, or analyst profits estimates.
Keywords: CSR; Corporate Finance; Financial performance

Artificial Intelligence: Challenges and Opportunities for the Accounting Profession in Nigeria - Nkwede, Maria; Aniuga, Chukwuma (African Journal of Politics and Administrative Studies, 2023)
Artificial intelligence with its fifth industrial revolution is fast griping the African continent. The emergence and adoption of artificial intelligence applications and systems is fast becoming a normal trend in emerging markets landscape across Africa. This paper is borne out of the need to identify challenges that professional grapple with in their quest to surmount the challenges posed by the realities of artificial intelligence applications in Africa. The study adopted the thematic style in presenting the challenges as well as the prospects of artificial intelligence applications for the accounting professional in emerging market. Some of the challenges of artificial intelligence application identified in this study include: complex algorithms, reduced investment, and software failure, lack of political will and limitations amongst others. On the other hand, opportunities of artificial intelligence in emerging market include transportation automation, technological cyborgs and robotic companions amongst others. From the findings, accounting professional are advised to strive harder in order to beat competition by delivering quality services to her clients through harnessing opportunities for rebranding, reengineering and radically improving the business and investment decisions which is the ultimate purpose of the profession. More so, they are encouraged to develop a novel set of proficiency revolving around data in the profession
Keywords: AI; Accounting Profession; Artificial Intelligence; Challenges; Fifth Industrial Revolution; Inteligência artificial; Intelligence Artificielle; Opportunities

Saudi Banks Level of Compliance with Accounting Standards of Accounting and Auditing Organization for Islamic Financial Institutions - A. Al-Bogami, S. (Information Sciences Letters, 2023)

The Relation between Corporate Governance, Risk Management and Financial Performance: Theoretical and Analytics Framework - Ayoob Mohammed Hassan, Noora; Din, Badariah binti Haji; Senasi, Vally (Information Sciences Letters, 2023)
The paper aims to review the relation between Corporate Governance, Risk Management and Performance. We reviewed these variables and develop a Theoretical and Analytics framework. First introduction (study background, Problem Statement, Research Objectives and research questions). Second literature review (A) financial performance such as ROA, ROE, EPS and Tobin’s Q, (B) Corporate Governance as Board of Directors, Board Composition, CEO Duality and Board Size (C) Risk Management. Third, we discussed Underpinning Theories such as, Agency Theory and Institutional Theory. Fourth, we developed a Theoretical Framework where we illustrated (A) Corporate Governance and Financial Performance, (B) Risk Management and Financial Performance (C) Compliance with Accounting Standards and Financial Performance. Finally, we developed a comprehensive reviewing based on above variables.
Keywords: Corporate governance; Performance; Risk Management

Influence of Training, Experience, and Expertise on Quality of Financial Reporting in Dubai – Mediation of Adoption of International Public Sector Accounting Standards - IPSAS - El Haron, Esam O.; Haji Din, Badariah (Information Sciences Letters, 2023)

Accounting Choices During COVID 19 Pandemic: Does Corporate Strategy and Corporate Social Responsibility Matter? - T. Hassan, N. (Information Sciences Letters, 2023)
This study aims to understand the accounting effects of the Corona pandemic in more depth and clarity, where the study explores the accounting choices during the pandemic period and the impact of the firm's strategic orientation and its social responsibility performance on those choices. Using data from non-financial Saudi companies, the accounting choices divided into aggressive accounting strategy and conservative accounting strategy, and regression models used to examine the study hypotheses. The results of the study provide a clearer and in-depth vision about the nature of accounting practices during the pandemic and indicated that business strategy affects accounting choices, while corporate social responsibility does not affect. The results can imply useful information for the market regulators that help them in controlling and stabilizing the market, as well as for professional accounting organizations to help them issue guidelines for accounting work during crises.
Keywords: Accounting choices; CSR; Corporate Social Responsibility; Corporate strategy; Covid-19 pandemic; Saudi companies

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

Banking System Fragility in Nigeria: Hanging on the Precipice? - Kayode, Peter; Oluwole, Foluso (AAU Journal of Business and Law, 2023)
The health of a country’s banking system is a key determinant to the development of the country. A fragile banking system portends danger not only to the financial system but the entire economy. This study investigates the state of the Nigerian banking system in terms of stability or fragility from 1981 to 2020. We used the banking system fragility index (BSFI) proposed by Kibritçioğlu (2003) to analyze Nigerian banking industry aggregate data from three risk areas: credit, market and liquidity. We estimated that out of the 40 years examined, the banking system was fragile for 23 years given their BSFI less than 0 while it was not fragile for 17 years with BSFI = 0 or greater. We found that most of the years when the Nigerian banking system was fragile were periods of relaxed monetary policies, deregulation and credit expansion. Secondly, the years of banking system stability were when the county’s banking system was subjected to stiff regulation and consolidation. Given the number of years that the system was fragile, we observed that sustained economic growth and development requires that the banking system remain strong as long as possible, and that the Nigerian situation could not promote this important objective. We recommend that the financial regulatory authorities put in place more stringent policies as banks are more fragile during the deregulation of the banking industry.
AAU Journal of Business and Law مجلة جامعة العين للأعمال والقانون
Keywords: Banking system fragility; Precipice

The adoption of international financial reporting standards and foreign direct investment inflows: the moderating effect of the institutional environment in Africa - Simbi, Chipo (Rhodes University; Faculty of Commerce, Accounting, 2023)
Globalisation has created a need for an international accounting language to facilitate the smooth flow of trade across countries. In 2003, in an effort to establish a global financial reporting language, the International Accounting Standards Board (IASB) developed a single set of high-quality accounting principles known as the International Financial Reporting Standards (IFRS). Over the last decade, several African countries have adopted IFRS, and Africa has become the second-largest adopting continent after Europe. IFRS promotes improved quality of disclosure of accounting transactions, reduces information asymmetry between preparers and users of financial information, lowers the cost of investing, and breaks down information barriers to cross-border investment. Researchers suggest many benefits of IFRS adoption for macroeconomic indicators such as Foreign Direct Investment (FDI). The reduction in information acquisition and processing costs which translates into the reduction in investment costs, has been cited by most researchers. Researchers have argued, however, that the economic benefits of IFRS in Africa depend on the strength of the institutional environment. They also argue that the Western environment in which the IFRS was developed differs from the African environment. Thus, the universal approach of the IASB may not be appropriate due to the historical, social, economic and political context of African countries. The impact of the adoption of IFRS by African countries requires further examination, particularly as a weak institutional environment confronts many African countries. Three research questions are designed for this study; (1) Is there a significant change in FDI inflows for IFRS adopters in selected African countries after the adoption? (2) Is there a significant change in FDI inflows due to the institutional environment? (3) Does the institutional environment in IFRS-adopting countries moderate the effect of IFRS on FDI in selected African countries? The present study is underpinned by the new institutional theory, the information asymmetry theory, the eclectic theory and the signalling theory, each of which provide reasons why African countries have adopted IFRS. Nine hypotheses are developed, based on the research questions, and tested using the Systems General Method of Moments and the Difference-in-Difference method. The study uses data from 26 African countries, 15 adopting and 11 non-adopting countries, over the period 1996 - 2018. First, the study establishes that the adoption of IFRS positively and significantly affects FDI inflows into the selected sample of African countries. Second, the study concludes that legal enforcement, accounting and auditing standards enforcement, and language origin positively and significantly impact FDI inflows into these countries. Legal origin, however, has a positive but insignificant association with FDI inflows. Third, legal enforcement, historical ties, accounting and auditing enforcement and the quality of the institutional environment are found to moderate the effect of IFRS adoption on FDI inflows. These results indicate that IFRS is a crucial determinant of FDI inflows into African countries, but a supportive institutional environment is needed for African countries to attract FDI inflows after adoption. The results contribute to the accounting and finance literature on FDI into African countries, and may assist the investment community to assess the institutional risk associated with investing in IFRS adopting African countries.
http://hdl.handle.net/10962/419230
Keywords: Accounting; Auditing; Difference in differences; FDI; Foreign direct investment; Generalized method of moments; IFRS adoption; Institutional infrastructure; International Financial Reporting Standards; Investments

Situation of Earning Management After Revision of the Ohada Accounting Standards Adopted on January 26, 2017 - Georges, Wandji; Nebasi, Akoso Wilfred (Law and Economy, 2022)
Following the mandatory adoption of the revised OHADA Accounting Standards that have moved closer to the International Financial Reporting Standards (IFRS), this study examines whether the level of Earnings Management of Companies making public offers or listed firms, in the West African Stock Exchange Market Abidjan-Ivory Coast (BRVM) has reduced. The study avails of Financial Statement figures during pre-adoption (2014–2017) and post-adoption (2018–2021) periods, for 26 selected listed firms in the BRVM. Findings suggest that firms in the post-adoption period of the revised OHADA Accounting Standards (2018–2021) are less likely to smooth earnings compared to the pre-adoption period (2014–2017). This indicates that adopting accounting standards of higher quality can bring an improvement in Financial Reporting Quality, everything being equal.
Number: 4
Keywords: Earnings management; IFRS; International Financial Reporting Accounting Standards (IFRS); Revised OHADA Accounting Standards; SYSCOHADA

Impact of Lack of Self-efficiency and Assets Evaluation on Resistance of IPSAS Implementation - Alhuda Tawffek Al-otoom, Nour; Alrabba, Hussein Mohammed (Information Sciences Letters, 2022)
This study examines factors influencing the international public sector accounting standards (IPSAS) implementation and presenting of accounting information related to the Jordanian public sector, also the information of reports is based on “Accounting principles and practices (No.39/1962) among government accountants. This study identified several important factors influencing the IPSAS implementation which are; lack of self-efficiency and assets evaluation. In addition, a quantitative approach was employed by distributed the questionnaires to 100 respondents enrolled at Jordanian General Budget Department using simple random sampling. The data were analyzed using SPSS to verify the relationships between the variables. The results found significant positive relationships between lack of self-efficiency and assets evaluation and IPSAS implementation resistance among government accountant in the public sector of Jordan. To sum up, this study contributes in expanding the literature concerning IPSAS implementation in Jordanian context, it’s also provides meaningful guideline to the government of Jordan for IPSAS implementation resistance. Finally, providing insights on the critical success factors to ensure successful implementation process.
Keywords: Accrual Accounting; Assets Evaluation; IPSASs; Public Sector Accounting; Self-efficiency

Comparison of IAS/IFRS and OHADA standards in terms of taking inflation into account in financial accounting - Matofali, Victoire (Revue du Contrôle de la Comptabilité et de l’Audit, 2022)
Financial accounting is one of the indispensable management tools in an organization, its objective is to present financial statements that reflect a true and fair view of the assets, financial position and results of the entity. In times of high inflation, however, money loses its purchasing power at such a rate that comparing amounts resulting from transactions and other events that occurred at different times, even during the same accounting period, can be misleading. This can cause the figures in the financial statements to be misleading. It is therefore essential to adjust these figures to the actual economic conditions in order to preserve a true and fair view of the company's assets, financial position and results. International financial standards such as those of OHADA analyze this problem of inflation in accounting through different methods of restatement of the figures of the financial statements to make them faithful and consistent with the economic reality. In this work, we will identify the points of divergence as well as the points of convergence between OHADA and IAS/IFRS accounting standards in terms of inflation accounting.
CERN European Organization for Nuclear Research
Keywords: Accounting; IAS/IFRS; Inflation; Standardization

An examination of the challenges posed by the internet economy for the South African income tax regime - Odhiambo, Oluoch Rodney (University of South Africa, 2022)
The way of doing business has changed significantly since the turn of this century due to the growth of internet technology and the global digital economy. This growth has reduced the importance traditionally attached to tangible assets and physical location in both commerce and taxation. This implies that any country that relies on physical presence to trigger tax liability in today’s digital economy may be forced to reconsider the relevance, effectiveness, and efficiency of its income tax legislation. This thesis postulates that South Africa’s income tax law and the international taxation principles it relies on in taxing cross-border and digital transactions have not grown in tandem with the changing landscape of today’s digital economy. The thesis contends that South Africa will not receive its fair share of tax from giant multinational enterprises such as Google, Facebook, and Amazon which operate and trade in the country, if it does not amend its income tax laws to address the challenges posed by the internet economy. In examining the challenges posed by the internet economy to South Africa’s income tax regime, the thesis commences in Chapter 2 by discussing the growth of the digital economy and its implications for South Africa’s income tax system. Chapter 3 offers a critical analysis of South Africa’s income tax laws and the international principles on which they rely in taxing the digital economy. Chapter 4 discusses the measures that South Africa’s government has taken to tax its digital economy, while Chapter 5 compares how the Organization for Economic Cooperation and Development (OECD), the European Union (EU), Kenya, India, and New Zealand have dealt with the issue of taxing the digital economy and the lessons to be learned from these jurisdictions. The thesis concludes in Chapter 6 by proposing recommendations that South Africa could consider to make its income tax regime more efficient and effective in taxing transactions that take place in today’s digitised economy.
Keywords: Cryptocurrency; Digital economy; Digital tax; E-commerce; E-signature; Electronic commerce; Formulary apportionment; Income tax; Internet industry; Signature électronique; Taxation; Virtual currency

Innovative Approaches for Tackling Tax Evasion in the South African Minibus Taxi Industry: Lessons from Ghana, Zambia, and Zimbabwe - Ndlovu, Jane; Mohale, Enhle (Journal of Law, Society and Development, 2022)
In South Africa, minibus taxis are a crucial mode of public transport for many commuters and a vital informal business sector with an estimated value of R90 billion. Concerns have been raised that the South African Revenue Service (SARS) is not collecting the optimal amount of tax revenue from this industry, with estimated tax collection at only R5 million in 2021. As a result of concerns that this industry might be involved in tax evasion or massive tax avoidance, this study investigates the taxation of minibus taxis in South Africa and explores alternative tax regimes that could be implemented to improve revenue collection. The study compares the current South African turnover tax system for minibus taxi operators to other African tax systems and evaluates a viable alternative tax regime or tax collection system. To improve tax collection from the industry, South Africa could consider a tax system tailored to the industry’s informal nature, utilising metrics such as vehicle seating capacity or distance travelled. A standardised tax system for small, medium, and micro enterprises may not be suitable. Consultation with industry stakeholders is essential for the proposed tax system to be acceptable. The study’s findings could inform South Africa’s National Treasury in creating a tax structure or collection scheme targeting the minibus taxi industry. This could increase tax revenue collection from the industry and support government expenditure, including income and wealth redistribution. This study distinguishes itself from prior publications on the South African minibus taxi industry by addressing tax compliance and collection challenges. It offers recommendations for alternative tax regimes to mitigate these challenges.
Keywords: Informal sector; Micro-enterprises; Minibus taxi; Presumptive tax; Tax relief; Turnover tax

Does the implementation of IFRS improve transparency regarding the company's financial conditions?: evidence from an emerging market - Ebaid, Ibrahim El-Sayed (PSU Research Review, 2022)
Purpose This study aims to examine whether there are differences between financial statements prepared in accordance with International Financial Reporting Standards (IFRS) and financial statements prepared in accordance with local accounting standards in terms of its ability to present the financial conditions of companies listed on the Saudi Stock Exchange as one of the emerging markets. Design/methodology/approach Data on study variables were obtained from the published financial statements of 67 of listed companies in the Saudi Stock Exchange during the period 2014–2019. The study addressed the research hypotheses by using Altman Z-score model. Both the T-test and Wilcoxon rank test were used to investigate the significance of differences between the values of Z-score and the individual variables included in the model in the pre- and post-IFRS mandatory adoption periods. Findings The results revealed a decrease in the values of Z-score as well as the values of the individual variables included in the model in the period following the adoption of IFRS than it was before the adoption of IFRS, which indicates the ability of IFRS to show the financial conditions of companies more transparently than local accounting standards. However, the results of the T-test and Wilcoxon test showed that these decreases were not statistically significant. Research limitations/implications This study has some limitations, including the small sample size as a result of the small size of the Saudi Stock Exchange, As well as the reliance of this study only on the Altman model with its five variables in assessing financial conditions without examining the impact of other factors that may affect the financial conditions of companies. Practical implications Financial conditions of the companies have important implications for multiple parties such as management, government, investors and others as an early warning sign that enables them to take the necessary measures early before the actual bankruptcy occurs and what results in costs. Originality/value Although assessing financial conditions of the companies is one of the basic uses of accounting information, this topic has not received sufficient attention as a means to test the benefits of adopting IFRS, especially in emerging markets such as Saudi Stock Exchange. This is the first study to examine the impact of adopting IFRS on the transparency of financial reporting in assessing financial conditions in Saudi Arabia.
Keywords: Financial conditions; IFRS; Saudi Arabia; Z-score

Does the impact of IFRS on audit fees differ between early and late adopters? - Tawiah, Vincent Konadu (International Journal of Accounting & Information Management, 2022)
Purpose This study aims to examine whether the impact of international financial reporting standards (IFRS) on audit fees differs between early and late adopters. Design/methodology/approach The authors use robust econometric estimation on a sample of 314 firms from both early and late IFRS adopting countries. Findings The authors find that IFRS is positively and significantly associated with an increase in audit fees for early adopters, but the impact is very weak for late adopters and insignificant in some cases. The results on auditing time suggest that increase in audit fees around IFRS adoption is due to an increase in audit reporting lags. After accounting for pre- and post-years, the authors find that the relationship between IFRS and audit fees, as well as audit time for late adopters, is significant only in the adoption year. However, early adopters experience a significant increase in audit fees and audit time in the transition year to one-year post-adoption. Practical implications The findings imply that countries that are yet to adopt IFRS are less likely to experience a significant increase in audit fees audit time. Hence, is probable that the benefit of IFRS will outweigh the cost. Originality/value The results, therefore, suggest that early adopters paid a premium for been the first users of IFRS, which is consistent with any innovation. The study provides new insights by demonstrating that the consequences of IFRS differ between early and late adopters.
Keywords: Africa; Audit fees; Audit reporting lags; Early adopters; IFRS; Late adopters

Accountability during the Incorporation of Public and Private Limited Companies under Ohada Law - Sama, Merinda Afanui (International Journal of Research and Innovation in Social Science, 2022)
This work sets out to evaluate the OHADA Uniform Act’s laws on accountability in Private and Public Limited Companies. Normally, laws which provide for effective accountability, guarantee the smooth functioning and stability of companies since its rules work at averting all forms of mismanagements. The inspiration of this work stems from the realization that, levels of accountability in these companies are still wanting. Hitherto, companies are plagued with vices of obscured activities, fake transactions, non-transparent reporting and acute dishonesty by its organs. It is therefore baffling that, these are still prevalent despite the existence of the Uniform Act’s laws which contains accountability mechanism aimed at dispelling all these forms of corporate transgressions. From this arose lingering doubts as to how these laws are.

Foreign Bank Penetration, Institutional Structures and Banking Sector Stability in Sub-saharan Africa - Abeka, Mac Junior (University of Cape Coast, 2022)
Link broken
Keywords: Bank penetration; Banking sector; Sub-Saharan Africa

Bank Bail-ins in International Investment Law - Duque-Cordero, Luciano (Universität Wien, 2022)
The global financial crisis led to the introduction of special resolution regimes for financial institutions. The most prominent innovation of these resolution regimes is the so-called bail-in tool, which allows regulators to recapitalise financial institutions by expropriating shareholders and creditors. This thesis analyses the conditions under which a hypothetical bail-in of a financial institution would constitute a compensable breach of international investment law. It identifies the issues that are most likely to be relevant if a bail-in were to be litigated before an investment arbitration tribunal. The thesis first addresses jurisdictional issues, in particular the question of whether bail-inable instruments can even be considered an investment in procedural terms. The analysis then continues to substantive standards of protection. It deals comprehensively with the question of expropriation and related issues such as compensation, the right to regulate, and causation. It concludes with possible violations of the fair and equitable treatment standard.
https://phaidra.univie.ac.at/detail/o:1417287
Keywords: Bail-in; Bank resolution; Expropriation; International Investment Law; Investments

Climate change and development : the global administrative law of the UNFCCC financial mechanism - Larrea, Gonzalo (European University Institute, 2022)
This research deals with the legal responsibility of states to provide climate finance to developing countries in order to facilitate climate mitigation and adaptation. The research demonstrates that the area of climate finance has not escaped globalization, where global actors operating at a level beyond the state (the UNFCCC and several Climate Funds) have increasingly taken over some of the climate finance functions previously performed by states. Against this backdrop, the thesis also examines the role of international bodies in providing climate finance, assesses to what extent these bodies are accountable to affected local stakeholders, and puts forward recommendations to foster increased accountability. The research project employs Global Administrative Law (GAL) as a normative framework for assessing and fostering accountability. This thesis is relevant, first and foremost, as an examination of the extent to which global climate finance is adequate for addressing climate change impacts in developing countries. To this end, it engages in a detailed analysis of the international legal framework for climate change and of the relevant financial instruments. It also engages in a normative evaluation of these instruments using the standards proposed by GAL. In keeping with this, the research gives substance and a better definition to these standards. As such, the thesis has the potential to contribute not only to the literature on climate finance, but also to the literature on GAL. It also sheds light on the relationship between climate finance and GAL, a topic that has been largely neglected in the academic literature so far.
Accepted: 2022-03-02T09:10:59Z
Keywords: Climate Change; Climatic changes; Environmental Law

Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

Four Essays on Tax Transition Reform in Developing Countries - Adandohoin, Kodjo (Université Clermont Auvergne, 2021)
Ces dernières années, la plupart des pays en développement sont confrontés à la nécessité de concilier deux impératifs : d’une part, une demande sociale forte qui nécessite un besoin de ressources publiques supplémentaires, et d’autre part le désarmement tarifaire consécutif aux politiques d’ouverture commerciale, qui les prive de la majeure partie de leurs recettes budgétaires. D’où l’impérieuse nécessité pour ces pays d’assurer une transition dans la structure de leur prélèvement public c’est à dire de transférer la pression fiscale du commerce extérieur vers la fiscalité domestique. Cette thèse s’intéresse à cette problématique et vise à étudier les conditions de réussite d’un tel phénomène dans les pays en développement au travers de quatre essais empiriques. Le premier essai concerne le rôle de la TVA et des droits d’accises dans une première vague de transition. La TVA étant un impôt neutre et à très large assiette fiscale, cette dernière a été suggérée comme outil majeur pour réussir le transfert des ressources publiques du cordon douanier vers la fiscalité domestique et en complémentarité avec les droits d’accises. Nos investigations empiriques soutiennent cette assertion théorique et montrent que le couple TVA-accise joue bien ce rôle de substitut aux recettes de porte en quasi baisse suite au démantèlement tarifaire dans les pays. Néanmoins le rôle d’appui de la TVA et des droits d’accises est limité à partir d’un certain seuil de baisse des recettes de porte, qui traduit aussi le fait que le potentiel de mobilisation fiscale par la TVA dans ces pays est limité et qu’il faudra s’en préoccuper. Dans le second essai nous analysons la transition de seconde génération basée sur les impôts directs (impôts sur les revenus et impôts fonciers). Nous trouvons que les impôts directs sont des outils pauvres de transition fiscale dans les pays en développement. Pourtant, nous trouvons que le développement financier est un médiateur certain et incontestable à une politique de transition fiscale de seconde génération basée sur les impôts directs, car permettant de recouper l’information sur les revenus des contribuables et de générer des traces documentaires à l’administration fiscale, qui permettent d’envisager une mise à fiscalisation des contribuables, gage de recettes fiscales directes supplémentaires dans les pays. Dans le troisième essai, nous nous intéressons à l’effet de la mise en place d’une réforme de transition fiscale sur l’efficience dans la collecte des recettes en menant une étude de cas pour l’union économique et monétaire ouest africaine (UEMOA). Nos résultats supportent l’affirmative, en ce sens que la réforme accroit globalement une mobilisation efficiente des recettes dans la zone UEMOA. Cette efficience entrainerait par ailleurs avec elle une amélioration du climat des affaires dans la zone, suite à la mise en place de cette réforme. Enfin nous terminons cette thèse par un quatrième essai qui interroge quand à lui les impacts distributifs et de pauvreté d’une réforme de transition fiscale basée sur la TVA. Quoique les résultats montrent une incidence régressive de la réforme sur le revenu des ménages, une redistribution par la dépense aurait le mérite d’atténuer l’incidence sociale de cette stratégie de réforme sur le revenu des contribuables.
Keywords: 2SLS-IV model; Accises; Administration fiscale; Analyse des frontières stochastiques; Business climate; Climat des affaires; Computable general equilibrium; Contrôle Synthétique; Coordination fiscale; Corporate tax; Developing countries; Développement financier; Efficience; Efficiency; Effort fiscal; Excise; Exemptions; Exonérations; Financial development; Fiscalité; GMM; Harmonisation; Harmonization; Impôt foncier; Impôt sur le revenu; Impôt sur les sociétés; Income tax; Inequality; Internet; Inégalités; Micro-simulation; Modèle 2SLS-IV; Pauvreté; Pays en développement; Politique fiscale – Pays en voie de développement; Potentiel fiscal; Poverty; Probit and Logit; Probit et Logit; Propensity scores; Property tax; Réforme fiscale; Scores de Propension; Stochastic frontier analysis; Synthetic control; TVA; Tax administration; Tax coordination; Tax effort; Tax potential; Tax reform; Tax transition; Taxation; Taxes sur le commerce extérieur; Trade taxes; Transition fiscale; VAT; Équilibre général calculable

Adoption des normes IFRS dans l’espace OHADA : Fondement théorique, intérêt et enjeux - Nyasseu, Emma Joachim; Yepdo, Florentin Gaël; Tatang Atabonfack, Pulchérie Léonie; Myskinole, Cheguem Shupo Davine (International Journal of Financial Accountability, Economics, Management, and Auditing, 2021)
Du fait des changements profonds qu’apportent les nouveaux concepts sur lesquels se base le référentiel de l’IASB, le passage aux normes IFRS a été qualifié d’une révolution comptable. Le but d’harmonisation de cette institution se réalise à travers la diffusion mondiale progressive des normes IFRS. Toutefois, les entreprises de la zone OHADA sont concernées par ce changement. Compte tenu de la rareté des travaux de recherche dans le domaine, nous essayons d’analyser à travers ce papier, l’adoption de telles normes en contexte OHADA. Pour y parvenir, cet article rappelle le mécanisme de passage aux normes IFRS dans l’espace OHADA, étudie ensuite l’intérêt pour les entreprises de cette zone et enfin met en évidence les enjeux liés à un tel projet. Les principaux résultats montrent que loin d’être un simple outil de présentation et de communication de l’information financière, les IFRS constituent pour les entreprises de la zone OHADA, un levier d’attraction des investisseurs et d’intégration économique.
Keywords: Normalisation comptable; Normes IFRS; OHADA; Référentiel; Révolution comptable

Firm Performance, Financial Constraints, and Dual-Class Share Structure - Ahamed, Fatematuz Tamanna (Victoria University of Wellington, 2021)
This thesis addresses two aspects of financial constraints focusing, firstly, on the impact of financial constraints on firm performance and, secondly, on the impact of dual-class share structure on financial constraints. The first issue has been addressed in a large number of research studies, but the results are mixed. This study, therefore, conducts a meta-analysis of those earlier studies to provide a summary view of the results which, in contrast to narrative reviews of the empirical literature, provides an objective overview. The second issue examines the impact of dual-class share structures on financial constraints. The period of the global financial crisis is used to test the impact of the state of the economy on that relationship. To examine the impact of financial constraints on firm performance, 26 empirical studies with 189 effect sizes representing listed firms have been analysed. The study finds that overall there is a positive relationship between financial constraints and firm performance. The study also shows that the set of market-based measures of firm performance has a significant negative impact on the relationship, compared with the set of accounting-based measures. In terms of the financial constraints measure, the set of external financial constraints measures have a positive and highly significant impact on the relationship. The meta-regression analysis suggests that the choice of measure, regional difference, journal quality and publication status all have a significant impact on the relationship, and explain the variation in the association. To examine the impact of dual-class share structures on financial constraints the study analyses a sample of non-financial US firms over the period 2002-2018. Share structure is measured by the existence of a dual-class structure and also by excess voting rights and the proximity of the superior class shareholders in such structures. The study also shows that if financial constraints are measured by the WW index, irrespective of how dual-class share structure is measured, it increases the level of financial constraints. Similar results are obtained where financial constraints are measured by the KZ and SA indexes, except where dual-class share structure is measured by the proximity of superior class shareholders. The study also finds that if financial constraints are measured by the WW index, dual-class had a reduced impact during the period of the global financial crisis, thus, providing support for the propping theory. However, if financial constraint is measured by the SA index, dual-class share structure appears to have an increased impact during the GFC years. Among the additional tests, the HM index has been used as a measure of financial constraints, and the findings show that the impact of dual-class structures on financial constraints appears to be driven by their effect on debt constraints. The study also shows that firm age moderates the impact of dual-class share structures if financial constraints are measured by the WW index. The KZ, WW, and SA indexes are based on firm characteristics and, therefore, the study also tests for an impact of dual-class structures when financial constraint is measured by a text-based index, the BLM index. However, the results do not provide evidence of an impact in that case.
Keywords: Dual-class share structure; Financial Accounting; Financial Constraints; Firm Performannce; Meta analysis

Value Relevance of Integrated Reporting using a Novel Approach: Comparative Cross Country Evidence of Mandatory and Voluntary Implementers - Mohaimen, F. J. (Victoria University of Wellington, 2021)
This thesis examines the value relevance of accounting information under integrated reporting (IR) in a comparative mandatory and voluntary setting. A meta review is conducted of all published work focusing on integrated reporting since 2011, which provides detailed insight into the gaps in the IR literature. Multiplicative log-linear model is used in measurement, which is a novel technique that mitigates the shortcomings of traditional value relevance models. The findings show that value relevance of summary accounting information increases after the implementation of IR in the mandatory setting. In the voluntary setting, market effect and the existing reporting paradigm effect the value relevance of accounting information under IR. If the market is large and existing reporting requirements are robust voluntary adoption of IR has minimal to no effect. However, in smaller markets with less rigorous reporting environment, adoption of IR does result in increased value relevance of accounting information. Compared to traditional models, the multiplicative model provides estimates that are more stable over time and shows better explanatory power. Overall, the findings of this thesis show that capital providers value the information content of IR under specific circumstances. This thesis contributes to the IR and value relevance literature by providing the first comparative cross-country evidence of the effect of IR in the change in value relevance of reported accounting information. It provides policy relevant input to the standard setters of IR by demonstrating the effect of IR in the decision usefulness of summary accounting information. The thesis further provides robust evidence of the efficacy of using the multiplicative log-linear model in measuring value relevance instead of the traditional linear additive models.

La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

Securities regulation, enforcement and market integration in the development of sub-Saharan Africa's capital markets - Aziza, Onoriode Reginald (University of Oxford, 2021)
This thesis examines securities market development in sub-Saharan Africa, focusing on securities law, securities law enforcement and securities markets integration. Adopting a primarily comparative methodology, the thesis examines the continued relevance of securities markets in sub-Saharan Africa; the way selected countries in the region regulate their markets and enforce compliance with securities law; and the potential of market integration to promote market development. This thesis advances 4 main claims. First, empirical evidence supports the link between liquid securities markets and economic growth, independent of the level of banking development. In this sense, securities markets can act as good complements to banks in providing capital to the real economy. Second, at the minimum, there is an arguable preliminary case that rules of securities regulation can hinder market development in select countries in sub-Saharan Africa, by imposing high compliance costs and eligibility requirements, without commensurate benefits in greater liquidity or reduced cost of capital. Third, enforcement of securities regulation in sub-Saharan Africa is generally weak. Whilst public regulators often have formal powers, budgets and staff; actual enforcement activity is sometimes limited by inadequate market monitoring and reliance on criminal as opposed to administrative sanctions. Poor public enforcement, in turn, reinforces poor private enforcement, leading to reduced market participation, illiquidity, and ultimately market underdevelopment. Fourth, although increased market integration can go a long way in facilitating market development in the region, integration cannot be a short/medium term solution to market underdevelopment in sub-Saharan Africa, given the significant economic, political and socio-cultural barriers to integration initiatives in the region. Ultimately, to develop their securities markets, policymakers in sub-Saharan Africa must focus their attention on making and credibly enforcing market-friendly rules of securities regulation. The thesis explores some ways this may be realistically accomplished.
Keywords: Africa; Capital Markets; Capital market; Developing countries; Fintech; Going public (Securities); Market Integration; Securities; Securities Law; Securities Law Enforcement; Sub-Saharan Africa

A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa - Baines, Daniel (University of Pretoria, 2021)
A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa', Daniel Baines explores whether South African resident taxpayers' constitutional rights to equality and property are infringed by current laws which tax residents at higher rates than non-residents on rental income and proceeds from the disposal of fixed property. He aptly sets out what the right to equality and property entails and how these relate to taxpayers. He finds that the higher effective tax rates paid by residents violates their constitutional right to equality. The thesis provides valuable insight into a resident's right to equality and property in terms of current tax rates and illustrates how current tax rates are unconstitutional. The recommendations brought forward contribute toward the discussion of how tax rates should be altered in order to ensure that residents' constitutional rights are no longer violated.
URI: https://repository.up.ac.za/handle/2263/82750
Keywords: Immovable property; Income tax; South Africa; Tax treatment

A comparative analysis between the Turkish Financial Reporting Standard for large and medium-sized entities and the OHADA accounting system - Diallo, Amadou Thierno (Sakarya Üniversitesi, 2021)
The rapidly growing bilateral and multilateral economic relationship between Turkey and African countries leads to the necessity of understanding each other's business and financial environment. Therefore, the accounting system as a fundamental tool for organizing and disseminating financial information should be accessible and understood by business actors and other stakeholders in these areas. Furthermore, the lack of study related to this subject has led us to carry out this comparative analysis between the two accounting systems by comparing financial statements prepared under each one and analyzing their main similarities and differences. The main purpose of this study is to highlight major differences and similarities between the SYSCOHADA and the FRS for LMSE. Also, the study is aimed to get a good understanding of both accounting sets and help practitioners and businessmen, and women operating in these places to have a good knowledge of the accounting regulations related to each country. On a topic basis and based on financial statements prepared following the SYSCOHADA rules and restated to be adapted to the FRS for LMSE, all main differences and similarities were thoroughly analyzed. Following the case study and the thematical analysis of different accounting topics, it can be understood that the two accounting sets differ to some extent due to philosophical approach on some topics such as the prudence principle where the SYSCOHADA, contrary to the FRS for LMSE, does not allow the recognition of potential profit resulting from currency translation gains related to receivable and payables until such profit becomes certain. However, these two sets also share some major similarities due to their proximity in some way to the IAS/IFRS. The effect of the main differences between the two sets can be noticed in the restated financial statements. The annual net income following the FRS for LMSE increased compared to the initial annual net income in the SYSCOHADA. Also, total assets and liabilities restated following the FRS for LMSE have decreased compared to the SYSCOHADA financial statements. Türkiye ile Afrika ülkeleri arasında hızla büyüyen ikili ve çok taraflı ekonomik ilişkiler, birbirlerinin iş ve finans ortamını anlama zorunluluğunu doğurmaktadır. Bu nedenle, finansal bilgilerin düzenlenmesi ve yayılması için temel bir araç olarak muhasebe sistemi, bu alanlardaki iş aktörleri ve diğer paydaşlar tarafından erişilebilir ve anlaşılabilir olmalıdır. Ayrıca bu konuyla ilgili çalışma eksikliği, iki muhasebe sistemi arasında bu karşılaştırmalı analizi, her biri altında hazırlanan finansal tabloları karşılaştırarak ve temel benzerlik ve farklılıklarını analiz ederek yapmaya yöneltmiştir. Bu çalışmanın temel amacı, SYSCOHADA ve BOBİ FRS arasındaki önemli farklılıkları ve benzerlikleri vurgulamaktır. Ayrıca, çalışma hem muhasebe standartları iyi anlamak hem de uygulayıcılara ve bu yerlerde faaliyet gösteren iş adamlarına her bir ülkeyle ilgili muhasebe düzenlemeleri hakkında iyi bilgi sahibi olmalarına yardımcı olmayı amaçlamaktadır. Konu bazında ve SYSCOHADA kurallarına göre hazırlanmış ve BOBİ FRS' ye uyarlanmak üzere yeniden düzenlenen mali tablolara dayalı olarak, tüm temel farklılıklar ve benzerlikler kapsamlı bir şekilde analiz edilmiştir. Vaka çalışması ve farklı muhasebe konularının tematik analizi sonucunda, iki muhasebe setinin bir ölçüde felsefi yaklaşım nedeniyle ihtiyat ilkesi gibi bazı konularda farklılık gösterdiğini anlaşılmaktadır. SYSCOHADA, BOBİ FRS'nin aksine alacak ve borçlara ilişkin kur farkı kazançları kaynaklanan potansiyel kârın kesinleşene kadar muhasebeleştirilmesine izin vermemektedir. Bununla birlikte, bu iki muhasebe seti, UFRS/UMS'ye bir şekilde yakın olmaları nedeniyle bazı önemli benzerlikleri de paylaşmaktadırlar. İki sistemin temel farkların etkisi, yeniden düzenlenen mali tablolarda fark edilebilir. BOBİ FRS'yi takiben yıllık net gelir, SYSCOHADA'daki yıllık net gelire kıyasla artmıştır. Ayrıca, BOBİ FRS'yi takiben yeniden düzenlenen toplam varlıklar ve yükümlülükler, SYSCOHADA finansal tablolarına kıyasla azalmıştır.
Keywords: Accounting standards; Accounting systems; Büyük ve orta boy işletmeler için finansal raporlama standardı; Comparative analysis; Financial reporting standard for large and medium size enterprises; Financial reporting standards; Finansal raporlama standartları; Karşılaştırmalı analiz; Muhasebe sistemleri; Muhasebe standartları; Turkish Financial Reporting Standards; Türkiye Finansal Raporlama Standardı

Transition from Local Accounting Standards to International Accounting Standards: A Comparison Between the OHADA Member Countries and Turkey - Diallo, Amadou Thierno; Çevi̇K, Zülküf (Yorum Yönetim Yöntem Uluslararası Yönetim Ekonomi ve Felsefe Dergisi, 2021)
This study tries to get a clear grasp of the factors that might play positively or negatively in a country’s convergence or adoption of the international financial reporting standards (IFRS). Through a comparative analysis between Turkey and the OHADA countries and based on the existing literature, the transition process towards the IFRS and challenges faced by each one is discussed from a historical perspective to the level of development. As a result, it is understood that the adoption or convergence towards the IFRS can be a challenging and a long-term process requiring multiple adjustments. Also, countries may differ in terms of historical past, level of development, cultural and socio-economic aspects which can all influence their transition. In addition, given the lack of study on the new adoption of the IFRS in the OHADA countries, this paper will contribute to filling the gap in the literature on the transition process. Furthermore, it will help countries which are in their early stage of the transition process to avoid some missteps and learn from others experience to get better prepared for a successful shift towards a fully IFRS compatible accounting system as has done Turkey. Bu çalışma, bir ülkenin uluslararası finansal raporlama standartlarına (IFRS) yakınsaması veya tam olarak benimsemesinde olumlu veya olumsuz rol oynayabilecek faktörleri tespit etmeyi amaçlamaktadır. Türkiye ile OHADA ülkeleri arasında karşılaştırmalı bir analiz yoluyla ve mevcut literatüre dayalı olarak, UFRS'e geçiş süreci ve bu süreçte karşılaşılan zorluklar, tarihsel bir perspektiften tartışılmaktadır. Sonuç olarak, IFRS’in benimsenmesi veya uyumlaştırılmasının zorlu ve birçok ayarlama gerektiren uzun vadeli bir süreç olduğu anlaşılmaktadır. Üstelik bu güçlükler, ülkelerin geçişlerini etkileyebilecek, tarihsel geçmiş, gelişmişlik düzeyi, kültürel ve sosyo-ekonomik yönler açısından farklılık gösterebilir. Buna ek olarak, OHADA ülkelerinde IFRS'in yeni benimsenmesine ilişkin çalışma eksikliği göz önüne alındığında, bu makale geçiş süreciyle ilgili literatürdeki boşluğun doldurulmasına katkıda bulunacaktır. Ayrıca, geçiş sürecinin erken aşamalarında olan ülkelere bazı yanlış adımlardan kaçınmalarına ve diğerlerinin deneyimlerinden öğrenerek, Türkiye'de olduğu gibi tamamen IFRS uyumlu bir muhasebe sistemine başarılı bir geçiş için daha iyi hazırlanmalarına yardımcı olacaktır.
Keywords: Accounting standards; Approche comparée; Comparison; Comptabilité; International Accounting Standards; Local Accounting Standard

Corporate Finance - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book comprises 19 papers published in the Special Issue entitled “Corporate Finance”, focused on capital structure (Kedzior et al., 2020; Ntoung et al., 2020; Vintilă et al., 2019), dividend policy (Dragotă and Delcea, 2019; Pinto and Rastogi, 2019) and open-market share repurchase announcements (Ding et al., 2020), risk management (Chen et al., 2020; Nguyen Thanh, 2019; Štefko et al., 2020), financial reporting (Fossung et al., 2020), corporate brand and innovation (Barros et al., 2020; Błach et al., 2020), and corporate governance (Aluchna and Kuszewski, 2020; Dragotă et al.,2020; Gruszczyński, 2020; Kjærland et al., 2020; Koji et al., 2020; Lukason and Camacho-Miñano, 2020; Rashid Khan et al., 2020). It covers a broad range of companies worldwide (Cameroon, China, Estonia, India, Japan, Norway, Poland, Romania, Slovakia, Spain, United States, Vietnam), as well as various industries (heat supply, high-tech, manufacturing).
Accepted: 2022-01-11T13:28:27Z

Challenges for Responsible Investment in the retirement benefits sector of Kenya - Mathenge, Elizabeth (Victoria University of Wellington, 2021)
Responsible investment (RI) is the investment strategy that incorporates environmental, social and governance (ESG) factors into the investment decision-making process (Hebb, Hawley, Hoepner, Neher, & Wood, 2015). RI has shifted from what was considered a niche market to become one of the fastest-growing areas of finance in many parts of the world (PRI, 2019b). However, a closer look at the development of RI and adoption rates in countries and regions reveals that RI is not commonly practised in sub-Sahara Africa (except for South Africa). This study explores the critical challenges for RI development in the retirement benefits sector of Kenya and, by engaging with a variety of key stakeholders, proposes how to overcome the identified challenges. It contributes to the literature on challenges for RI in a developing country by offering an in-depth case study of the retirement benefits sector.My study employs qualitative methods to collect and analyse data collected from semi-structured interviews with 22 participants (asset managers, regulators and capital market experts, and a council member of the Association of Retirement Benefits Schemes of Kenya) as well as a collection of published documents by government agencies in Kenya. Also, I analysed 10 annual reports to assess the kind of ESG information that is disclosed by listed companies. My study explores, in particular, how actors in the retirement benefits sector conceptualise RI. It identifies the leading ESG factors in Kenya and draws on the business-case approach to RI to explore whether the participants consider those factors as material risk factors that present both risks and opportunities to the investment decision-making process. Further, my study identifies the specific barriers for RI development and proposes how to overcome them. The findings show that participants define RI using several terminologies. This is consistent with the existing literature. My study finds that all participants consider corporate governance as a material risk factor that can impact the financial returns of a portfolio. However, most of the asset managers do not think that the environmental and social factors can present material risk factors to their investment decision-making process. Although over a third of the asset managers recognise that the environmental and social issues in Kenya present business opportunities to retirement benefits schemes, there is a shortage of well-structured assets in those areas. Further, this study identifies five specific barriers for RI development: diversification challenges; a lack of ESG data; a lack of demand/incentives; short-termism; and the demand for high financial returns and a lack of awareness and expert knowledge of RI practices. My study recommends that the National Treasury of Kenya develops RI policy for the entire finance sector. In addition, the findings support a recommendation for the Capital Markets Authority and the Retirement Benefits Authority to embark on capacity building programmes to educate the actors in the finance sector on RI strategies and to create awareness of the impact of ESG on financial returns in the long run.
Keywords: Investment and Risk Management; Kenya; Responsible investment; Retirement benefits schemes

Governance of non-bank systematically important financial institutions - Morbee, Katrien (University of Oxford, 2021)
This thesis identifies the circumstances under which corporate governance regulation can help gain traction to minimise systemic risk. Systemic risk is the risk that local losses spread through the financial system and badly affect the financial system and the real economy. Excessive risk-taking by financial institutions can contribute to such systemic risk. Prudential regulation and supervision of financial institutions leave corporate decision-makers with room for discretion to increase or decrease systemic risk. The incentives of these decision-makers are not necessarily aligned with minimising systemic risk. The thesis shows that this problem exists across different business models. More specifically, it identifies perverse incentives in the case of systemically important banks, CCPs, mutual funds, and hedge funds. The need for corporate governance regulation therefore lies in the inherent incompleteness of prudential regulation and supervision. Corporate governance regulation can help fill this gap by regulating the environment within which choices are made within these types of institutions. The analysis has three steps. First, it characterises the systemic importance of financial-sector activities carried on outside the context of ‘banks’. The governance literature so far has focused on the ‘systemic externalities’ created by banks. However, our analysis shows that other non-bank SIFIs generate similar systemic externalities with socially harmful consequences. These systemic externalities are not considered by SIFIs when taking business decisions. In a second step, the thesis shows that prudential regulation and supervision are incomplete and leave room for governance regulation to fill in the gaps. The final step shows that a corporate governance framework focused solely on the interests of shareholders will have negative consequences for systemic stability. Given such divergence between the decision-makers’ and society’s interests, corporate governance regulation can complement the traditional prudential framework.
Keywords: Asset managers; Central counterparties; Corporate governance; Finance; Non-bank financial institutions; Systemic risk

Regulatory measures to address bank failures in Zimbabwe - Nyaude, Ashley Batsirai (University of Pretoria, 2021)
The main rationale of prudential bank regulation and supervision of banks has traditionally been to ensure the safety and soundness of banks and protection of depositors. However, best practice standards in bank supervision acknowledge that it is impossible to completely prevent bank failures. Therefore, it is crucial to have regulatory measures in place to deal with banks that fail. Banks are core players in the financial system as the intermediaries between savers and users of capital. In addition, banks provide critical services to consumers, small and medium-sized businesses, large corporate entities and governments who rely on them to conduct their daily business, both at domestic and international level. Banks also fulfil a sui generis role that sets them apart from other financial institutions that are role players in the financial system because, inter alia, they hold “highly” liquid liabilities in the form of deposits that are repayable on demand; they extend long-term loans that may be difficult to sell or borrow against on short notice; they are the back-up source of liquidity to all other institutions (financial and non-financial); and, are also the transmission belt for monetary policy. Unlike other players in the financial system, banks are vulnerable to loss of public confidence and to liquidity risk. Liquidity risk being the risk that a bank will not have sufficient cash to meet short term obligations and the fact that a "run on the bank" by depositors can result in devastating liquidity drainage. Because banks play a special role in the economy and their failure may have a significant impact on financial stability, they need a special approach when they become insolvent or are likely to become insolvent. The 2008 Global Financial Crisis (“GFC”) demonstrated the importance of special resolution regimes for banks; and the need to balance the interests of shareholders, creditors and depositors, while promoting financial stability objectives. Given the critical role of banks in the economy the need is clear for a special resolution regime for banks that provides a legal framework for regulators that avails to them a suite of resolution tools which they can apply to resolve the bank in an orderly manner; to rescue those parts of the bank that may still be viable and to liquidate those parts that are not whilst avoiding a drain on public funds. In order to deal with bank failures in Zimbabwe, the Banking Act [Chapter 24:20] has provided for the mechanism of curatorship since 2000, as a rescue measure aimed at restoring failing banks to economic viability. Curatorship has over the years been applied with mixed success; consequently, Zimbabwe has undertaken a number of reforms which include the enactment of the Troubled Financial Institutions (Resolution) Act in 2005; and the introduction of the problem bank regime via the Banking Amendment Act of 2015. Throughout these reforms, Zimbabwe has elected to retain curatorship, which was once a standalone process in banking legislation to enable bank rescue; and assimilated it into a broader bank resolution framework. This study seeks to determine whether Zimbabwe’s resolution regime requires to be strengthened and if so, to recommend reforms that will align the resolution regime in Zimbabwe with international best practice. For such purpose it will draw upon the Financial Stability Board’s Key Attributes of Effective Resolution Regime as international best practice benchmark. It will further also consider guidance yielded by a comparative study of the resolution regimes in the United Kingdom and South Africa.
URI: https://repository.up.ac.za/handle/2263/80388
Keywords: Bank failure; Bank supervision; Zimbabwe

Allocating rights between nations: Legitimacy and justice in international tax policy - Ozawa Ozai, Ivan (McGill University, 2021)
Although extreme poverty has decreased in the last decades, we are a long way from eradicating global poverty. Similarly, the world has seen a considerable decrease in global inequality due to recent developments in emerging economies, but overall inequality between nations has risen in the last decades. International tax law may have a relevant role in improving or worsening global inequality. Extensive research has shown that the present international tax system was designed in a way that tends to benefit high-income economies. However, there has been no significant discussion about whether and how international tax law rules should be changed to address global inequality. The main goal of this thesis is to analyze the existing legitimacy and distributive justice issues that limit the ability of lower-income countries to raise tax revenues and consider what can be done to make the current international tax regime more aligned with global justice principles.The thesis builds on the contemporary literature in international political economy and global distributive justice and puts forth a normative framework for allocating the international tax base among states. First, it analyzes some of the legitimacy deficits of the present international tax system. In contrast to prevailing views about improving legitimacy, it demonstrates the shortcomings of focusing solely on making international tax policymaking processes more inclusive and argues for a greater focus on global distributive justice. It then analyzes the main tax theories that have defined international tax relations to date and demonstrates some of their limitations. The final part of the thesis puts forth normative principles that integrate distributive justice and considers the practical implications of the proposed normative framework for some of the most recent issues discussed in international tax policy
Identifier: https://escholarship.mcgill.ca/concern/theses/rf55zd52x
Keywords: International tax; International tax policy

Double taxation treaty interpretation : lessons from a case down under - Du Plessis, Izelle (Potchefstroom Electronic Law Journal, 2020)
In the Australian case of Bywater Investments Ltd v Commissioner of Taxation; Hua Wang Bank Berhad v Commissioner of Taxation (the Bywater case) the Australian High Court dealt with the question of whether certain companies were resident in Australia for income tax purposes. The majority answered this question by applying Australian domestic law. In a separate but concurring judgement, Gordon J also discussed the interpretation and application of the relevant double taxation treaty. This contribution analyses Gordon J's judgment to extract guidance from it for the South African courts on their interpretation of double taxation treaties. It is submitted that South African courts should also follow the "first step" proposed by Gordon J when interpreting double taxation treaties. South African courts may find Gordon J's judgment "instructive" when dealing with the interpretation of the "place of effective management" concept in both domestic law and double taxation treaties. In his judgment Gordon J favours the goal of common interpretation and it is argued that South African courts should follow this example and explicitly support this notion in applicable cases. From Gordon J's judgment and the judgement in Krok v Commissioner, South African Revenue Service, it is deduced that the positions in South Africa and Australia are similar in that the courts in both countries will be bound by the principles of Articles 31 and 32 of the Vienna Convention on the Law of Treaties when interpreting double taxation treaties. Moreover, Gordon J's judgment indicates that the domestic principles of interpretation should not be used in the interpretation of double taxation treaties. Recent South African cases have suggested that there are no differences between the South African domestic principles of interpretation and those contained in Articles 31 and 32 of the Vienna Convention on the Law of Treaties. This contribution submits that there are many similarities between the two, but that the rules are not exactly the same. South African courts should be aware of these differences and rather apply the rules of public international law, including those contained in the Vienna Convention on the Law of Treaties, when they interpret double taxation treaties. Gordon J specifically identifies the category of the Vienna Convention on the Law of Treaties in which he places the Commentary on the OECD Model Tax Convention, to rely on it for his interpretation of the relevant double taxation treaty. South African courts may well learn from this approach, to create more certainty in the process of interpreting a double taxation treaty.
http://hdl.handle.net/10019.1/124068

The Development of Accounting in Africa in the Era of International Financial Reporting Standards - Agyeman, Charles Gyamf (University of Westminster, 2020)
This thesis consists of two separate, but related studies on the development of accounting in Africa in the era of International Financial Reporting Standards. The first part of this thesis presents the first empirical test of a hypothetical classification of financial reporting in Africa based on de facto or actual practices as opposed to de jure rules. Three multivariate techniques (principal component analysis, cluster analysis, and multidimensional scaling) were used to analyse the accounting policies of large, listed companies in Africa that are required by law to adopt IFRS. It was found that there is a dichotomy between the IFRS policy choices of companies in Francophone and Lusophone countries, on the one hand, and those in common law jurisdictions, on the other, thus confirming the two-group classification schemes proposed by Elad (2015) and Nobes (1983). The results of this study extend previous research by demonstrating that international differences in financial reporting in Africa have survived in the era of IFRS and that pre-IFRS regulations enshrined in national and regional charts of account appear to have influenced IFRS policy choice. Furthermore, companies in common law countries tend to provide more extensive disclosures in their IFRS financial statements than their counterparts in code law countries. These findings have important policy implications, particularly in the context of recent recommendations of the World Bank, the International Monetary Fund, and the Pan-African Federation of Accountants that large entities in Africa adopt IFRS. The systematic differences in the choice of IFRS options between companies in civil law and common law jurisdictions suggest that it would be difficult to achieve internationalcomparability and consistency in financial reporting. The second part of the study uses semi structured telephone interviews to undertake interpretive accounting research (Baker and Bettner, 1997, p.293) to assess the perception of accounting professionals in relation to IFRS adoption and its use in Ghana. It concludes that despite the problems associated with its adoption and implementation, overall, International Financial Reporting Standards are viewed as necessary for the financial reporting needs of the country.
Keywords: Accounting classifications; CFA franc zone; IFRS practices; OHADA accounting system; Plan Comptable Général; SYSCOHADA

Commercialization of Microfinance in Cameroon : How can Microfinance Institutions manage their dual social and commercial goals? - Singhe, Steffi Sandra (Université de Nantes, 2020)
La commercialisation de la microfinance a mis au premier plan la performance financière des I MF, les IMF adoptant désormais une logique commerciale de rentabilité en plus de leur logique sociale établie de lutte contre la pauvreté. Cela pose un défi de gestion crucial pour les IMF pour équilibrer l'aspect social et commercial de leur mission. Cette thèse vise à analyser comment les IMF surmontent leurs défis pour atteindre leur double objectif social et commercial. Elle s'appuie sur le concept de bricolage comme perspective théorique et sur une approche méthodologique abductive, exploratoire et qualitative. La thèse vise également à fournir une meilleure compréhension du secteur de la microfinance camerounaise, en termes de son histoire et évolution, et des défis spécifiques au secteur. L'étude identifie diverses pratiques de bricolage que les IMF utilisent pour faire avancer la réalisation de leur double mission. Les résultats suggèrent l'utilisation de ces pratiques de bricolage par les IMF pour mobiliser des ressources, renforcer la légitimité et accroître leur ou/reach, dans un contexte caractérisé par des contraintes de ressources. Ces trois résultats de bricolage se renforcent mutuellement pour faciliter la réalisation du double objectif des IMF. Cette recherche a également mis en évidence les quatre phases d'évolution du secteur de la microfinance camerounaise et les cinq principaux défis auxquels sont confrontées les IMF du secteur. Cette thèse contribue à la littérature sur la microfinance. Elle propose un nouvel regard sur la gestion de la double mission des IMF en montrant comment les IMF mobilisent les stratégies de bricolage pour faire avancer leurs objectifs sociaux et commerciaux. Elle met en lumière le lien entre la littérature sur la microfinance et le bricolage. The commercialization of microfinance has brought to the forefront the financial performance of MF!s, with MF!s now adopting a commercial logic of profitability in addition to their established social logic of poverty alleviation. This poses a crucial management challenge for the MF!s in terms of balancing the social and commercial aspect of their mission. The main aim of this thesis is to understand how MFls overcome their challenges so as to achieve their dual social and commercial goals. lt draws on the bricolage concept as a theoretical perspective and on an abductive, exploratory and qualitative research approach. The thesis also aimed to provide a better understanding of the Cameroonian microfinance sector, in terms of its history and evolution, and the challenges specific to the sector. The study identifies various bricolage practices that the MF!s use to advance the fulfilment of their dual mission. The findings suggest the use of these bricolage practices by the MF!s to mobilize resources, build legitimacy, and increase outreach, in a context characterized by resource constraints. These three bricolage outcomes reinforce each other, and they all strengthen the achievement of the MF!s' dual goals. This research also highlighted the four phases of evolution of the Cameroonian microfinance sector and the five main challenges faced by MF!s in the sector. This thesis contributes to the microfinance literature. lt offers a new perspective on MF! dual-mission management by showing how MF!s mobilize bricolage practices to advance their dual social and commercial goals. lt brings light on the link between the literature on microfinance and bricolage.
Keywords: CSR; Cameroun; Microfinance; RSE; Responsabilité sociétale; Régulation (théorie)

Tax Competition: Global but Virgin under Rwandan Law - Habimana, Pie (Recht in Afrika, 2020)
This paper’s foundation is the global character of (harmful) tax competition. While this phenomenon’s global existence is widely recognised alongside the…

Transition to the Revised OHADA Law on Accounting and Financial Reporting: Corporate Perceptions of Costs and Benefits - Fossung, Micheal Forzeh; Ntoung, Lious Agbor Tabot; Santos de Oliveira, Helena Maria; Pereira, Cláudia Maria Ferreira; Bastos, Susana Adelina Moreira Carvalho; Pimentel, Liliana Marques (Journal of Risk and Financial Management, 2020)
This paper examines the ongoing transition to the revised Organisation for the Harmonisation of Business Law in Africa Act on Accounting and Financial Reporting for companies in general and to the International Financial Reporting Standards for listed and group companies with a particular focus on recent institutional developments and corporate concerns. The study used 80 professional accountants, most of whom were members of the Institute of Chartered Accountants of Cameroon and academics. Using the descriptive statistics, the study shows that the transition to the revised OHADA brings about a high level of comparability and transparency of the financial statements, that the International Financial Reporting Standards can be implemented in Cameroon (but not fully), and that the benefit of the transition exceeds the cost.
Number: 8
Keywords: Comparability; IFRS; OHADA accounting; perception; transition

The Opportunity for Convergence of SYSCOHADA towards IFRS Standards: An Effect of Coercitive and Mimetic Isomorphism - Souleymanou, Kadouamaï; Mouafo, Cédrick Nzokouo (Journal of Modern Accounting and Auditing, 2020)
The last few years have been marked by the increase in power of IFRS international accounting standards. From the full or partial adoption to the gradual convergence, many countries have displayed a strong preference for these standards. Meanwhile, the implementation of International Financial Reporting Standards (IFRS standard) in the context of developing countries is not trivial. We are witnessing an unprecedented clash between the authors who support the interest of these standards for developing countries, and those who conversely demonstrate that these norms are not well adapted to the context of those countries. Falling within this problematic, this thesis analyses the issues and determinants of the convergence of the Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) accounting system towards IFRS international accounting standards in view of the reforms introduced by the last revision. From a sample of 10 companies, among which two local firms, two international firms, three publicly traded companies, and three not listed other companies, we show that the current convergence towards international accounting standards follows an effect of coercitive and mimetic isomorphism. In so doing, the timely implementation of these standards in the context of Cameroon is contingent with a number of structural and environmental factors that call their pertinence into question.
Keywords: Convergence; Developing countries; IFRS; SYSCOHADA; Système Comptable OHADA

Capital market effects of adoption of IFRS - Opare, Solomon (Victoria University of Wellington, 2020)
This thesis examines the impact of adoption of IFRS (International Financial Reporting Standards) on two aspects of the operation of capital markets. Firstly, the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital. Secondly, the impact of adoption of IFRS on seasoned equity offering (SEO) underperformance. To examine the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital, the study used meta-analysis of empirical studies published since 2000. Meta-analysis provides an objective view of the empirical results, in contrast to narrative reviews, which offer subjective conclusions. From meta-analysis of 55 empirical studies with 1,259 effect sizes, the study finds that IFRS adoption has increased financial reporting comparability, market liquidity, and reduced cost of equity. For cost of debt, a decrease is observed only for voluntary adoption. The meta-regression analysis shows how the results differ across mandatory and voluntary adoption of IFRS and that the measurement choices, type of control variables, study design, and strength of empirical results explain the variation in the observed effect of adoption of IFRS. To examine the impact of adoption of IFRS on SEO underperformance the study analyses a large sample of SEOs from 51 countries over the period 1992-2017. Given that the empirical literature on SEOs has established that information asymmetry contributes to SEO underperformance, it is important to assess whether adoption of IFRS has reduced the uncertainties surrounding SEOs and, thus, subsequent underperformance. The study employs a control sample of non-IFRS adoption countries and applies a difference-in-difference (DiD) design to test for the incremental change for IFRS adoption countries over non-IFRS adoption countries. The study finds that SEO underperformance reduces for IFRS adopters relative to non-IFRS adopters in the post-adoption period. The reduction in SEO underperformance is influenced by increased disclosure, increased comparability, and number of accounting changes. The study also finds that the impact of adoption of IFRS on SEO underperformance exists only for firms in countries with strong enforcement, and is conditional on the implementation credibility of countries. The findings are robust to the application of a different measure of SEO underperformance. Overall, the study suggests that IFRS has had a positive impact on capital markets. However, increased disclosure, comparability, and credible implementation play important roles in realising the benefits of adoption of IFRS. Thus, policymakers of weak enforcement countries are encouraged to strengthen their institutional environment in order to reap the benefits that adoption of IFRS can provide to their capital market.
Keywords: Cost of debt; Cost of equity; Enforcement; Financial reporting comparability; IFRS adoption; Market liquidity; Meta-analysis; SEO underperformance; Seasoned equity offering

The Distributional Effects of Value-Added Taxes in OECD Countries - Thomas, Alastair (Victoria University of Wellington, 2020)
Most OECD countries’ value-added tax (VAT) systems apply reduced VAT rates to a selection of expenditure items in order to achieve distributional goals, and – to a lesser extent – social, cultural and employment-related goals. This thesis investigates the distributional effects of the VAT in OECD countries, and the merits of using reduced VAT rates to achieve distributional goals. The research adopts a microsimulation modelling approach that draws on household expenditure microdata from household budget surveys for an unprecedented 27 OECD countries. A consistent microsimulation methodology is adopted to ensure cross-country comparability of results. Non-behavioural VAT microsimulation models are first built to examine the overall distributional impact of the current VAT systems in each country. The research assesses the competing methodological approaches used in previous studies, highlighting the misleading effect of savings patterns on cross-sectional analysis when VAT burdens are measured relative to income. Measuring VAT burdens relative to expenditure – thereby removing the influence of savings – is found to provide a more reliable picture of the distributional impact of the VAT. On this basis, the VAT is found to be either roughly proportional or slightly progressive in most of the 27 OECD countries examined. Nevertheless, results for a small number of countries (Chile, Hungary, Latvia and New Zealand) highlight that broad-based VAT systems that have few reduced VAT rates or exemptions can produce a small degree of regressivity. Results also show that even a roughly proportional VAT can still have significant equity implications for the poor – potentially pushing some households into poverty. Behavioural VAT microsimulation models are then built for 23 OECD countries to investigate whether reduced VAT rates are an effective way to support poorer households, and whether the use of targeted cash transfers would be more effective. The behavioural microsimulation methodology follows the Linear Expenditure System based approach of Creedy and Sleeman (2006). Complementing this approach, a Quadratic Almost Ideal Demand System (QUAIDS) is estimated specifically for New Zealand, thereby providing the first estimates of a QUAIDS model based on New Zealand data. Simulation results show that, as a whole, the reduced VAT rates present in most OECD countries tend to have a small progressive impact. However, despite this progressivity, reduced VAT rates are shown to be a highly ineffective mechanism for targeting support to poorer households: not only do rich households benefit from reduced rates, but they benefit more in aggregate terms than poor households do. When looking at reduced VAT rates applied to specific products, results are found to vary considerably. Reduced VAT rates specifically introduced to support the poor (such as reduced rates on food consumed at home and domestic utilities) are generally found to have a progressive impact, though rich households still receive a larger aggregate benefit than poor households. In contrast, reduced VAT rates introduced to address non-distributional goals (such as reduced rates on restaurants, hotels, and cultural and social expenditure) often have a regressive impact. Additional simulation results show that an income-tested cash transfer will better target support to poorer households than reduced VAT rates in all countries. Furthermore, even a universal cash transfer is found to better target poorer households than reduced VAT rates. However, results also show that it is very difficult for an income-tested cash transfer to fully compensate all poor households for the removal of reduced VAT rates. This is due to the significant variation in the underlying consumption patterns across households. While a small number of poor households lose out from replacing reduced VAT rates with targeted cash transfers, those that receive support are instead determined by income and family characteristics as opposed to consumption tastes – thereby increasing horizontal equity. Furthermore, many households are lifted out of poverty as revenue previously transferred to richer households is now transferred to poorer households. These results empirically confirm the theoretical expectation that, where available, direct mechanisms (whether via the income tax or benefit system) will better achieve distributional goals than reduced VAT rates. Countries that currently employ reduced VAT rates to achieve distributional goals should therefore consider removing these reduced rates and adjusting their income tax or benefit systems to achieve these distributional goals instead. Countries should also consider removing reduced VAT rates aimed at non-distributional goals where a more effective instrument is available to achieve the particular policy goal. At a minimum, the merits of these reduced VAT rates should be reassessed in light of their negative distributional impact.

Critical reflections on the development of integrated reporting: Are integrated reporting and IFRS competing frameworks? - Barker, R.; Teixeira, A. (The Routledge Handbook of Integrated Reporting, 2020)
Although integrated reporting emphasizes the contemporaneous relationship between financial and non-financial capitals, its primary purpose is to explain how an organization creates value over time. This is similar to the purpose of management commentary, which is part of a general-purpose financial report. We compare and contrast the information requirements of an integrated report with the type of information that supplements the primary financial information in general purpose financial reports, prepared in accordance with International Financial Reporting Standards (IFRS). We examine whether the information in those reports is intended to be forward-looking and predictive, whether non-financial capitals can (and should) be monetized in order to facilitate integration, and whether the reporting boundary should be drawn in different ways to serve different purposes. We find that the International Integrated Reporting Framework and IFRS do not serve different purposes or apply different approaches, but that – in essence – they are competing frameworks. While IFRS has highly developed standards for reporting financial capital, neither has a well-developed approach for reporting any other capital.

Political business cycles, bank pricing behaviour and financial inclusion in Africa - Iddrisu, Abdul Ganiyu; Turkson, Festus Ebo (Cogent Economics & Finance, 2020)
This paper analyses financial inclusion in Africa focusing on the role of political business cycles and pricing behaviour of banks. We employ a sample of 330 banks operating in 29 African countries to test for two related hypotheses. Panel fixed and random effects were estimated for the period 2002 to 2013. The regression results that ensued suggests first that loan price increases in pre-election and election years. Building on this result and employing various specifications of financial inclusion, the second results suggest that, high bank loan prices in election years tend to increase financial access more, compared to non-election years, and that, high deposit price reduces financial usage but increases financial access in election years, compared to non-election years. By extension, these results have important policy implications for policymakers.
Publisher: Abingdon: Taylor & Francis https://www.econstor.eu/handle/10419/245317
Keywords: Africa; Banks' pricing behaviour; Election; Financial inclusion; Political business cycles

The effectiveness of the adopted OECD transfer pricing dispute resolution mechanisms in an African context - Kekana, Nelson Doctor (University of Pretoria, 2020)
With the developments happening globally that are aimed at curbing base erosion and profit shifting by multinationals, improving the resolution of transfer pricing disputes has been identified as one of the key issues. This thesis investigates the challenges uniquely faced by African countries that militate against the use of the OECD transfer pricing dispute resolution mechanisms. The thesis starts by reflecting on the effect of transfer pricing manipulation by multinational enterprises in Africa in particular. Transfer pricing manipulation is one of the causes of the so-called tax gap, which is, the gap between anticipated and actual revenue collection. The aggression by revenue authorities against transfer pricing manipulation in order to close this gap has triggered a lot of transfer pricing adjustments. These adjustments have resulted in multiple transfer pricing disputes. In the analysis of the adopted OECD dispute resolution mechanisms, the thesis focuses on the effectiveness of the mutual agreement procedure (MAP), the advance pricing arrangement (APA) and the mandatory binding arbitration (MBA). It identifies the problems that result in the failure of or the delay in the resolution of many transfer pricing disputes by analysing the domestic frameworks that exist in four African countries namely: South Africa, Kenya, Uganda and Ghana. The thesis identifies problems such as the absence of a tax treaty network within the African continent, the use of underdeveloped double tax agreements and the lack of commitment from African countries to subscribe to and ratify multilateral conventions. These problems delay or stifle the resolution of tax treaty disputes. They also cause uncertainty for taxpayers and lead to continued tax avoidance by multinational enterprises that essentially avoid paying tax in African countries where the economic activities of these enterprises take place. The thesis also identifies the importance of other OECD supporting tools such as the exchange of tax information in the resolution of transfer pricing disputes. It focuses on tools such as country by country reports, the master file, the local file and simultaneous tax examination as covered by the Multilateral Convention on Mutual Administrative Assistance in Tax Matters. The thesis contributes to the resolution of the identified problems with transfer pricing dispute resolution in Africa by recommending certain improvements that can be effected. These recommendations entail, regarding the MAP, the expansion of tax treaty networks by African countries and the establishment of a Tax Treaty Dispute Resolution Committee by ATAF. Regarding the APA, it is recommended that African countries should sign the multilateral instrument (MLI) and make use of advance tax rulings (ATRs) as alternatives. With respect to the MBA, this thesis recommends that African countries should use optional arbitration by effectively using article 25(4) of the OECD Model tax convention (MTC). It also recommends that African countries must enhance their tax transparency by ratifying multilateral conventions that seek to address international tax co-operation and to improve compliance with transfer pricing documentation requirements in order to make the resolution of transfer pricing disputes more effective.
https://repository.up.ac.za/handle/2263/80889
Keywords: Dispute resolution; Model Tax Convention; OECD; Transfer pricing

IFRS compliance, corporate governance and financial reporting quality of GSE-listed nonfinancial firms - Mbir, Deborah Esi Gyanba; Agyemang, Otuo Serebour; Tackie, George; Abeka, Mac Junior (Cogent Business & Management, 2020)
The adoption of International financial reporting standards (IFRS) has been presented in several empirical literature as a factor that could improve the quality of financial reports. However, Ghana has not attained the desired levels of financial reporting quality after the adoption of IFRS. Literature reveals that lack of proper enforcement of these high-quality standards may result in limited compliance and will undermine the effectiveness of these standards in terms of attaining high-quality financial reports. This study therefore argues that the relationship between IFRS compliance and reporting quality revolves around some enforcement mechanisms like corporate governance structures. In view of that, by using random effect estimation technique, this study examined the role of corporate governance in the relationship between IFRS compliance and the reporting quality of firms listed on the Ghana Stock Exchange (GSE). The study found that the right corporate governance mechanisms will enhance the positive effect of IFRS compliance on reporting quality. This study further recommends that to gain an appreciable level of public confidence in the annual reports of firms listed on the GSE, the audit committee’s independence and the board’s independence should be strengthened to ensure that management does not only adopt IFRS, but that the standards are actually complied with.
Keywords: Compliance; Corporate governance; IFRS; Reporting quality

The Effect of IFRS Adoption on Foreign Direct Investment in Africa - Musah, Alhassan; Adjei, Eunice; Ahmed, Ibrahim Anyass (Journal of Applied Accounting and Taxation, 2020)
Adoption of International Financial Reporting Standards (IFRS) is supposed to help enhance comparability of financial statement, improve the quality of financial reporting and accounting information of businesses in a country. This is expected to help improve Foreign Direct Investment (FDI) in the adopting countries. This study examined the effect of IFRS adoption on FDI inflows in Africa. Unlike previous studies that sample both adopting and non-adopting countries, this study sampled only Africa countries that have adopted IFRS to determine whether the adoption has improved FDI inflows. To achieve this objective, 20 African countries that have adopted IFRS were sampled covering a period 1980 to 2015. Data was sourced from The World Bank financial and Economic Data. Control variables such as GDP growth, openness of the economy, government debt and population growth were included in the model. The correlation and regression analysis showed that IFRS adoption has a positive and significant influence on FDI inflows in Africa. On the other hand, open economy, government debt and population growth had a positive and significant association with FDI. Overall, the results show that African countries that want to improve FDI inflows must improve the quality of their reporting environment by adopting IFRS.
Keywords: Africa; FDI; Foreign direct investment; IFRS; IFRS adoption; Investments; Macroeconomic variables

Fiscal Potential and Political and Institutional Constraints to Increasing Domestic Revenues - Niang, Birahim Bouna; Mbaye, Ahmadou Aly (Center for Global Development, 2020)

Promoting financial inclusion through mobile money while introducing regulatory solutions to reduce and control money laundering in Lesotho - Taole, T. E. (North-West University, 2020)
Mobile money services have considerable potential in modern economies. They have the potential to increase financial inclusion for poor people and people excluded from formal financial services. This is because mobile money services can be accessed simply using a mobile cellular phone and the majority of people nowadays own mobile phones, including people living in the rural areas. Mobile money can therefore solve the problem of financial exclusion because even the people who live in the rural areas without access to formal financial services can now access financial services thorough mobile money services. Financial inclusion, on the other hand, is simply defined as a situation where every member of the society has access to and is able to use financial services offered by formal financial services institutions, such as banks and insurance companies. Financial inclusion has many benefits, the main benefit being the stimulation of the economy of a country. For mobile money services to operate smoothly and financial inclusion to be achieved, there must be enabling regulation. Regulation must not be so strict as to prevent mobile money service providers from operating. Regulation must allow for innovation and at the same time maintain financial integrity and stability by ensuring that financial crimes, such as money laundering, do not affect mobile money services. Although mobile money services can increase financial inclusion, regulators must be vigilant to ensure that they stop criminals from using mobile money services to commit money laundering offences. This research focuses mainly on mobile money services in the Kingdom of Lesotho. The aim is to find out how regulation can be improved to ensure that mobile money services can help to increase financial inclusion. The aim is also to find out how regulation can help to ensure that mobile money services operate smoothly, and that the crime of money laundering is prevented from affecting mobile money services. To achieve this aim, the research is divided into different chapters and in each chapter the aim is to find ways in which the main aim can be achieved. In the research, mobile money and financial inclusion will be defined and their importance in modern economies will be demonstrated in greater detail. Furthermore, the issues of money laundering will be discussed. The threat of the crime of money laundering will be highlighted. An analysis of the legal regulatory framework of mobile money services and money laundering in Lesotho will be undertaken to determine the extent to which these regulatory frameworks can help realise financial inclusion and promote mobile money services in Lesotho. The same discussion is made in respect of other African countries. The legal regulatory framework of Lesotho will be compared to the framework of other African countries to ascertain how mobile money services and money laundering and financial inclusion issues are regulated in those countries. The countries discussed in this research are South Africa, Malawi, Kenya, Nigeria, Uganda, Tanzania, and Ghana. Based on these discussions, some shortcomings in the legal regulatory framework of mobile money services and money laundering in Lesotho will be identified and the conclusion will be drawn that the two frameworks have to be revisited to ensure that mobile money services will operate smoothly in the Kingdom of Lesotho. Furthermore, recommendations will be made to address the legal shortcomings identified in the framework.
Keywords: Financial inclusion; Lesotho; Mobile money services; Regulatory framework

The Impact of Economic Institutions on Small Firms in Developing Countries - Pouliquen, Victor (Ecole des Hautes Etudes en Sciences Sociales, 2019)
In many developing countries, economic institutions are failing. This translates into structural problems such as widespread informality, rampant corruption and the impossibility for governments to raise taxes. This thesis study how economic policies affect economic institutions in developing countries. It focuses on two broad questions: (1) What are the effects of policies to reduce informality? and (2) how are new technologies reshaping the way governments collect taxes?The first chapter uses a randomized experiment to study the introduction of a new legal status in Benin, created to make it easier for small firms to become formal. To make this new status attractive, the government added supplementary incentives designed to enhance the presumed benefits of formalizing. We find that few firms register when just given information about the new regime, but our full package of supplementary efforts boosts formalization by 16.3 percentage points. However, this formalization does not bring firms higher sales, profits or access to credit, and the cost of formalizing these firms exceeds the added taxation they will pay over the next decade. We show how better targeting of these policies towards firms that look more like formal firms to begin with can increase the formalization rate and improve cost-effectiveness. The second chapter studies the impact of formalization on intra-household relationships, still in Benin. The idea behind this chapter is that formalization changes effective property rights by clarifying who in the household is the legal owner of the business and who will keep it in case of divorce. The causal effect of formalization is identified using the same random experiment used for the first chapter. We find first that formalization increases entrepreneurs' (both male and female) control over household revenue. They contribute proportionally less to household expenditures and to the personal expenses of their partner. Second, using a behavioral game, we find strong gender differential effects of formalization on the probability that entrepreneurs pay to hide a windfall transfer from their spouse. Female entrepreneurs are much more likely to pay to hide, while male entrepreneurs are much less likely to do so. Using a theoretical model, we show that this result is compatible with the idea that women entrepreneurs are constrained and cannot invest as much as they would like in their own business. Women who became formal hide the windfall transfer more because they have more property rights and want to invest more in their business. Our conclusion is that formalization has important effects on intra-household dynamics.The third and final chapter of this thesis deals with the second question and examines how internet is changing the way taxes are collected. Specifically, we study the impact of electronic tax filing (e-filing) for small firms to replace in-person submission of paper-based forms to tax officials. We examine the impact of e-filing on compliance costs, tax payments, and bribes payments using experimental variation and data from Tajikistan firms. We find that firms that e-file have lower compliance costs, spending five fewer hours each month on fulfilling tax obligations. There are no significant average effects of e-filing on tax or bribe payments, but significant heterogeneity exists across firms by their baseline likelihood of tax evasion. Among firms previously more likely to evade, e-filing doubles tax payments, likely by disrupting collusion with officials. Conversely, among firms less likely to have been evading, e-filing reduces tax payments, suggesting that officials had previously required them to pay more. These firms also pay fewer bribes, as e-filing reduces opportunity for extortion. Our conclusion is that e-filing reduces compliance costs and makes the distribution of tax payments across firms arguably more equitable. Dans les pays en développement, les institutions économiques sont souvent défaillantes. Cela se traduit par des problèmes structurels tels que l’omniprésence du secteur informel, la corruption généralisée et l’incapacité des États à collecter les impôts. Cette thèse porte sur les politiques publiques permettant d’améliorer le fonctionnement des institutions économiques. Elle se focalise sur deux questions : (1) Quels sont les effets des politiques de réduction de l’informalité ? et (2) Comment les nouvelles technologies affectent la collecte des taxes ? Le premier chapitre étudie à l’aide d’une expérimentation aléatoire l’introduction d’un statut légal facilitant la formalisation des petites entreprises au Bénin. Afin de rendre ce statut attractif le gouvernement l’a accompagné d’incitations supplémentaires créés pour amplifier les bénéfices potentiels de la formalisation. Nous trouvons que très peu d’entreprises se formalisent lorsqu’elles reçoivent uniquement de l’information sur le nouveau statut. Cependant, lorsque l’information est combinée aux incitations, la formalisation augmente de 16,3 points de pourcentage. En revanche, les effets sur les performances des entreprises sont limités, et le coût des incitations est supérieur au total des impôts qu’elles paieront pendant les 10 prochaines années. Enfin, nous montrons comment un ciblage sur les entreprises ayant des caractéristiques proches des entreprises déjà formelles améliorerait l’efficacité de ce type de programme. Le second chapitre étudie l’impact de la formalisation sur les relations intra-ménages, toujours au Bénin. Dans ce contexte, la formalisation renforce les droits de propriété et clarifie au sein des ménages qui est le propriétaire légal de l’entreprise, et qui la gardera en cas de divorce. L’effet causal de la formalisation est identifié à l’aide de l’expérimentation aléatoire déjà utilisée pour le premier chapitre. Nous trouvons que les entrepreneurs s’étant formalisés ont plus de contrôle les ressources de leur ménage. Ils ou elles contribuent proportionnellement moins aux dépenses du ménage et transfèrent moins d’argent à leur partenaire. Deuxièmement, en utilisant un jeu comportemental dans lequel les entrepreneurs peuvent cacher un transfert monétaire à leur partenaire, nous trouvons que les femmes qui se sont formalisées cachent davantage à leur mari. A l’aide d’un modèle théorique, nous montrons que ce résultat est compatible avec l’idée que les femmes ne sont pas libres d’investir comme elles le souhaiteraient dans leur entreprise et doivent le faire secrètement. Notre conclusion est que la formalisation a des effets importants sur les dynamiques intra-ménage. Le troisième chapitre utilise une expérimentation aléatoire conduite au Tadjikistan pour étudier l’impact d’un système permettant aux entreprises de déclarer leurs taxes en ligne plutôt que de soumettre un formulaire en personne. Nous trouvons que ce système réduit le temps passé par les entreprises pour remplir leurs obligations fiscales de 5 heures par mois. Nous ne trouvons pas d’effets sur le montant des impôts payés ni sur le versement de pots-de-vin. En revanche, l’absence d’effets moyens masque une importante hétérogénéité. Les entreprises le plus susceptibles de faire de l’évasion fiscale dans le système précédent payent davantage d’impôts quand elles déclarent en ligne, probablement car elles ne peuvent plus entrer en collusion avec les agents des impôts. À l'inverse, les entreprises qui étaient les moins susceptibles de faire de l’évasion, payent moins des taxes quand elles déclarent en ligne, suggérant qu’elles étaient forcées de payer plus d’impôts avant. Ces entreprises paient également moins de pots-de-vin, ce qui suggère que déclarer en ligne offre une protection contre le risque d'extorsion de la part des agents du fisc. Notre conclusion est que permettre la déclaration des taxes en ligne a rendu l’appareil fiscal à la fois plus efficace et plus juste.
Keywords: Droits de Propriétés; Electronic Tax Filing; Impôt; Impôt (recouvrement); Informality; Informalité; Innovation; Intra-Household Relationships; New Technologies; Nouvelles Technologies; Paiement en ligne des Taxes; Petites Entreprises; Petites et moyennes entreprises; Property Rights; Propriété; Relations Intra-Ménage; Small Firms; Taxation; Économie souterraine

Personal Property Security Law: International Ambitions and Local Realities - Castellano, Giuliano; Tosato, Andrea (International Business Law, 2019)
Personal property security law is a key element of “access to credit” and “financial inclusion”. The prevailing view is that a legal framework enabling the effective use of personal property as collateral markedly benefits both lenders and borrowers. Lenders can offer financing at a lower cost thanks to reduced credit risk; borrowers can access funding by leveraging the otherwise unavailable value of the assets integral to their operations. Over the past century, the priorities of personal property security law have evolved fundamentally. As small and medium-sized enterprises (SMEs) and individual entrepreneurs have become the growth engine of both developed and developing economies, legislators have grown sensitive to the financing needs of these entities. In parallel, the advent of the information society has demanded that lawmakers address squarely the rules governing the use as collateral of intangibles such as “receivables”, “intermediated securities”, “non-intermediated securities”, and “intellectual property rights”, rather than confine their gaze to tangibles such as industrial machinery, mobile equipment and inventory. Concurrently, the increasingly transnational nature of both economic development policies and commercial activity have engendered the need for global principles and standards for asset-based lending. To address these novel priorities and promote a healthy and vibrant credit ecosystem, international and regional organizations have undertaken projects aimed at modernizing and harmonizing personal property security law. Over time, these efforts have yielded a panoply of legal instruments. Binding conventions have been adopted to unify the rules of discrete facets of personal property security law, while soft-law texts, such as model laws and legislative guides, have been formulated to supply comprehensive legal templates to lawmakers keen to revise their domestic legal regimes. Nevertheless, states have struggled to assimilate these international efforts into their domestic legal systems. Common law jurisdictions have been loath to abandon the familiarity and safety of the path paved by centuries of case law; in similar vein, civil law jurisdictions have resisted inducements to renovate the normative infrastructure erected by the codifications of the 19th century. This Chapter explores the tension between international ambitions and local realities, with a special focus on the issues encountered in civil law jurisdictions. To this end, the case of Italy is examined as a living experiment in comparative personal property security law. In this jurisdiction, the recent enactment of a non-possessory security device, absent a comprehensive reform of the country’s civil code affords important lessons for any civil law system which might be pondering personal property security law reforms. More profoundly, it epitomizes the gap that separates the aspirations of international legal instruments from their effective implementation in domestic contexts. This analysis is divided into two parts. The first reviews international and regional legal initiatives that have shaped the personal property law landscape and then identifies a set of core tenets shared among them. In the second part, attention shifts to Italy, scrutinizing both the personal property security legal edifice originally constructed in this jurisdiction and the attempts to overhaul it that have taken place over the past three decades. This is followed by a critical appraisal of the current state of the law, by reference to the aforementioned core tenets of personal property law reform.
Keywords: Commercial Law; Law Reform; Non-possessory Pledge; Personal Property Security Law; Secured transactions

Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
OpenAlex: https://openalex.org/W2998516176
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

The Influence of IAS/IFRS on the New OHADA General Chart of Accounts - Tchokoté, Ivan Djossa (Journal of Modern Accounting and Auditing, 2019)
Accounting standardization in black African French-speaking countries is presented through two streams of research. The first stream presents the general chart of accounts common to all these countries as an accounting model which reconciles the divergences between the Anglo-Saxon and continental approaches to accounting, and thereby satisfies the requirements of users of accounting information. The second stream considers that the convergence towards IAS/IFRS is a vital way of attracting international investors and increasing development. This article stands by the second perspective and analyzes the changes introduced in the PCG-OHADA (2017) compared to the PCG-OHADA (2000). It shows that the new provisions of the PCG-OHADA are mainly inspired by IAS 1, IAS 16, IAS 19, IAS 36, IAS 38, IAS 40, and IFRS 6.
Keywords: Accounting harmonization; Accounting standards; IFRS; PCG

A comparative appraisal of debt relief measures for no income no assets (NINA) debtors in Nigeria - Osunlaja, Tobi Titilayo (University of Pretoria, 2019)
Nigeria currently has a non-functioning insolvency system; it is yet to record a successful insolvency case. This failure principally is attributable to the weak laws and enforcement policies in existence. The problem is exacerbated by burgeoning consumer debt in the formal sector. The causal factors for this increase in debt are negative economic growth indices such as rising inflation, interest rates and unemployment. With these indices predicted to worsen, a new Bankruptcy and Insolvency Act (BIA) was proposed in 2016. The BIA seeks to regulate individual insolvency proceedings in Nigeria. However, the BIA (as currently conceptualized) does not make provision for debtors with neither income nor assets, often referred to as No Income No Assets (NINA) debtors who, it can be argued, are in the majority in the Nigerian state. The aim in this thesis is to propose debt relief measures that cater for NINA debtors in Nigeria. This proposal aims to prevent further discrimination against these debtors in terms of the current law and the proposed BIA. It envisages that catering for NINA debtors in Nigeria will boost the Nigerian government’s drive to encourage entrepreneurship. In providing for NINA debtors it will provide a safe landing for poor debtors in the event of entrepreneurial failure. The thesis achieves its stated aim by studying international principles and guidelines as espoused by leading bodies. Furthermore, the thesis performs a comparative analysis of relevant NINA provisions in South Africa, Sweden, France, Ireland and Canada. The thesis proposes amendments to the proposed BIA in light of the aforementioned analysis and posits that procedures that are formal and extra-judicial, which have no financial requirements and are easily accessible to debtors should be incorporated.
https://repository.up.ac.za/handle/2263/92927
Keywords: Debt relief measures; Insolvency; Insolvency system; Laws and enforcement policies; No Income No Assets (NINA)

How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit

What Process is Due – Sanctions Regimes of Multilateral Development Banks - Madir, Jelena (University of Westminster, 2019)
Much has been written about the consequences for companies of criminal convictions for bribery and other corrupt practices. However, less attention has been paid to the sanctions regimes that have been developed by multilateral development banks in order to combat fraud and corruption in their operations. This is likely to change in view of the fact that on 9 April 2010, the heads of five leading multilateral development banks (MDBs) – the African Development Bank, the Asian Development Bank, the European Bank for Reconstruction and Development, the Inter-American Development Bank and the World Bank Group – signed the Agreement for Mutual Enforcement of Debarment Decisions, which provides for mutual and reciprocal enforcement of debarment decisions taken by any one of them against parties that engage in fraud, corruption, coercion or collusion in connection with MDB-financed projects. For parties that are seeking financing form an MDB or are competing for contracts funded by an MDB, this means that a sanctionable practice committed in a single country could result in global sanctions. Against this background, this thesis examines the type of due process rights that should characterise MDBs’ sanctions procedures. More particularly, the thesis analyses the extent to which MDBs’ sanctions regimes should be bound by the rules of law, analogous to those of national judicial bodies, and the level of due process and transparency that should be required from these ever-evolving regimes. In other words, (how) can the tension between the administrative and business considerations of MDBs’ sanctions regimes (coupled with their immunity from judicial review) be reconciled with due process considerations and principles of fairness that underpin a national judicial model?

Block Chain Accounting: The Face of Accounting and Auditing in Industry 4.0 - Antoney, Laly; Augusthy, Theresa Josephine (International Multilingual Journal of Science and Technology, 2019)
Keywords: Accounting Education; Block Chain Accounting; DLT; Future Audit; Tripple Entry Book Keeping

Electronic Tax System As A Panacea For Tax Revenue Leakages In Nigeria - Nwamgbebu, Obinna; Oketa, Chiamake; Odom, Amarachi; Nwambe, Cynthia; Nweke–Charles, Uchenna (African Journal of Politics and Administrative Studies, 2019)
The broad objective of the study is to assess the problems of the traditional tax system in Nigeria and establish electronic taxation as a solution to these problems. The study adopted content analysis in analyzing text books, journals, newspapers and other essential materials that were used to obtain the needed information for the study. Extensive review of the literature showed that electronic tax system solves the problem of low tax collection, unavailability of tax statistics and poor record keeping, complex of payment and high cost of tax compliance. The implication of these findings is that an adoption of electronic tax system is an intelligent means of achieving a system of tax administration that allows for the collection and accountability of required taxes at a minimum cost. The study concluded that there are some challenges with the manual system of administering taxes and that modern technology could simplify these challenges and alienate them in the form e-tax. The study therefore recommended that government should support with everything on their disposal the establishment of e-tax administration so as to start ripping the benefit of high rate of compliance among taxpayers at all levels of government in Nigeria.

Adoption, compliance, and consequences of International Financial Reporting Standards in Africa - Tawiah, Vincent K. (Griffith University, 2019)
This thesis investigates the adoption, compliance and consequences of International Financial Reporting Standards (IFRS) in Africa, a continent which has mostly been ignored in prior studies due to the use of generic proxies. Drawing on DiMaggio and Powell (1983), this thesis examines the institutional pressures of IFRS adoption in Africa. Stakeholder salience theory, developed by Mitchell, Agle and Wood (1997), is employed to analyse the determinants of IFRS compliance outside the traditional capital market settings. As regards to the consequences of IFRS in Africa, this thesis analyses the impact of IFRS on audit fees, audit reporting lags and auditor switch. The study used panel data from 54 countries and 205 firms covering the financial years 2003-2016. Secondary data was sourced from reputable database and annual reports of sample companies. Different analytical tools such as ordinary least squares, logit and multinomial regressions were used based on their suitability to address the research questions. The study found that only 18 out of the 54 countries required all listed and large companies to report per IFRS, while 25 did not permit IFRS. The results supported the theoretical prediction that coercive, mimetic, and normative isomorphism influenced IFRS adoption in Africa. Specifically, the World Bank (WB) and International Monetary Fund’s (IMF) influence on African countries in adopting IFRS was not through foreign aid and grants; instead, their recommendations made in the Report on Observance of Standard and Codes (Accounting and Auditing) initiatives. The finding(s) also demonstrated that the presence of global audit firms and the number of years of IFAC membership had a strong association with a country’s decision to adopt IFRS. Moreover, countries with strong professional accounting organisations (PAO) were more likely to adopt IFRS. On IFRS compliance, the study found that the average compliance score among the companies over the period was 70.94%, with a minimum score of 58.59% and a maximum of 83.55%. The findings reported a significant positive association between audit committee competence (ACC) and compliance, and between chartered accountants on board (AOB) and compliance. The thesis also documented that compliance has been increasing over the years. Regarding the impact of IFRS on the audit market, the findings suggested IFRS was positively and significantly associated with an increase in audit fees regardless of early or late adoption. Also, on average, ARL increased by 26% across all samples, with late adopters experiencing 28% and earlier adopters 22% during the adoption year. Contrary to the late adopters, early adopters experienced a significant increase in audit fees during the pre-IFRS period due to the set-up and implementation at the time. In addition, IFRS adoption was likely to cause companies to switch from small audit firms to the Big 4. The findings on adoption suggest that global accounting agencies such as IFAC and IASB should focus on building vibrant national level accounting institutions such as PAOs to facilitate the adoption of IFRS in Africa. The thesis, therefore, adds to the adoption literature the finding that the isomorphic pressures in Africa are different from those suggested in prior studies. The results on compliance imply that companies that appoint more professional accountants to their boards are more likely to comply with the requirement of IFRS. Therefore, it is suggested that companies should engage more chartered accountants in their governance. Also, corporate boards must strive to strengthen their audit committees by appointing more NEDs and CAs to the committee. The findings also provide valuable information for professional accounting organisations on the role of its members (professional accountants) in the effectiveness of IFRS compliance. The findings of the consequences of IFRS on the audit market alert small and medium practitioners (SMPs) in non-IFRS countries of the possible loss of clients to the Big4 due to the adoption of IFRS. To mitigate this effect, the national PAO should build the capacity of their local accountants through training and education to handle the complexities and continuous upgrading of IFRS. Such training is seen as being crucial for SMPs in OHADA countries, Ethiopia, Djibouti and other countries which are in the process of implementing IFRS.
Keywords: Adoption; Africa; Audit market; Compliance; Consequences; IFRS; Institutional pressures; International Financial Reporting Standards; Stakeholder salience

The definitions of ‘inside information’ and ‘insider’ in the Financial Markets Act 19 of 2012 - Van Der Walt, Johann Nico (Stellenbosch University, 2019)
The definitions of ‘insider’ and ‘inside information’ in the Financial Markets Act 19 of 2012 are, as is the case with their international counterparts, central to the Act’s regulation of insider trading. It has long been recognised, however, that those definitions, inherited from repealed companies and market abuse legislation, are cumbersome and counter-intuitive. This state of affairs obtains as the South African legislature has failed to undertake the most fundamental enquiry in formulating a coherent regulatory scheme aimed at prohibiting supposedly wrongful conduct: identifying a single theory of wrongfulness upon which to base its prohibitions. Instead, the definitions include elements of all possible regulatory bases for insider trading, including those having as their object the protection of proprietary rights in information and born out of the fiduciary doctrine. It is argued that the definitions, part of legislation aimed at addressing a financial market wrong, should be formulated with reference to the rights and obligations at play in those markets and the legislature’s objectives for those markets. A proposal is made in that regard.
URI: http://hdl.handle.net/10019.1/105745
Keywords: Finance; Financial Markets Act; 2012; Insider trading in securities; Markets; South Africa

The tax trade interface : an investigation of the influence of the Nigerian income tax incentives on taxpayer behaviour - Aniyie, Ifeanyichukwu Azuka (University of Pretoria, 2019)
The Companies Income Tax Act provides the architecture for corporate income taxation (CIT) in Nigeria. It specifies the rate, the tax base and contains the bulk of the incentives to which qualified corporate taxpayers are entitled. This thesis investigates the influence of incentives on the compliance behaviour of micro and small companies (MSCs) in Nigeria. By Nigeria’s standard, these are companies which: (1) employ between 1 to 49 persons and/or own assets (excluding land and building) valued at less than NGN 100million; or (2) are either private limited companies or one-man businesses. In the context of the Nigerian tax system, MSCs are corporate taxpayers with turnover of less than NGN 200 million. This choice of research population is a consequence of the globally acknowledged niche occupied by MSCs vis-à-vis the of the socio-economic objectives of any state. In the course of the study, the formulated research questions were resolved using a multi-stage mixed methods framework which allowed for the fusion of qualitative and quantitative epistemology as well as facilitated the introduction of pragmaticism into the research process. The thesis, inter alia, identified gaps in the administrative regime of CIT incentives in Nigeria and highlighted the fact that they have the potential to introduce uncertainty into the tax system. In addition, it revealed that the regulatory regime for the role and services of tax intermediaries within the tax system, in terms of current standards and reality, is sub-optimal. On the basis of a survey of a small sample of MSCs, it was concluded that the influence of tax intermediaries with regard to the compliance behaviour of MSCs was marginal. Reason for this was traced to the fact that the role and services of the latter vis-à-vis clients who are MSCs are actuated by variables which are within the psycho-social space of the tax intermediairies and the desires/requests of the MSC. This dismisses, in the context of Nigeria, the notion that the tax intermediary is the initator of every tax dodge. Based on the findings, the thesis, inter alia, recommended a re-orientation in the conceptualisation of tax compliance as the prevailing theoretical premise for the extant tax law and policy does not contemplate that non-economic factors and referents outside the realm of taxation are capable of influencing tax compliance behaviour. In addition, recommendations with the capacity to change the law, policy and administrative regime relating to CIT incentives as well as the role and services provided by tax intermediaries were made after an examination of the situation in Kenya and South Africa.
URI: https://repository.up.ac.za/handle/2263/72637
Keywords: Companies Income Tax Act; Corporate income taxation; Income tax; Nigeria; Tax trade; Taxpayer

Modernisation of customs regulations and practices to combat customs offences in France, South Africa and Cameroon - Kouamo, Juliette Armelle (North-West University, 2019)
The modernisation of customs regulations and practices involves a process of transformation aimed at boosting the capacity of customs agencies so that they can respond more efficiently to the ever-changing trade environment. In the context of this study, the transformation referred to is changes and adaptations of the institutional, structural, legal, practical, and managerial aspects of revenue collectors’ work. Several global changes in international trade prompted the World Customs Organization (WCO), an international customs body, to pilot projects for the modernisation of customs in order to adapt the approach of this administration to the various changes occurring in the field. These changes relate to the increasing volume of world trade, technological advances, the transformation of businesses models and the steady rise in criminal activities and security threats. The modernisation of customs with the WCO's guidance and support entails inviting and empowering member states of the WCO to align their customs regulations and practices with international standards. Customs modernisation became a topic of interest and started gaining worldwide attention when international trade experienced unprecedented changes coupled with technological advances. This has opened debates around issues relating to globalisation, such as the lowering and removal of trade barriers. There is also a necessity to ensure that customs authorities have sufficient strategic controlover imported and exported commodities. It has become imperative for all states to improve their competitiveness in customs through the revision of regulations which give rise to burdensome practices and procedures. The removal of cumbersome legislative provisions and practices will ensure an increment of efficiency in customs processes.Customs modernisation differs in developed, developing or under-developed states. Hence, the approach to customs modernisation differs from one jurisdiction to another. While some states embrace customs modernisation, others are unable, unwilling or merely reluctant to do so. There are different reasons for the variation in states’ attitudes towards customs modernisation. These attitudes are reflective of the political and economic realities prevailing in each state. Some states are open to customs modernisation but lack the financial and structural resources necessary to be vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools. vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools.
Keywords: Customs modernisation; Customs offences; Customs regulations

Curbing transfer pricing manipulation in South Africa : lessons from selected jurisdictions - Mboweni, Abel Mabawuzeni (University of Pretoria, 2019)
Transfer pricing manipulation is a worldwide problem which results in a massive loss of revenue which is meant to finance government socio-economic programmes. South Africa is not immune to this problem. South Africa is losing billions of Rands in tax revenue due to this scourge. This research is an attempt to find ways and means which can be employed to combat or control the problem. In order to find the envisaged solutions, this research investigates the causes of the problem by analysing the weaknesses and the strong points of the arm’s length principle which is the basis of transfer pricing practice in South Africa and elsewhere. The research also investigates and analyses the corporate reasons for Multinational Enterprises (MNEs) to engage in transfer pricing with a view to demonstrating that transfer pricing is a neutral tax avoidance concept if it is applied for genuine business considerations. The investigation also entails analysing the legal framework of transfer pricing in South Africa which is embodied in section 31 of the Income Tax Act 58 of 1962. The research analyses the efficacy of section 31 in dealing with the sophisticated transfer pricing manipulation schemes. In addition, an extensive reference to the Organisation for Economic Co-operation and Development (OECD) Transfer Pricing Guidelines is made as South Africa relies heavily on the guidelines. A comparative analysis of selected topics is also conducted with the United States (US) and India with a view to drawing lessons from those jurisdictions. Based on the outcome of the analysis and the lessons drawn from the comparative analysis, findings are presented followed by legislative proposals or recommendations which will help to eradicate the problem. It is hoped that implementation of the recommendations taking into account the socio-economic conditions of South Africa will help to deal with the problem.
URI: https://repository.up.ac.za/handle/2263/69915
Keywords: Loss of revenue; South Africa; Tax Revenue; Transfert pricing

Le défi de l'Organisation pour l'harmonisation en Afrique du droit des affaires face au développement des marchés financiers africains: Quid de la protection des investisseurs - Sita, Gloria Lubaki (Recht in Afrika, 2019)
By the time the founding fathers of the Organization for the Harmonization of Business Law in Africa (OHADA) signed the Treaty of Port Louis, the financial markets in Western and Central Africa were embryonic. Nowadays the situation has changed and it seems appropriate to reconsider relationship between OHADA law and securities exchange markets. Indeed, OHADA's Community legislation has to deal with the securities markets covered and serve both the proper functioning of the market and the protection of investors. The uniform Act on Commercial Companies and Economic Interest Groupings contains provisions referring to specific financial rules. However, is this sufficient to earn the public trust? Financial market law is a complex discipline. If we supplement this the effort required for investors to find their way between the West African Economic and Monetary Union (WAEMU) or the Economic and Monetary Community of Central Africa (CEMAC) stock exchange law and national constraints throughout OHADA, the following question must be asked: How is the investor's interest protected in this legal jungle? This paper tries to analyse the legal mechanisms of investor protection in the WAEMU Regional Stock Exchange and the Central African Stock Exchange, combining them with the uniform law for commercial companies of OHADA.

The Implementation of Provisions of IFRS Framework and Financial Perfomance of Banks - Anichebe, Alphonsus Sunday; Okpala, Ngozi Eugenia (International Journal of Trend in Scientific Research and Development, 2018)
The need for global financial language gave birth to International Financial Reporting Standards (IFRS). The adoption of IFRS has been argues to have changed the manner in which the financial statements are prepared, presented and reported. IFRS represents a single set of high quality, globally accepted accounting standards that can enhance comparability of financial reporting across the globe. The significant disparities between the Nigerian Statement of Accounting Standards and International Financial Reporting Standards have resulted in the Statement of Accounting Standards being regarded as outdated and incomplete as an authoritative and internationally accepted guide to the preparation of financial statements. The study however examined the extent to which Nigerian banks have implemented the provisions of IFRS frameworks. The sample comprises of fourteen quoted deposit money banks in Nigeria. Specifically, financial statement figures of 2007 – 2011 (pre-adoption period) and 2012 – 2016 (post-adoption period) were utilized. The study adopted the ex-post facto research design. Annual panel data were collected from the financial statements and accounts of 14 deposit money banks quoted on the Nigerian Stock Exchange as well from the Securities and Exchange Commission statistical bulletin from 2007 to 2016. The findings revealed that the return on shareholders’ funds has improved since implementation of International Financial Reporting Standards (IFRS) on Nigerian banks. IFRS implementation has significant effect on the profitability of quoted banks in Nigeria. The implementation of International Financial Reporting Standards (IFRS) has significantly influenced banks’ earnings and it was concluded that IFRS has positive impact on equity and earnings of banks. It was recommended that government and regulatory authorities should organize more quality training to get bankers informed.
Keywords: Banks; Financial performance; IFRS

Business combinations and group of companies : perspectives from accounting, law and corporate finance - Coda, Stefano (Université Paris 1, 2018)
Dans le cadre général des regroupements d'entreprises et des groupes de sociétés, cette thèse porte sur des questions d'intérêt à la croisée de la comptabilité, du droit (notamment les dispositions légales et la réglementation comptable) et de la finance d'entreprise. En ce qui concerne la théorie comptable, le chapitre 2 étudie comment les chercheurs en économie d'entreprise ont compris les groupes d'entreprises, les comptes de groupe et le processus de leur préparation, en particulier par rapport aux juristes italiens. Ensuite, le chapitre 3 reconstruit le processus politique et législatif qui a engendré la naissance du concept de groupe de sociétés dans le corpus juridique italien.Concernant le droit et la politique comptable, une analyse comparative est effectuée au chapitre 4qui montre clairement l'évolution de la notion de contrôle et de son utilisation dans les comptes consolidés (comptes de groupe) et les regroupements d'entreprises (I) en droit européen, (II) selon les normes comptables internationales publiées par l'IASB (International Accounting Standards Board) et (III) par rapport aux principes comptables généralement admis aux États-Unis («USGAAP»). De plus, les chapitres 5 et 6 étudient les effets du lobbying sur les normes comptables concernant les états financiers consolidés et les regroupements d'entreprises publiés par l'IASB. Fait intéressant, les résultats concordent avec une forme de capture du normalisateur comptable international par une catégorie d'institutions financières. En effet, confrontées à un modèle de consolidation prétendument basé sur le contrôle, ces dernières ont plaidé en faveur d'une exception de consolidation fondée sur un modèle de propriété et documentée comme ayant été proposée par les sociétés d'audit américaines dans ce contexte au moins depuis 1995. Ce modèle s’avère avoir trouvé un terrain fertile au sein de l'IASB. En conséquence, d'autres catégories d'institutions financières,telles que les fonds d'investissement à long terme et ceux gérés par une famille tout en préférant un modèle de consolidation différent, ne sont plus autorisées à présenter des états financiers consolidés. En ce qui concerne la finance d’entreprise, le chapitre 7 analyse les implications de différentes décisions de financement dans un nouveau échantillon de fusions et acquisitions entre institutions financières (banques et assurances) consommées dans le monde entier au cours des deux dernières décennies. En particulier, il étudie (I) la relation entre la méthode de choix de paiement (si le prix est payé en cash, en actions ou une combinaison des deux) et le choix du mode de financement d'un regroupement d'entreprises (y compris les instruments hybrides) et (II) la réaction des investisseurs à l'annonce de la combinaison. En ce qui concerne ce dernier point, l'utilisation de deux tests non paramétriques permet de détecter une relation intéressante entre la réaction du marché à l'annonce et les différents modes attendus de financement de la transaction.
Keywords: Accountings standard setting; Comptabilité; Consolidation exemption; Egroupements d'entreprises; Finance d'entreprise; Finances; Financial institutions; Gestion d'entreprise; Groupes de sociétés; IASB; IFRS 10; IFRS 3; Mergers and acquisitions; Method of payment; Politics; Politique comptable; Sources of fundings; Économie d'entreprise

Effect of IFRS on Value Relevance of Accounting Information: Evidence from Quoted Manufacturing Firms in Nigeria - Ezejiofor, Raymond Asika (International Journal of Trend in Scientific Research and Development, 2018)
This study evaluated the extent to which value relevance of financial information in Nigerian manufacturing firms has improved after the implementation of International Financial Reporting Standards (IFRS). Specifically, the study intended to: Ascertain the extent the adoption of IFRS has significantly improved the book value per share of manufacturing companies in Nigeria; Determine the extent the adoption of IFRS has significantly improved the Earnings Per Share of manufacturing companies in Nigeria and Examine the extent the adoption of IFRS has significantly improved the cash flow of manufacturing companies in Nigeria. Ex-post facto research design was adopted for the study. A sample of 54 manufacturing companies was randomly selected from manufacturing companies quoted on the Nigerian Stock Exchange for the periods of 2008-2015. Data for the study were obtained from the annual reports and accounts of the sampled companies. Specifically, a modified price model for detecting value relevance of accounting data for two different periods was employed. Regression Analysis and Chow test statistical tools were used to analyze and validate the data with aid of SPSS version 20.0. The study found that the adoption of IFRS has improved the book value per share, market share price, Earnings Per Share and cash flow of manufacturing companies in Nigeria. The implication of findings is that the value relevance of accounting information of manufacturing companies is more sensitive during Post-IFRS era than the Pre-IFRS era. The findings also imply that the book value per share, market price, earnings and cash flow have become informative to equity investors in determining the value of firms following IFRS adoption. The study recommends among other things that the accounting information for book value per share should be communicated to the investing public; and such information should be of high quality to avoid negative consequences on the part of investors.
Keywords: Accounting information; Manufacturing company; Value relevance

Application of the OHADA Accounting System by Companies in DRC, Current Status and Prospects: Case of the City of Bukavu - Kulondwa, Safari; Nshobole Bahirwe, Nathalie (Journal of Accounting, Finance and Auditing Studies, 2018)
The objective of this research was to determine the current status of the application of the OHADA accounting system in DRC, five years after its adoption. A survey was conducted on thirty small and medium-sized enterprises in Bukavu to determine the level of compliance with the SYSCOHADA principles, the degree of harmonization of accounting practices and the difficulties related to the application of this system. The results shown consistently that compliance with Syscohada principles is not absolute, the level of Harmonization is still low and finally companies in DRC still need time to fit into the OHADA accounting system.
Keywords: Accounting Practices; Accounting Principles; Harmonization

A contract theory approach to Islamic financial securities - Hanif Arbi, Lukman (La Trobe University, 2018)
The aim of this thesis is to investigate the economic and financial substance of certain contractual requirements imposed by Islamic commercial law as well as some of their implications. More attention is given to requirements that have financial implications and are related to those discussed in the contract theory literature. We divide our investigation into four parts. The first part is an examination of the fundamental transactional requirements in Islamic commercial law, focusing on those related to four primary Islamic Financial Securities (IFSs). In the second part, we use our findings to construct an alternative asset pricing methodology. We also explore our findings in the third and fourth parts using the principal-agent model of Holmström and Milgrom (1991). More specifically, we use it to respectively model the relationship between underwriters and Islamic commercial law regulators as well as consider the case of ambiguous incentive contracts. Each part of our investigation has yielded substantial contributions to the literature as follows. Firstly, our examination of Islamic commercial law principles and contracts reveals that there are indeed legal requirements which have direct implications for financial models, such as the need for a liquidity discount in receivables-based ṣukūk as they are – in principle – non-tradeable. Secondly, the asset-pricing model we have constructed allows us to examine the equilibrium return and investment levels of IFSs. This allows us to derive conditions at which one security yields higher returns than another. Thirdly, our cooperation model suggests that cooperation between underwriters and Islamic commercial law regulators is only beneficial for an issuer of a structured Islamic financial product if their synergy benefits are over a certain level. Lastly, our investigation into ambiguous incentive contracts demonstrates that it is never beneficial for principals to offer such contracts to ambiguity averse individuals as it unambiguously reduces the principal’s profit.

The Impact of Private Securities Lawsuits on Accounting Conservatism and the Moderating Influence of Corporate Governance - Kerr, Ryan (Victoria University of Wellington, 2018)
This study investigates the impact of conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit, on the level of accounting conservatism in financial reporting. This study also investigates the moderating influence of corporate governance on the level of accounting conservatism following conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit. The study uses a sample of 617 privately enforced disclosure-related securities lawsuits against listed US firms, taken under SEC rule 10b-5 of the 1934 Securities Exchange Act, over the period 2002 to 2010. The results of the study indicate that following both the conduct that gives rise to a securities lawsuit, and the filing of a securities lawsuit, firms adopt higher levels of accounting conservatism. However, the study finds no evidence that corporate governance moderates the impact of securities lawsuits on the level of accounting conservatism.
Keywords: Accounting Conservatism; Governance; Securities Lawsuits

An evaluation of market responses to corporate disclosures in a continuous disclosure environment - Li, Hanqiao (Victoria University of Wellington, 2018)
Corporate disclosure has attracted the attention of researchers from the accounting and capital markets. Researchers have been trying to better understand how capital markets respond to corporate disclosures. This study explores the short- and the long- term market effects of corporate disclosures in a continuous disclosure environment. This study aims to find the answers to the following research questions. (1) How market (price/volume) sensitive is the information contained in each disclosure category in a continuous disclosure environment? (2) How quickly is the value-relevant information incorporated into share prices before the annual earnings announcement is released, and how can company announcements promote this timeliness of price discovery? Specifically, this study examines the extent to which the Australian share market reacts to new public information immediately after the information is released, and the impacts of announcement frequency as to different continuous disclosure categories on the timeliness of price discovery (also known as the speed of price discovery). Prior research has mostly concentrated on a single type of information event to examine the information’s market consequences by monthly, weekly or daily data. Instead, by covering all public announcements and using tick (transaction) data to calculate intraday abnormal returns and abnormal trading volumes, this study examines which type of announcement has the largest immediate market responses, and compares the magnitude (with positive/negative signs) of market reactions to different announcement categories on the Australian Securities Exchange (ASX). This study is more attractive under the Australian Continuous Disclosure Regime (CDR) because of the classification system regarding the market-sensitive announcements. Whether or not an announcement is market-sensitive is predetermined by ASX ‘specialist staff’ before the announcement is released on the market. This study investigates how the market interprets the announcement, examining market sensitivity from both the share price and trading volume movements after the announcement is available to the market. In other words, to some extent, the ‘market sensitivity tag’ shows the announcement that the market should react to, and this study reveals the announcement that the market does react to. Focusing on market-sensitive announcements, except for the ASX Query, the significant results show a positive association between announcement categories and intraday Cumulative Abnormal Returns (CARs). Share prices react the most to Progress Reports and to Asset Acquisition & Disposal, and the least to Periodic Reports and Issued Capital. Share price reactions to Distribution Announcements and Other are in the middle. There are at least two possible reasons for the different market reaction magnitudes. One is the information materiality nature: if one type of information is more important to investors than other information, this may cause higher abnormal returns on the market. The other is the information predictability: if there has been a lot of relevant information available in previous days or months, share prices could adjust to the information more smoothly. In terms of the trading volume reactions, intraday Abnormal Trading Volumes (ATVs) are observed after the release of Progress Reports, Asset Acquisition & Disposal, Issued Capital and Periodic Reports. After separating good and bad news subsamples, the results show that Progress Reports and Asset Acquisition & Disposal tend to indicate good signs to the market and cause larger trading volumes. Periodic Reports and Issued Capital could contain either good or bad news, but the trading volumes are driven by bad news. The results also reveal that company size is an important factor. Large companies tend to have relatively small market responses after information is released, which confirms that the larger companies are more stable. This study also evaluates long-term market effects of corporate disclosures by examining the timeliness of price discovery (also known as the speed of price discovery). It is the timeliness with which the full value relevant information is priced over a year before the annual earnings announcement is released. Previous literature has revealed that earnings announcements convey information, because significant stock returns or increased trading volumes are observed around the time that earnings announcements are released. However, it has also been suggested that there are other more timely information sources available that contain essentially similar or even the same value-relevant information. By the time preliminary final reports become available to the market, any potential value-relevant information has been included in the share price. The CDR again provides an attractive environment to examine the impact of corporate disclosures on the timeliness of price discovery, because listed companies have to disclose to the market before any other media sources. This enables an exploration of the relationship between the timeliness and the frequency of continuous disclosures. If the CDR is efficient in keeping investors fully informed, there should be no stock price surprise after the earnings announcement is released. Given the importance of the Preliminary Final Reports to the timeliness metric and the fact that the immediate market reaction tests only cover announcements released during trading hours, this study investigates in depth the Preliminary Final Reports and finds some evidence that companies tend to release bad news after the market closes and/or on Fridays. In terms of the impacts of announcement frequency on the timeliness of price discovery, following the step ‘All announcements – Periodic/Non-periodic announcements – Detailed categories of Non-periodic announcements’, the findings reveal that only earnings-related and cash flow announcements (Periodic Reports, Distribution Announcements and Quarterly Cash Flow Reports) can accelerate the timeliness of price discovery. Unfortunately, the results do not confirm that more announcements on the market could promote the timeliness with which the value-relevant (i.e. earning/income) information is incorporated into share prices. In addition to announcement frequency influences, the price discovery process is faster for companies with better share performance, are larger or have greater profitability. Financial companies have a timelier price discovery process than other companies; the price discovery process of financial companies was affected more by the 2008 – 2010 Global Financial Crisis than that of other companies. This study contributes to the market reaction literature by covering all categories of company announcements and comparing immediate market consequences for each type of announcement, and builds upon the timeliness of the price discovery literature by linking the announcement frequency of each continuous disclosure category to the timeliness with which annual earnings information is incorporated into share prices.
Keywords: Announcement categories; Announcement frequency; Continuous Disclosure Regime; Immediate market reactions; Market sensitivity; Timeliness of price discovery

Financing Infrastructure in Africa - Ashiagbor, David; Deiana, Rodrigo; Kappeler, Andreas; Minsat, Arthur; Nguyen-Quoc, Thang; Bank, European Investment (European Investment Bank, 2018)

Gaps in the IFRS Conceptual Framework - Barker, Richard; Teixeira, Alan (Accounting in Europe, 2018)
The stated purpose of the IFRS Conceptual Framework is to assist the IASB to develop Standards that are based on consistent concepts, and also to assist preparers to develop consistent accounting policies when Standards either do not apply or allow a choice of accounting policy. Yet, the Framework actually does surprisingly little to help the IASB (or preparers) determine which assets, liabilities, income and expenses should be recognised, and how they should be measured. The Framework’s focus on assets and liabilities implies that the accounting can, and should, be determined from the balance sheet. Yet, many current financial reporting requirements focus initially on the income statement, and so they are not so much derived from the Framework as instead in need of being reconciled back to it. At its heart, the problem here is that, while the Framework states that accrual accounting provides a better basis for assessing past and future performance than cash-based information, it does not explain why. To do so would require a conceptualisation of how entities’ business models are employed to create value, and of the strengths and limitations of accounting data in enhancing investors’ understanding of that value-creation. The lack of explanation of the purpose and informational objectives of accruals, how they relate to business models and how they cause the income statement and the balance sheet to interact are gaps in the Framework. Filling those gaps would provide a more robust, and natural, way for the IASB to develop recognition and measurement requirements in its Standards.
Keywords: Accruals; Conceptual framework; IFRS; Measurement; Unit of Account

The Banking Sector in the Central African Economic and Monetary Community (CEMAC): Great Potential in the Face of Enormous Challenges - Benhamdane, Jad; Hidane, Said; Stijns, Jean-Philippe; Bank, European Investment (European Investment Bank, 2018)

An analysis of the effects of tax policy and tax abuse on the fulfilment of human rights in developing countries : the case of Zambia - Chigubu, Salome (University of Johannesburg, 2018)
Keywords: Droit fiscal; Pays en voie de développement; Politique fiscale; Tax; Zambie

Financial Accounting: International Financial Reporting Standards - Harrison Jr., Walter T.; Horngren, Charles T.; Thomas, C. William (Bill); Tietz, Wendy M.; Suwardy, Themin (Pearson, 2018)

Accounting Translation of Corporate Social and Environmental Expenditures in Small and Medium Industry: What Evaluation Approach and what Accounting Scheme? - Missomba, Jean Christian Ewane; Hanko, Osée (Research Journal of Finance and Accounting, 2018)
The question remains whether societal reporting integrates the field of financial reporting. This old debate is repeated to scrutinize the case of African companies with strong cultural roots, which do not publish alternative societal documents to traditional financial reports. Through stakeholder theory (Jones and Wicks, 1999), this study aims to analyze the phenomenon, by describing the process of accounting recordings for social and environmental information (SEI) identified by the ISO 26 000 standard in an oil Company operating within OHADA Jurisdiction. The results indicate the presence of mandatory SEIs in the financial statements, which visibility depends on the pressure exerted by the State and the accounting regulations in force. Voluntary SEIs are not visible.
Keywords: Financial reporting; ISO 26000; Social and Environmental Information (SEI); Stakeholder Theory

Essays on Bank risk, capital and Lending - Alraheb, Tammuz (Université de Limoges, 2017)
Cette thèse examine trois questions importantes dans le secteur bancaire, à savoir le risque, les fonds propres et le crédit. Elle comprend trois essais empiriques. Le premier chapitre analyse l'impact du «printemps arabe» et de la crise financière mondiale de 2007-2008 sur la stabilité du secteur bancaire dans la région MENA. Les résultats montrent que le «printemps arabe» n'a pas eu d'effet négatif sur la stabilité des banques, alors que la crise financière mondiale a considérablement réduit leur stabilité. Le deuxième chapitre étudie le rôle joué par l'environnement institutionnel dans la mise en place de coussin de fonds propres par les régulateurs ou par les banques en interne. D’après les résultats, pour que les ratios de capital réglementaire soient efficaces, l'environnement institutionnel ne doit pas être négligé lors de la mise en place de ces ratios. Le troisième chapitre étudie les différents effets des droits des consommateurs et des créanciers sur le coût des prêts. Les résultats révèlent que le coût des prêts augmente en présence de lois strictes sur la protection des consommateurs, tandis que l'augmentation des droits des créanciers réduit ce coût.
Keywords: Bank Capital Structure; Bank foreign expansion; Bank loan growth; Banque expansion à l'étranger; Banques; Consommateur (protection); Cost of intermediation; Coût de l'intermédiation; Creditors' rights; Crise économique (2008); Croissance du crédit bancaire; Droits des créanciers; Structure du capital de la Banque

Financial Development, Integration and Access to Finance in Africa - Essien, Grace Etim (University of Leeds, 2017)
This thesis is made up of three empirical studies that fall under the general classification of international and financial economics, particularly the study focuses on the financial system of selected African countries. The first empirical study presented in Chapter 2 examines the role of financial development in improving the effect of FDI on the economic growth of some African countries. Investigations were conducted to pinpoint which financial structure could provide the best improvement by applying the bank-based vs. market-based debate. Results from the regression analysis conducted show that the effect of FDI on economic growth becomes significant only when financial development measures were factored in. Analysis of results indicate that development of the overall financial system of African countries would be more beneficial in comparison to developing either the banks or financial markets alone. Chapter 3 empirically measures the level of financial integration in Africa’s Regional Economic Communities (RECs) using beta and sigma convergence to measure the speed and degree of financial integration in four RECs. These chapter also theoretically examines how regional financial integration contributes to financial development and economic growth in Africa. Analysis of the results show that Africa’s RECs are integrating at a relatively slow and diverse rate. Therefore, policy makers in Africa would need to focus on reform strategies that would strengthen financial integration in their regions. A fully financially integrated system would contribute immensely to financial development and promote sustainable economic growth. The fourth chapter investigates the effect of access to finance on firms’ productivity. Using cross-sectional firm-level data to estimate the effect of access to finance on labor productivity, total factor productivity (TFP), and the stochastic frontier trans-log model. This study estimates an instrumental variable (GMM) model to address potential endogeneity bias between access to credit and firms’ productivity. The results obtained show that the lack of access to finance negatively affects the productivity of firms in Africa. This study suggests that the development of a balanced financial system should be of topmost priority to policy makers. This ensures that more finance is channelled towards those firms whose productivity depends heavily on the availability of finance irrespective of their characteristics. This would result in firms increasing their investments in productivity-enhancing activities, which would benefit long-term economic growth

The taxation of small business in developing countries - AKM, Atiqul Haque (Monash University, 2017)
The thesis attempts to explore an efficient policy and administrative framework to tax the small businesses in developing countries. In order to approach the policy and administrative problems concerning the taxation of small business in developing countries this thesis asks How can small businesses be efficiently taxed in developing countries? This thesis over eight chapters qualitatively explores this research question. The analyses conclude that first, in a typical developing country a well-designed simple to follow presumptive tax regime is more efficient than the actual account based tax system. Second, this thesis argues that the noncompliance of small businesses in developing countries may not be adequately explained by the standard expected utility based compliance models. The leading tax compliance models which mainly emphasise on the perceived reward from evasion might ignore some crucial factor that constitutes the tax compliance environment of small businesses in developing countries. This thesis illustrates broadly the typical tax compliance environment of small businesses. It argues that a simple to follow tax system that requires a minimal level of taxpayer compliance would attract a section of small taxpayers into the formal tax net. Third, this thesis demonstrates that there are crucial differences between typical urban and rural businesses. A small business tax regime should have a separate set of presumptive instruments for each class of small business in order to make an efficient estimate of their economic activities. Fourth, this thesis analytically examines the presumptive methods and their practical applications. The findings suggest that in developing countries presumptive tax methods have been adopted mostly in arbitrary manner, without the objective considerations to many crucial design issues. Fifth, this thesis has developed a focused analysis on the taxation of urban small businesses in the contexts of developing countries. This thesis analyses some crucial characteristics of urban small businesses and stresses that enterprise formalization should be a key element of urban small business tax policy. For a meaningful expansion of the tax net, tax administration should put more focus on urban small businesses as these businesses have relatively more potential to grow as more stable and sustained taxpayers. This thesis concludes that a turnover based presumptive taxation is more efficient to tax the urban small businesses. Lastly, this thesis explores the issues concerning the taxation of rural small businesses. This thesis reports that the overall tax burden on the agricultural income had substantially declined over the last few decades. Developing countries should not ignore the tax potential of the rural taxpayers. In a typical developing country an asset based presumptive tax system is more efficient to tax the agricultural income of the rural small businesses. This thesis has argued that it would be more efficient to adopt a single asset based presumptive income tax replacing all the prevailing taxes on the agricultural income such as agricultural land tax, wealth tax and income tax.
Keywords: Fiscal policy; Small business taxation; Taxation administration; Taxation in developing countries; Taxation law; Taxation of rural small business; Taxation of shadow economy; Taxation of urban small business; Taxation policy

Towards responsible lending in Namibian consumer credit law : a comparative investigation - Asheela, Ndatega Victoria (University of Pretoria, 2017)
The regulation of consumer credit in Namibia mainly is provided for by the Usury Act 73 of 1968 and the Credit Agreements Act 75 of 1980. These legislative enactments originated in South Africa and were applied in South West Africa during the period of South Africa’s mandate over what is now the Republic of Namibia. Despite the fact that these enactments are over 35 years old, they are substantially unchanged. In response to an awareness of the threat of consumer over-indebtedness and other events such as financial crises, the purpose in this thesis is to undertake a situational analysis of the debt prevention measures as provided for by the Namibian legislative framework and the extent of protection these measures afford consumers in terms of irresponsible credit and over-indebtedness. A broad survey of the policies aimed at promoting responsible lending benchmarks the Namibian consumer credit regulatory framework against the leading international best principles which have been developed in response to global economic challenges. The Namibia Financial Institutions Supervisory Authority in the 2014 Microlending Bill proposes to introduce responsible lending practices in the form of a compulsory pre-agreement assessment of the prospective consumer before providing them with credit. In a comparative investigation, the creditworthiness assessment and related measures central to the responsible lending regimes in South Africa and Australia are considered. Measuring the Namibian consumer credit regulatory framework against these recent developments, it is submitted that the current debt prevention measures are inadequate in protecting consumers from irresponsible credit lending and the risk of consumer over-indebtedness. This thesis supplies reasons for the need in Namibia to update the regulatory structure of the credit industry in order to protect consumers. As a contribution to the promotion of a culture of responsible lending in the Namibian consumer credit market, the thesis proposes the introduction of responsible lending measures in Namibia’s consumer credit legislative framework.
URI: https://repository.up.ac.za/handle/2263/65659
Keywords: Consumer credit; Debt; Namibia

International Accounting Standards in Africa: Selective Recursivity for the 'Happy Few'? - Botzem, Sebastian; Quack, S; Zori, Solomon George (Global Policy, 2017)
This study explores recursivity in international accounting standard-setting, focusing on participation of actors from African countries. While the International Financial Reporting Standards (IFRS) Foundation bases its legitimacy claims as a global standard-setter on a combination of expertise and a formally transparent set of recursive procedures for consultation of stakeholders, empirical results show that participation in the latter is geographically very uneven. The article argues that conceptual mismatch between the standard-setter's objectives on the one hand and the socio-economic, cultural and political conditions in many African countries on the other leads to selective recursivity that is problematic for the former's legitimacy and effectiveness. These findings are of wider relevance for debates on global standard-setting and development.
Keywords: Accounting Standard; Africa; Economics of Culture; IFRS; International Accounting

An appraisal of selected tax-enforcement powers of the South African revenue service in the South African constitutional context - Fritz, Carika (University of Pretoria, 2017)
There is tension between the South African Revenue Service’s duty to collect taxes on the one hand, and its duty to respect taxpayers’ rights on the other. An environment where there is clearly respect for the rights of the taxpayer may indeed result in increased voluntary compliance. This thesis constitutes a comparative appraisal of whether the following enforcement powers of the South African Revenue Service (“SARS”) in the South African constitutional context, namely (i) SARS’ power to conduct searches and seizures in order to verify compliance and investigate the commission of offences; (ii) the “pay now, argue later” rule; and (iii) the appointment of a third party on behalf of a taxpayer are in accordance with the Constitution of the Republic of South Africa, 1996 (“Constitution”). It is argued that these powers do not necessarily conform to the Constitution’s values and the fundamental rights contained in the Bill of Rights in Chapter 2 of the Constitution. To address the apparent shortcomings in the current dispensation, the thesis compares these enforcement powers of SARS with similar powers afforded to the revenue authorities of Canada, Australia, New Zealand and Nigeria. Important conclusions are drawn from this comparative review and a number of recommendations for law reform are proposed which, if implemented, would align these enforcement powers with the provisions of the Constitution. The recommendations entail, inter alia, that the seizure component of a search and seizure process should be treated separately, that half of the payment obligation should be suspended until the dispute is heard by an impartial forum, and that an objective measure must be in place to ensure that a taxpayer is able to afford basic necessities when a third party appointment is made.
URI: https://repository.up.ac.za/handle/2263/62233
Keywords: Recouvrement fiscal; South Africa; Tax-enforcement power

Three Essays in Bank Financial Reporting - Liu, Yi (McMaster University, 2017)
This thesis investigates three important issues on bank financial reporting quality: 1) the impact of banks’ retail versus wholesale funding structure on their earnings quality, 2) the implications of economic and monetary policy uncertainty for banks’ earnings opacity, and 3) the relationship between banks’ bad time history and accounting conservatism. In the first essay, we examine the implications of banks’ funding strategies for banks’ earnings quality. We find that banks’ greater reliance on retail deposits over wholesale funds is negatively and significantly associated with the magnitude of earnings management through discretionary loan loss provisions, the likelihood of meeting-or-beating earnings benchmark, and the extent of income smoothing through loan loss provisions. This finding is consistent with the arguments that retail deposits are relatively more stable and information-insensitive, represent a more conservative business model, and attract more intensive monitoring from the Federal Deposit Insurance Corporation (FDIC) than wholesale funds, thereby improving banks’ financial reporting quality. In the second essay, we investigate whether economic and monetary policy uncertainties affect banks’ earnings opacity. When economic and monetary policies are relatively uncertain, it is easier for bank managers to distort financial information, as unpredictable policy changes make assessing the existence and impact of hidden “adverse news” more difficult for investors and creditors. Policy uncertainty also increases the fluctuation in banks’ earnings and cash flows, providing additional incentives for bank managers to engage in earnings management. Our results show that uncertainty in economic and monetary policy is associated with greater magnitude of discretionary loan loss provisions, higher likelihood of just meeting-or-beating the prior year’s earnings, and lower levels of accounting conservatism, suggesting that economic and monetary policy uncertainties lead to higher banks’ earnings opacity. In the third essay, we examine the impact of banks’ bad times on the conservatism of accounting policy. Specifically, we investigate two types of bad times: banks’ own past experiences of undercapitalization and their experiences of witnessing the failures of other banks in state-wide and county-wide crises. We find that both types of banks’ bad times are positively related to timelier recognition of earnings decreases versus earnings increases in accounting income. We also find that following exposure to bad times, banks increase their allowance for loan losses. Collectively, our results suggest that bank-specific bad times and macro-level banking crises lead to greater bank accounting conservatism. These findings support the arguments that banks exposed to past crises overweight their bad time history, and become more cautious and pessimistic about their future earnings performance and loan quality.

Strategies adopted by Commercial Banks in Kenya in Response to the Law Capping Interest Rates - Ragor, Rodgers Kiptoo (University of Nairobi, 2017)
The ability of an organization to adjust its operation in light of the evolving changes in their operating environment determines the sustainability of the business unit in both the short and long term. The objective of the study was to determine the response strategies adopted by Kenyan commercial banks in response to the interest capping laws. A descriptive cross-sectional design was used. The population of the study was 42 commercial banks operating in Kenya. Primary data was collected using a questionnaire that was both closed and open ended. Data was analysed using the descriptive statistics. The study found that banks have employed adaptation strategies through working with other partners in the banking sector to leverage their synergy and concentrate on areas that enhance competitive advantage. The research findings also reinforced the need for the banks to work together as a sector and attempt and change the laws that inhibit their operations through lobby groups in parliament and other forums. The study also show that there exists a link between firms‟ strategic activities and their strategic responses and therefore, bank managers should diversify their product range especially to the youth who are apt in using the mobile technology to access services and improve the bank level of efficiency and effectiveness in their operations. The study recommends that the commercial banks ought to conform to the regulations to attract customers while the Central Bank as a regulator should likewise be sensitive to the operating environment and should be flexible in setting the rules in order to attract investment and support the growth in the banking industry. The Interest capping law is still at its infancy stage in Kenya and thus there is room for further research as the full impact of the law is realized in the long term.

Non-discrimination in international economic law - Risvas, Michail (University of Oxford, 2017)
This thesis examines the jurisprudence of the World Trade Organization (WTO) Panels and Appellate Body (AB) and investment tribunals on non-discrimination clauses contained in the WTO agreements and investment agreements respectively. The thesis puts forward an alternative conceptual perspective through which the interpretation of non-discrimination provisions in international economic law could be analysed. It is argued that nondiscrimination obligations (as every legal rule to a greater or lesser extent) are inherently indeterminate. This is a fortiori the case in regard to non-discrimination provisions due to their link to the concept of equality. The concept of equality is open-ended and value-laden: its content depends on the prioritisation of different values. Thus, equality in the economic sphere can accommodate different conceptions which reflect different ideological approaches in relation to regulation, economic development and the proper role of the State in the economy. International courts and tribunals enjoy broad discretion in selecting which conception of equality to adopt when interpreting non-discrimination clauses. This indeterminacy is a positive characteristic of international economic regimes. Both the WTO and the investment arbitration regime are equipped with institutional characteristics which enable the contestation of different ideological approaches and promote pluralism. In the WTO context, this role is fulfilled by the institutional structure of the organization which facilitates the dialogue between the WTO members and the WTO Dispute Settlement System. In the realm of international investment arbitration, the mechanism of party-appointed arbitrators, despite its shortcomings which can be addressed, ensures value pluralism.
https://ora.ox.ac.uk/objects/uuid:23e7e195-c657-46d0-9a21-bde0c793dc45

Tax Mobilization in Sub-Saharan Africa: The Impact of Tax and Business Law Reforms - Bertinelli, Luisito; Bourgain, Arnaud (Economics Bulletin, 2016)
This paper contributes to measuring the influence of business (and tax) law reforms on sub-Saharan African countries tax mobilization ability. Relying on a new business law reform indicator, our results validate the significant impact of corporate law modernization on governmental revenue, and unearth a complementary effect between business and tax law reforms.

Sovereign wealth funds in international economic law - Dekastros, Michail (European University Institute, 2016)
Sovereign Wealth Funds have been the new 'rising star' of the global economy for a few years. Host States have reacted to their rise cautiously and have quite frequently cited 'national security' as a justification for maintaining an absolute degree of freedom in regulating their entry into their markets. This thesis is arguing that a substantial proportion of regulatory concerns that surround the operation of SWFs are actually not of a national security nature—at least as perceived by the relevant instruments regulating investment in International Economic Law. As a consequence, the current regulatory framework screening SWFs investments a priori is both legally and normatively problematic and, in fact, it constitutes a form of protectionism. As an alternative, this thesis suggests that SWFs ought to be primarily regulated after their entry into Host States' markets. In that context, a proper conceptualisation of the principle of non-discrimination that takes into account the 'regulatory unlikeness' between SWFs and other market suppliers/investors will allow the Host States to properly regulate them after their entry into their markets. Such a conceptualisation – contrary to usual analyses – draws heavily from International Investment law in order to interpret the relevant provisions of the GATS.
Keywords: Foreign investment; International law; Sovereign wealth funds

Assessment of Compliance with OHADA Uniform Accounting Act by Public Limited Companies - Fossung, Michael Forzeh (Accounting and Finance Research, 2016)
Francophone African countries have made a tremendous effort in harmonising domestic standards and reporting with the International Financial Reporting Standards (IFRS). Moving from two distinct OCAM streams to two OHADA streams (effective 1985) and now one OHADA Uniform Accounting Act embodying 17 member countries (effective 2001) is a milestone towards harmonisation of reporting practice both domestically and internationally. This empirical study examines whether the effort of harmonisation, especially after the 2001 standards has resulted in the successful convergence of firms' accounting practices by analysing public limited liability companies' compliance with the OHADA Uniform Accounting Act and if such compliance has improved over time. The study has been carried out using the 2008 and 2009 annual reports of three public limited companies in the OHADA zone that translate their financial statements into IFRS. The ranks of closeness and compliance index have been used to analyse data. Findings reveal a relatively high level of compliance with the accounting regulation by sampling limited liability companies. The results also give an indication of harmonisation in accounting practice of limited companies within member countries as they were found to be substantially consistent in compliance, especially in countries that have instituted the Statistics and Tax returns (or "DSF") as a reporting medium.
Number: 3

Reflections on the Nexus Between Public Procurement Reforms and Economic Development in Nigeria - Okolie, Aloysius-Michaels; Nnamani, Kelechi (African Journal of Politics and Administrative Studies, 2016)
Corruption has widely been recognized as one of the impediments to the socio-economic cum political development of Nigeria. By 2000, it was observed that the conduct of government business in Nigeria had become difficult and expensive due to pervasive corruption, particularly procurement fraud. Although procurement fraud is one of the most common avenues of corruption in most countries, its incidence in Nigeria by 2000 was particularly widespread. To reverse this ugly trend, the Nigerian government initiated the public procurement reforms with a view that a corrupt-free procurement process will among other things, promote economic development in the country. Consequent upon the reform, the Public Procurement Act was enacted while the Bureau of Public Procurement was established to ensure due process, accountability and transparency in the award of government contract. In this light, this study evaluated the impact of the public procurement reforms on the economic development of Nigeria. We relied on documentary method of data collection and content analysis of data. Meanwhile, employing the basic propositions emanating from the Marxist theory of the Post-Colonial State, this study noted that the nature and character of Nigerian state undermined the procurement reform from achieving its expected goals. We however, recommended for the removal of the immunity in the constitution and strengthening of the anti-graft agencies in Nigeria.
Keywords: Corruption; Economic Development; Public Procurement; Reforms; Transparency

The Quality of External Audit in OHADA Space: A Qualitative Study with Board of Director’s Members’ Perception as Understanding Variable - Hanko, Osée (Applied Finance and Accounting, 2016)
Audit quality has been evaluated in academic literature accordingly with auditor qualities, due to the difficulties of observing auditing technical process itself. The qualities of a good auditor are then competence and independence, sine qua none conditions of audit quality. That approach is otherwise valid only if there is a valuable framework like stock market where auditor’s competence and independence could be observed. In OHADA space countries, the financial market is approximately off. It is therefore impossible to assess audit quality the way it has been done in prior literature. This study suggests a new approach of assessing audit quality in OHADA countries in relation with audit committees member’s perception of auditing process. Using an innovative qualitative approach inspired from Manita (2008), the results suggest to take into account the auditor’s knowledge of the company, the relevance of the identified zone of risks and the degree of communication with the board of directors.
Number: 2

An investigation into customer accounting in customer-focused organisations - Bates, Ken (Victoria University of Wellington, 2016)
Management accounting information should aid management in the design and implementation of strategy. Firms adopting a customer-focused strategy need customer accounting (CA) metrics. Yet accounting literature provides limited insights into what CA metrics are used, how they are used, or what factors influence CA measure choice or hinder more widespread adoption of CA practices. This thesis enhances knowledge of actual CA practices as they operate in firms with a customer-focused strategy and uses contingency theory to explain the choice of CA practices and their use in three exploratory case studies consisting of two national banks and a global courier company. The two strategic business units in Alphabank employ locally-developed, activity-based costing systems to produce CA information. Personal Banking incorporates a ‘customer needs met’ variable into a customer lifetime value measure used to segment customers based on potential profitability. Business Banking is smaller and currently uses historical customer profitability analysis at the individual customer level. Despite Alphabank’s overall customer-focused strategy, only product profitability is reported at executive level, and tensions between finance and operations potentially hinder more widespread CA usage. Betabank offers excellent customer service, but despite being very customer-focused they do not measure customer profitability. Executives use predominantly aggregate financial figures with a focus on net interest margin. Service excellence is paramount and Betabank do not consider financial CA useful as they do not segment customers. However, they extensively use non-financial customer related measures to monitor excellent customer service provision in order to enhance future profitability. The courier company uses activity-based costing to produce historical customer profitability analysis which reports direct margin, gross margin and earnings before interest and tax. The analysis discloses significant profitability differences between customer segments, and even between individual customers within segments where customer relationship management is employed. They do not measure full customer lifetime value but the next year’s customer profitability can be modelled using historical cost drivers. Financial CA measures drive initiatives to enhance customer profitability and/or trigger price negotiations. Non-financial CA measures are used to drive the customer-focused strategy and enhance profitability. The three cases demonstrate a considerable diversity in their usage of financial CA practices, with Betabank choosing to use no financial CA at all. Competitive intensity and the use of customer relationship management are found to be key drivers of CA usage at the individual customer level. Segmental customer profitability analysis is used when a large number of customers receive standard services at standard prices. No individual customer profitability analysis is needed for such homogenous customers as they can be efficiently managed using revenue. Non-financial CA measures were found to be widely used and hence a key contribution of this study is that in practice customer-related, non-financial performance measures are a key component of CA practices and may be extensively used to drive a customer-focused strategy. From case analysis a contingency-based framework has been develop which identifies combinations of factors with strong interrelationships and common influences on the choice and usage of CA measures. This framework provides three main groupings of contingent factors (type of competitive advantage, level of customer heterogeneity, and stage of organisational development) which together potentially have strong predictive power in relation to the nature of CA measures which benefit firms with a customer-focused strategy.
Keywords: Bank; Courier; Customer Accounting; Customer Profitability Analysis

Value and risk effects of financial derivatives: Evidence of corporate governance on hedging, speculation and selective hedging strategies - Tashfeen, Rubeena (Victoria University of Wellington, 2016)
This study investigates whether there is a relationship between corporate governance and derivatives, whether corporate governance influence in firms impacts the association between derivatives and firm value, and whether corporate governance influence affects the association between derivatives and cash flow volatility, stock return volatility and market risk. This study uses two different data samples of publicly traded firms listed on the New York Stock Exchange. The first sample comprises a panel of 6900 firm year observations and the other consists of a panel of 6234 firm year observations both over the eight-year period from 2004-2011. With regard to whether there is a relationship between corporate governance and derivatives, the findings from the empirical results show that corporate governance does influence derivatives and therefore is an important determinant in the firm’s decisions to use derivatives. Of the thirteen corporate governance variables examined, board size, institutional shareholders, CEO age, CEO bonus, CEO salary, insider shareholders and total CEO compensation show significant association with derivatives. This study finds that derivative users exhibit higher firm value on account of the corporate governance influence, which is correspondingly largely insignificant for derivative non-users. Further the research indicates that the impact of corporate governance varies according to the different types of risks examined. Generally, the board of directors and CEO governance mechanisms reduce stock return volatility to achieve hedging effectiveness. This supports the view that directors and management take actions to reduce stock return volatility to protect their personal portfolios without having to bear the costs of hedging themselves. With respect to cash flow volatility, the board of directors and CEO related corporate governance mechanisms largely exhibit increased risk to show evidence of speculative behavior. It supports the perceptions that managers and directors have a strong motivation to show higher earnings to protect jobs and reputation and to enhance compensation. All the shareholder governance mechanisms encourage risk taking with respect to stock return volatility, without any increase in firm value. This is in line with research findings of market granularity by institutional and other larger block holders to indicate that these investors increase stock price volatilities and play the markets for their own financial gain. Besides they have little interest in diversifying firm risk as they already have well protected portfolios and would not want to incur additional costs of hedging. The study finds evidence of association between corporate governance and hedging, speculation and selective hedging. Of the thirteen corporate governance variables examined in the study board diversity consistently shows hedging effectiveness, with accompanying increase in firm value. While board meetings, institutional shareholders, block shareholders, CEO age, CEO base salary and CEO compensation exhibit exclusive speculative behavior. The remaining corporate governance mechanisms: board size, insider shareholding, CEO tenure, CEO bonus and audit committee size, show evidence of selective hedging behavior. The concurrent hedging and speculative behavior evidenced in this study supports literature in respect of selective hedging by non-financial firms. It also validates the idea that corporate governance delves in risk allocation strategies that have been evidenced by past research. The results remain unchanged, after using alternative measures for firm value and firm risk, and alternative methods of analyses.

Contracts as regulation model : applications and legal implications in over-the-counter financial markets - Borowicz, Maciej Konrad (European University Institute, 2016)
We develop a conceptual model of contracts as regulatory instruments in over-the-counter (OTC) financial markets. The model is informed by the functional understanding of financial regulation as addressing problems of counterparty risk, liquidity, information and systemic risk and structural understanding of regulation as a process of standard-setting, monitoring and enforcement. The justification of conceptualization contracts as regulatory instruments is found in the nature of the political economy considerations that inform the definition of certain contracts used in OTC financial markets. While many scholars rely on conceptualization of the said contracts as boilerplate, we argue that there exist important qualitative differences between boilerplate and regulatory contracts, which we link to a broader spectrum of interests taken into account in their definition in the process of standard-setting. The model and its application to loan and derivatives markets help to highlight the impact of governance features of the organization developing the contract and the regulatory competition to which the organization is exposed on the scope of the regulatory function. We also use a number of indicators and attributions to examine the effectiveness of regulatory contracts. While the contractual model displays some weaknesses in terms of both standard-setting (conflicts of interest) and enforcement (reliance on delegation) compared to its better established counterpart – the organizational model associated with exchanges – the contractual model helps to account for important self-regulatory features of OTC financial markets and offers suggestions as to how the structure of OTC financial markets can be improved.
Accepted: 2016-06-21T15:10:25Z
Keywords: Derivative securities; Financial risk management; Over-the-counter markets

The coordination of controlled foreign company legislation and international business taxation in developing economies with specific reference to South Africa - Lambrechts, Hendrik Frederik Johannes (University of Johannesburg, 2016)
This research is aimed at making out a case for the taxation of foreign source income in countries with developing economies. To this end the argument is presented that it is possible to tax foreign source income in a way that optimally coordinates the revenue entitlements of countries with developing economies, with the entitlement of multinational enterprises operating within their area of jurisdiction, to maximum profitability. It is proposed that this result may be achieved through the careful coordination of controlled foreign company (CFC) legislation and international business taxation in domestic law. To support this proposition, the following issues are addressed: a theoretical and conceptual framework for the implementation of a regime of foreign source income taxation in a country with a developing economy; an evaluation of the efficacy of the CFC legislation implemented in South Africa from which lessons in relation to the implementation of foreign source income taxation regimes in other developing countries are distilled; how the coordination of the interaction between a CFC regime, a domestic business income taxation regime, and an international business income taxation regime is effected; and an exposition of the factors that should be taken into account in the drafting of CFC legislation. To illustrate the possible real-world realisation of the coordination between CFC legislation and international business taxation in a country with a developing economy, model CFC provisions are drafted followed by an explanatory note on these provisions.
Keywords: Controlled foreign corporations; Double taxation; Foreign Corporations; International economic relations; South Africa; Taxation

A comparative reappraisal of debt relief measures for natural person debtors in South Africa - Coetzee, Hermie (University of Pretoria, 2015)
The purpose of this thesis is to do a comparative reappraisal of debt relief measures available to natural person debtors in the South African insolvency law. Although the broader South African natural person insolvency system currently includes three statutory debt relief procedures, namely, the sequestration procedure regulated by the Insolvency Act 24 of 1936, the administration order procedure in terms of the Magistrates Courts Act 32 of 1944 and the debt review procedure found in the National Credit Act 34 of 2005, not all natural person debtors have access to the system. The majority of this marginalised group are debtors with no income and no assets (the so-called No Income No Asset (NINA) debtors). Also, only one measure provides real debt relief in the form of a statutory discharge of debt. Furthermore, the existing measures have developed in a haphazard fashion which has led to a multiplicity of procedures, regulators and forums that resulted in ineffectiveness, inequality and uncertainty. The larger system therefore lacks proper policy considerations. This thesis provides the reasons for reform by, amongst others, arguing that the present situation is unconstitutional as it unreasonably and unfairly discriminates against the NINA group of debtors in particular. It measures the broader South African system against internationally accepted principles of efficient and effective natural person insolvency regimes. In this regard it is found that the system as a whole is seriously deficient. With reference to international principles and guidelines as well as suitable attributes found in foreign jurisdictions, the thesis concludes with suggestions for real law reform. Both substantive and procedural recommendations are made.
URI: https://repository.up.ac.za/handle/2263/52372

A Comparative Study on Customs Tariff Classification - Colesky, Theo (University of Pretoria, 2015)
The field of customs is commonly referred to as that of imports and exports. It is perceived as a maze of processes, procedures, and forms required to enable a customs administration to perform their wide range of responsibilities. One of the responsibilities of a customs administration is the collection of duties, which necessitates classification of the goods in question. This study sets out to determine the extent of customs control in relation to tariff classification in South Africa. The starting point is the establishment of the foundations of customs, both internationally and in South Africa. After origin and valuation, tariff classification is the third technical customs-related focus area. An analysis of the responsibilities of the customs administration in South Africa confirms the importance of revenue collection and, subsequently, tariff classification. As a result of South Africa’s membership of the World Customs Organization, specific obligations in relation to tariff classification are incurred. The implementation and application of the international provisions are considered and compared in South Africa, Australia, and Canada. Not only is South Africa’s existing legislation considered, but also two new Acts. It is found that despite similarities in the implementation of the Harmonized System Convention into the legislation of the three countries, South Africa’s existing legislation makes the most detailed provision for the Harmonized System and its aids. This is based on the finding that the legislation in Australia and Canada, as well as the two new Acts in South Africa, do not have the same comprehensive provisions. A critical review of the varying processes of classification in the three countries suggests that more suitable and effective processes could be implemented in South Africa. In addition, a synopsis of some of the principles developed in case law is provided and compared. In relation to facilitation, the access to relevant information and the adequacy thereof, as well as the availability of rulings, are considered. Differences in the approach to dispute resolution in the three countries are furthermore provided. Proposals are made to address the discrepancies in the implementation and application of the legislation, the process of classification, the principles developed in case law, the enhancement of related guides, the publication of tariff classification rulings, and the extent of facilitation and dispute resolution. Finally it is recommended that an independent and expert tribunal is established to adjudicate technical customs matters.
URI: https://repository.up.ac.za/handle/2263/42838
Keywords: Comparative study; Customs tariff classification

The Disclosure and Use of Social and Environmental Information by Libyan Banks - Elsakit, Omer M (Griffith University, 2015)
There is increasing interest in social and environmental issues throughout the world, especially in developed countries, where governments, organizations, and society well recognise the impact of business activities on the environment and society. Consequently, companies have potentially no alternative but to behave in a responsible manner, socially and environmentally, and to prove this by disclosing information about their related conduct. In this regard, banks play two important roles: first, as providers of social and environmental information in much the same manner as nonfinancial companies; and second, as providers of finance, by encouraging—if not obliging—bank customers to consider society and the environment in their bank-financed projects. Banks fulfil the latter role by requiring social and environmental information from companies when making lending decisions. Only a few Libyan studies have examined social and environmental issues in relation to economic activity, and these have generally revealed low levels of disclosure practice by organisations, including banks, in these areas. In addition, many changes have taken place in the Libyan economy and banking sector in recent years, including the establishment of a market exchange; decreased government participation in economic activities; and increased growth of the private sector that results, especially in the banking sector, with the entrance of foreign investors. These changes have placed a new emphasis on bank operations and the participation of banks in the Libyan economy. Thus, studying Libyan banks, in terms of their role in the environment and society, has attracted growing interest. As such, the core objective of this thesis has been to investigate the position of Libyan banks in relation to social and environmental issues and disclosure by considering their dual role as both providers and users of such information.
Keywords: Banks and banking; Environmental policy; Finance and environment; Libya

International taxation of cross-border digital commerce - Kadikov, Artem (University of Oxford, 2015)
This thesis discusses jurisdiction to tax cross-border digital commerce. The primary objective is to consider the reasons for the erosion of jurisdictional links, or nexus, between countries and taxpayers' digital activities and evaluate possible solutions for addressing such nexus erosion. Whilst it is argued that digital commerce is impossible to ring-fence due to digital technologies transcending all industries, the main focus of this research is on automated business models as case studies for the broader tax issues applicable across the entire digital economy. Using cloud computing, online advertising and e-tailing models as examples of digital commerce in the narrow sense, this thesis demonstrates that the proxies for establishing jurisdictional nexus have become increasingly fluid, thereby challenging the traditional international tax regimes for profits and consumption taxation. Numerous policy solutions have been proposed in order to rectify nexus erosion, including global and territorial tax models. Unlike the previous research in this area, this thesis focuses on the nexus elements of such proposals and assesses their viability in the light of the wider Internet governance jurisprudence. Global tax solutions, such as global e-commerce taxes and formulary apportionment, are analysed in the context of the international governance regime for the technical Internet infrastructure. Territorial virtual tax solutions, such as virtual permanent establishments, withholding taxes and destination cash flow taxes, are considered in the light of the Internet jurisprudence on the 'effects' and 'targeting' nexus standards. It is argued that, given the lack of technical and political infrastructure, none of the proposed routes would be viable from a practical perspective in the near future. It is concluded, therefore, that a practical solution would involve retaining the traditional profits and consumption tax models, whilst testing a narrow version of the digital targeting nexus standard as a backstop anti-abuse measure. It is envisaged that the limited anti-avoidance provision would subsequently pave the way for a comprehensive long-term solution, as digitisation continues to transform global commerce.
Keywords: Corporations; Digital commerce taxation; Double taxation; E-commerce taxation; Electronic commerce; International Trade; International business enterprises; Internet governance; Internet jurisdiction; Internet taxation; Jurisdiction to tax; Taxation

Establishing continental sovereignty in Africa: risk and opportunity in financial integration - lessons for Africa from a legal perspective - Ngwafor Ndeh, Edwin (University of Glasgow, 2015)
This thesis identifies and defines the new African sovereignty. It establishes a modern sovereignty in Africa hatched from the changing nature of sovereignty in which countries come together at various levels or grades of partial surrender of national sovereignty in order to work closer together for their mutual advantage and benefit. To this end, the narrative zooms in on the central issues within the realms of money matters whereby a new model of monetary sovereignty and monetary solutions is designed in an attempt to ease the recurring tensions and challenges of modern national sovereignty in the continent of Africa. As such, this discussion will offer a historical journey through the constitution of sovereignty, to the birth of the nation state and international public law. It develops the theory of the changing nature of sovereignty within the modern state and opens new lines of inquiry for Africa. In this regard, it draws from juxtaposing and mixing elements of regional and global financial integration as well as retaining national financial sovereignty features to form this new design which I dub continental sovereignty. At its core, the thesis will deal with the legal aspects that stem from the co-mingling of legal systems of nation states and communities at the regional and global levels within the context of financial integration. The argument is that the rule of law remains sacrosanct in monetary management. Effective financial integration is the result of properly structured and managed legal frameworks with robust laws and institutions whether at a national, regional or global level. However, the thesis reveals that in order to avoid undermining the progress of Africa’s financial integration project, any solution for Africa must be immersed within a broader global solution where development issues are addressed and resolved and Africa can form a more central part in all relevant international discussion fora. The work will expound these issues by applying them within a regional and global context, with the state of affairs in Africa forming the nucleus. This application consequently presents the six key themes of the thesis which will be considered therein. They are: a.) regional advantage: which exploits the possibilities of deeper and further financial integration between smaller communal arrangements; b.) regional risk and exposure: the extent to which this deeper form of financial integration can spiral out of control if effected too quickly and too ambitiously; c.) global advantage: which considers the merits of global financial integration and the influence exerted by financial laws on the global financial architecture; d.) global risk and exposure: which considers the challenges of global financial integration especially within the background of the Global Financial Crisis 2007-2008; e.) African challenge: which considers the extent to which this analysis impacts the African economic and financial integration agenda; and f.) development challenge: which examines the extent to which global development issues impact the African solution (continental sovereignty) and the need for any solution for the continent to be roped into a broader global solution within which Africa can form an important part. Even though the thesis requests an optimistic undertone on the progress made so far, it unearths the African problem of multiple national sovereignty and multiple overlapping regional sovereignty constituted as the ‘spaghetti bowl’ dilemma. As such, the unique contribution to knowledge on financial integration in Africa can be echoed in these words: Africa‘s financial integration agenda has had little success in authenticating a systematic and dependable legal framework for monetary management. Efforts made have been incomplete, substandard, and not carefully followed through particularly reflected in the impuissant nature of the judicial enforcement mechanisms. Thus, the thesis argues that, any meaningful answer to the problems dogging the continent is inter alia deeply entrenched within a new form of cooperative monetary sovereignty. In other words, the thesis does not prescribe the creation of new laws; rather it advocates the effective enforcement of existing laws.
Keywords: African Integration Project; Crisis response; Financial crisis; Financial integration; Regional systems; Regulation of financial markets; continental sovereignty

Internal Audit Characteristics and Quality of Accounting Information in Nigeria - Ogundana, Oyebisi Mary; Ojeka, Stephen; Ojua, Michael; Nwaze, Chukwu (Conference Proceedings, 2015)
The basic goal of Accounting is to provide enabling accounting information for reliable decision-making. The quality level of this accounting information comes from the company's governance practices, thereby emphasizing the importance of corporate governance in companies. Recently, following the financial crises resulting in accounting scandals, attention has been moving towards Internal Audit Function as an important factor in the structure of Corporate Governance. This paper therefore examined the extent of the relationship between internal audit function and the quality of accounting information of companies. The study adopted the Survey research design. The research instrument employed was Questionnaire which was administered to internal auditors of the “Big Four”. Linear regression analysis was employed in the analysis of the data collected with the use of Statistical Packages for Social Sciences (SPSS). The results revealed that there is a significant relationship between the internal audit characteristics and the quality of accounting information. It was recommended that in order to provide credibility to the financial statement, there should be a law in place mandating attachment of internal auditors report to the financial statement
Keywords: Accounting quality; Accounting report; Corporate governance; Fraud; internal auditing

Synthetic securitisation in South African law - Wessels, Francois Claassens (University of Pretoria, 2015)
The objective of this thesis is to critically analyse synthetic securitisation schemes in South African law as synthetic collateralised debt obligations using primarily credit default swaps (CDSs). This transpires from the perspective of primarily company law, and secondarily securities law and the law of contract. It includes a contextualised study of these schemes with regards to their origins, their significance regarding the recent financial crisis, and their rationales micro-economic influence and Basel capital requirements. Not only are the participants, such as parties acting in a primary role and secondary role and special-purpose institutions, studied, but also the obligations between these parties, such as the CDS contract, and the meaning of commercial paper, the legal nature of credit-linked notes, the business of a bank, and the influence of recent case law. It also includes a consideration of synthetic securitisation schemes in terms of the Collective Investment Schemes Control Act 45 of 2002. Furthermore, the role of systemic risk and moral hazard is explained, as well as the interaction between synthetic securitisation schemes, credit rating agencies and the function of risk management. The CDS is compared with insurance contracts, and a discussion of the 2014 International Swaps and Derivatives Association Credit Derivative Definitions is incorporated. For legal comparison, the South African model is compared with Canadian law and its unfunded credit derivatives in the light of recent regulation, and compared to German law and its prevalence of funded credit derivatives. Finally, suggestions are made as to the future of synthetic securitisation schemes.
URI: https://repository.up.ac.za/handle/2263/53208
Keywords: Company law; Debt obligation; Securities Law; Securitisation; South Africa; Titrisation

A South African perspective on some critical issues regarding the OECD model tax convention on income and on capital, with special emphasis on its application to trusts - Du Plessis, Izelle (Stellenbosch University, 2014)
Trusts are used for a variety of purposes, both in South Africa and abroad. Like so many other entities, trusts often do not function only in one jurisdiction and may therefore be exposed to international double taxation. South Africa, like most other states, enters into bi-lateral double taxation treaties, to limit the effects of international double taxation. Most of these treaties are based on the OECD Model Tax Convention on Income and on Capital (the OECD MTC). The South African trust is a unique creature. It is not based on the dual ownership concept on which most common law trusts are based, yet, it is not a juristic person either. The question that this research aims to address is how South Africa will interpret and apply certain provisions of the OECD MTC to trusts. Although the South African position is investigated, it is compared to the positions of the United Kingdom, Canada and the Netherlands. The dissertation starts with an analysis of the trust law in each of the relevant states, followed by an overview of the taxation regime governing trusts (and the parties thereto) in each state. The status of double taxation treaties and their interpretation are examined before certain critical provisions of the OECD MTC are analysed to determine how South Africa will apply these provisions to trusts. Hence it is explored whether a trust will be regarded as a person, whether it may be a resident and a beneficial owner for purposes of the OECD MTC. Furthermore, possible solutions for conflicts of attribution in the application of double tax conventions to trusts are investigated. The dissertation concludes that South Africa will regard a trust as a person for purposes of the OECD MTC. Moreover, some types of trusts may be viewed as residents and as beneficial owners for purposes of the OECD MTC. The solution proposed in the OECD’s Partnership Report should be applied to resolve conflicts of attribution involving trusts.
URI: http://hdl.handle.net/10019.1/95878
Keywords: Double taxation; Income tax; International taxation; OECD Model Tax Convention; South Africa; Taxation; Treaties; Trusts and trustees

Cross-border resolution of banking groups: old demons, current progress, future challenges - Pnevmonidis, Ilias (Université de Genève, 2014)
This contribution focuses on the development of bank resolution regimes as a credible antidote to the ‘too big to fail' problem. The main objective of the analysis is to demonstrate the repercussions and challenges resulting from the implementation of bank resolution schemes on a cross-border level. This work is a selective survey of specific legal questions, which remain relatively unaddressed by academic literature and international standard-setting bodies (e.g. bank resolution triggers or safeguards for bank creditors under bank resolution) or still problematic (e.g. resolution planning or cooperation and information exchange between resolution authorities), in particular when applied in a cross-border context. The author aims to shed more light to the complexities of cross-border bank resolution while trying to answer to the fundamental question: have we ended the ‘too big to fail' problem?
Keywords: Bank-failures; Bank-insolvency; Bank-resolution; Financial-crisis; Insolvency; Systemic-risk; Too-big-to-fail

Bringing Formal Business Laws to Cameroon’s Informal Sector: Lessons and Cautions from the Tax Law Example - Dickerson, Claire Moore (Washington University Global Studies Law Review, 2014)
A substantial majority of non-agricultural workers in a developing country such as Cameroon engage in legal businesses below the governmental radar, that is, in the informal sector. Because that segment of the Sub-Saharan economy is critical to subsistence within the region, and because the financial crisis has expanded the informal sector in the Global North, developing economies’ experience with the informal sector is of world-wide relevance. Formal business laws do exist in the formal sector; however, trying to move informal-sector workers to the formal sector where these laws already offer some protection can disrupt the entrepreneurs’ ability to sustain themselves, and to contribute to the national economy. A pilot study in five Cameroonian markets is thus of general interest when it reveals that entrepreneurs there do not benefit from formal business laws, which in turn limits their ability to borrow and their willingness to lend. The same study also suggests that tax literature has interesting, non-coercive strategies to improve tax compliance in ways that may be applicable to facilitating the introduction of formal business laws to the informal sector, instead of forcing informal-sector workers into the formal sector. The tax-morale literature recommends deploying strategies of reciprocity, in addition to providing public goods and services—strategies that encourage compliance—instead of using governmental power to extract tax payments. Similarly, tax-based strategies can apply to business laws while informal-sector workers remain in the informal sector, even though the government’s posture vis-à-vis commercial actors is less direct than vis-à-vis taxpayers. The experience of Cameroon’s informal sector with formal tax law thus provides important insights on steps within the government’s control that would not only improve tax compliance, but would also bring formal business laws and their transaction-cost-reducing potential to the informal sector. The pro-business strategy is to apply tax-morale learning, which calls for government authorities to enter into a reciprocal relationship— respectful and communicative—with private parties and to focus on investing in basic infrastructure.

An evaluation of the predictive value of bank fair values - Ehalaiye, Oludimu Oluseun (Victoria University of Wellington, 2014)
This thesis examines whether the net asset fair values of banks possess predictive ability for the banks’ future cash flows and earnings. This is an important issue considering the arguments for and against the wider use of fair value accounting for banks’ financial instruments and the claim by some that fair values during economic recessions (where markets may be illiquid) are irrelevant and largely unreliable. A number of studies have found that the explanatory power of bank fair values when compared to traditional historical cost are more value-relevant based on capital market reactions. However, there is a very limited literature on how bank fair values are related to the future performance (e.g. earnings and cash flow) of banks. This study fills this gap by providing empirical evidence on the relationship between U.S. bank fair value disclosures and banks’ future performance as measured by operating cash flows and earnings over a three-period future horizon. Furthermore, the thesis provides evidence on the relationship between bank fair values, in terms of the levels classification introduced during the 2008 global financial crisis, and the future performance of banks, thus showing whether market illiquidity affected the underlying relationships. The study examines two distinct periods. The first study period, 1996-2005, was based on annual data of banks with minimum total assets of $US150 million as of year 1996. The second study period from 2008-2010 (this period encompassed the global financial crisis period and also the levels classification of bank fair values according to SFAS 157), was based on quarterly data of banks with minimum total assets of $US150 million as of the first quarter of 2008. The thesis provides strong evidence that there is a predictive relationship between bank fair values and future bank performance. The evidence is strong during the first study period from 1996 to 2005 where the current net asset fair values of on-balance sheet financial instruments of banks were significantly associated with future operating cash flows and operating earnings of such banks over a three-year future time horizon. However, the predictive relationship between net asset bank fair values and operating cash flows is stronger than the predictive relationship between net asset bank fair values and operating earnings. In the second study period, from 2008 until 2010 the empirical results show strong evidence that there is a predictive relationship between level 1 and level 2 bank fair values and future operating cash flows. The findings from the empirical results were that the current quarter’s level 1 and level 2 net asset fair values of banks were significantly associated with the future quarters’ operating cash flows of such banks. The level 3 net asset fair values of such banks in most cases were not significantly associated with the banks’ future quarterly operating cash flows. The corresponding relationships for operating earnings were that the current quarter’s level 1 net asset fair values of banks were positively associated with the future quarters’ operating earnings of such banks. However, the level 2 net asset fair values of banks were negatively associated with the future quarters’ earnings of such banks. This result is in contrast to the results obtained when the predictive relationship between level 2 bank fair values and future operating cash flows was evaluated, where it is found that both level 1 and level 2 net asset bank fair values are positively related to future quarterly bank cash flows. Further empirical analysis showed that a possible reason behind this disparity was that there was a structural change in the relationship between bank operating cash flows and operating earnings over the course of the first and second study periods, where, in particular, for the second study period (which includes the period of the global financial crisis) there was a systematic downward bias in operating earnings relative to the operating cash flows of the sampled banks. This in turn makes operating earnings a poor proxy for operating cash flows during the second study period. The findings from this study provide confirmation that net asset fair values have predictive ability as argued by Ball (2008); Barth (2006b) and Tweedie (2008). The study findings that net asset fair values have predictive ability is consistent with the FASB’s view that the asset values shown in firm financial statements should communicate information about the potential future financial performance of the affected firms (FASB 2010:17). Furthermore, the study also confirms that objectively determined bank fair values based on market prices rather than model based bank fair values provide greater predictive value in relation to future performance as measured by operating cash flows. Lastly, this thesis showed that during the first study period (where there was no financial crisis) that bank size, capital adequacy and growth prospects, had little impact on the results obtained, while for the second study period, there were cases where bank size and bank capital ratios did have a significant impact on the predictive relationship between bank fair values and future cash flows. The study contributes to the fair value accounting and accounting standard-setting literature and highlights that fair values have predictive ability, especially with respect to future operating cash flows of banks, both during and outside of periods of financial crisis.
Keywords: Economic forecasting; Fair value; Predictive value

A macro-financial theory of corporate financing and forecast modelling of market movements - Sutton, David (Victoria University of Wellington, 2014)
This thesis identifies a gap in existing theories of corporate finance. This gap is an implication of a Keynesian-Minskian analysis of markets and market-based economies. From a founding theoretical perspective rooted in the view that markets are not reliably efficient the case is developed that past price trend extrapolation is an important factor in corporate financing decisions. At a macro-financial level, companies repurchase equity over periods of strong market rises, while increasing debt at the same time. During periods of sustained, substantial market decline debt is retired and large new equity issues occur. This change in corporate financing is implicitly expensive as relatively low prices are realised for the new stock issued at these times. These factors suggest that conventional theories of corporate financing decisions that rely on corporate rationality and optimisation do not provide a compelling fit with observations in the period 1980-2012. Moreover, inference to Minsky’s (1986) argument that companies are compelled through market declines to shore up their balance sheets provides a better fit with the evidence. These arguments form the basis for the development of the ‘extrapolative expectations’ theory of corporate finance. The second major development in this thesis draws on the theoretical development outlined above to create market movement description and prediction models. These models operate on data drawn from the US Standard & Poors 500 index over the period 1980-2012. Two primary models are developed using binomial logistic regressions. The dichotomous dependent variables are drawn as quarters of market rise (1) or no rise (0), and market falls (1) or no fall (0), respectively for the ‘buy’ model and the ‘sell’ model. Variables tested and those found to add to an explanation of the dependent variables include: corporate debt flows, corporate equity flows, corporate dividend flows, interest rates, market volumes, and historical market levels. Each variable is tested for up to ten lags (two-and-a-half years). Collectively, the variables add to our understanding of those factors influencing (or at the least, signalling) market levels, enabling quarter ahead market forecasts to be made with greater accuracy than arises from an assumption of a random walk. This conclusion crystallises the view that company macro-financial flows and prices are an important cause or signal of future market direction.
Keywords: Corporate financing; Financial Accounting; International Accounting; Macro-financial; Minsky

The collection of value added tax on online cross-border trade in digital goods - Van Zyl, Stephanus Phillipus (University of South Africa, 2013)
Technological advances have had a major impact on traditional retail shopping changing it from a physical undertaking to a completely digitised experience where consumers buy digital media online. VAT systems that do not specifically provide for, or which have not been adapted to cope with, technology-driven advances, generally do not provide for the adequate levying and collection of VAT on cross-border digital trade. The South African VAT system is no different. The taxation of e-commerce should not artificially advantage or disadvantage e-commerce over comparable traditional commerce, or unnecessarily hinder the development of e-commerce. This thesis determines whether the South African VAT Act 89 of 1991 in its current form, can be applied adequately to raise and collect VAT on cross-border digital transactions. Where shortcomings in the VAT Act are identified, the harmonised VAT rules of the European Union (EU), together with the Organisation for Economic Cooperation and Development (OECD) proposals on consumption taxes, are analysed and discussed to seek possible solutions and make recommendations.
Keywords: Anonymising technology; B2B transactions; B2C transactions; BIT-rate tax; Banker-customer confidentiality; Blocked VAT account; Consumption taxes; Cross-border digital trade; Electronic commerce; Electronically supplied services; European Union; European Union countries; Fractionated VAT; OECD; South Africa; Taxation; VAT collection model; Value-added tax

Bridging the GAAP? : IFRS in accounting practice - Hartmann, Berit (Jönköping International Business School, 2013)
This thesis investigates how International Financial Reporting Standards (IFRS) come to act within an organizational context. In particular, the thesis explores how the requirements for goodwill accounting and leasing influence organizational calculative practices, transforming and shaping operations management. Drawing on actor-network theory, this study moves away from a priori distinctions, following the construction and mobilization of accounting numbers across institutionalized boundaries within and around the organization. The empirical investigation took place in a large, worldwide active media group that is listed on a European stock exchange. The group is a particular interesting setting because of its diverse business structure and its German code-law accounting roots. Business combinations are a major growth factor within the industry and a high degree of decentralization in the organization placed responsibility for investment decisions at low hierarchical levels. Goodwill accounting and impairment testing were therefore highly significant calculative practices in the group. The study finds that the constitutive role of the financial reporting standards in the organization both solves tensions and dilemmas around the number and creates new ones when crucial interests are lost in translation. These tensions and dilemmas arise between the aim of standardization and closure for the construction of a legitimate value of the future, and the aim to mobilize numbers in order to motivate and create value for a future. Originally intended for the financial representation of organizational substance and performance, the standards become associated with operations management activities, helping to create the faithful records that sum up the organization. This interrelation helps to close concern around the representation of the future in a ‘fair’ value by distributing the calculative practices over a wide network of actors spanning inside and outside the organization. However, the relationship also forces a connection between calculations and ambitions that otherwise would have preferred to stay separate. This thesis offers a new perspective on IFRS implementation by emphasizing organizational activities. Through a focus on integration and the link between financial and management accounting, the ‘implementation problems’ highlighted in previous literature gain a refined theorization. When taking organizational practice seriously, integration becomes a process that may find temporal stability but will never be final. In the process, conflicts might be solved but new dilemmas will arise. In turn, concepts like decision usefulness, comparability and earnings management cannot exist in a stable form but are rather constructed in networks that disregard commonly assumed boundaries inside and around the organization.
JIBS Dissertation Series, ISSN 1403-0470 ; 094 URN: urn:nbn:se:hj:diva-23148 OAI: oai:DiVA.org:hj-23148 DiVA, id: diva2:689238
Keywords: IFRS; International Financial Reporting Standards

A Comparative Analysis of the Efficacy of the General Anti-Avoidance Rule as a Measure Against Impermissible Income Tax Avoidance in South Africa - Kujinga, Benjamin Tanyaradwa (University of Pretoria, 2013)
This thesis comparatively analyses the SA income tax general anti-avoidance rule (GAAR) in s 80A-L of the Income Tax Act 58/1962 and similar rules in Australia, Canada, the UK and the judicial doctrines in the US and the UK. It is argued that, while the SA GAAR may serve as a deterrent, it is going to have limited efficacy against impermissible tax avoidance due to the uncertainty it creates. It is argued that uncertainty will cause judicial activism to protect permissible tax avoidance, extensive and inconsistent judicial interpretation and confusion amongst taxpayers and SARS as to what constitutes permissible or impermissible tax avoidance. This thesis ends by recommending certain amendments, based on the comparative analysis, to the SA GAAR which can reduce uncertainty and thus improve it efficacy.
URI : https://repository.up.ac.za/handle/2263/33430
Keywords: General Anti-Avoidance Rule; Income tax; South Africa

Direct taxation and the internal market: assessing possibilities for a more balanced integration - Yevgenyeva, Anzhela (University of Oxford, 2013)
The role of the Court of Justice of the European Union in the process of direct tax integration in the European Union (EU) has been widely discussed in the academic literature, while another important actor, the European Commission, has attracted much less attention. The Commission’s input is commonly perceived to be limited to the right of legislative initiative. This study questions such an oversimplified interpretation and draws a more nuanced picture of EU tax harmonisation by integrating an analysis of the complex regulatory approaches adopted by the Commission for the establishment and smooth functioning of the Internal Market. It is argued that the past decade brought a notable change in the Court-dominated pattern of direct tax integration. This change is apparent first in the evolution of enforcement strategies under Articles 258 and 260 TFEU; and second, in the increased reliance upon non-binding regulatory measures. Both developments have strengthened the role of the Commission, supplying it with more possibilities for influencing national direct tax systems, despite the reluctance of Member States to agree upon legislative harmonisation. Against this background, the procedural and substantive problems associated with these instruments require closer examination. The normative scope of this research covers the key procedural problems related to the infringement procedure and non-binding regulatory measures. The empirical component explores the Commission’s enforcement and coordination practices, drawing particular attention to two case studies: the tax treatment of losses in cross-border situations and exit taxation. Following the analysis of enforcement and coordination in the field of direct taxation, the study argues the need and proposes potential solutions for (i) the developing of a more comprehensive procedural framework for the infringement procedure and non-binding regulatory acts; (ii) the strengthening of accountability mechanisms; and (iii) the enhancing of the effectiveness of their application.
Keywords: Direct taxation; EU Law; Enforcement; European Law; Exit tax; Good governance; Infringement procedure; Internal Market; Non-binding coordination; Soft law; Tax coordination; Tax integration; Tax treatment of losses; Taxation

Financial liberalisation and economic growth in ECOWAS countries - Owusu, Erasmus Larbi (University of South Africa, 2012)
The thesis examines the comprehensive relationship between all aspects of financial liberalisation and economic growth in three countries from the Economic Community of West African States (ECOWAS). Employing ARDL bounds test approach and real GDP per capita as growth indicator; the thesis finds support in favour of the McKinnon-Shaw hypothesis but also finds that the increases in the subsequent savings and investments have not been transmitted into economic growth in two of the studied countries. Moreover, the thesis also finds that stock market developments have negligible or negative impact on economic growth in two of the selected countries. The thesis concludes that in most cases, it is not financial liberalisation polices that affect economic growth in the selected ECOWAS countries, but rather increase in the productivity of labour, increase in the credit to the private sector, increase in foreign direct investments, increase in the capital stock and increase in government expenditure contrary to expectations. Interestingly, the thesis also finds that export has only negative effect on economic growth in all the selected ECOWAS countries. The thesis therefore, recommends that long-term export diversification programmes be implemented in the ECOWAS regions whilst further investigation is carried on the issue.
Keywords: ARDL-Bounds testing approach; Capital accounts liberalisation; Co-integration; ECOWAS; Economic Community of West African States; Economic growth; Economic stablization; Financial crises; Financial liberalisation; Ghana; Interest rates liberalisation; Ivory Coast; Monetary Policy; Nigeria; Stock market developments

Effectiveness of the Beneficial Ownership Test in Conduit Company Cases - Jain, Saurabh (Victoria University of Wellington, 2012)
Countries enter into double tax agreements with the economic objective of preventing double taxation of cross-border transactions. To achieve this objective, the contracting states agree reciprocally to restrict their substantive tax law. That is, a major policy of double tax agreements is to reduce double taxation of residents of states that are parties to the agreement. Residents of third states sometimes contrive to obtain treaty benefits typically by interposing a person or a conduit entity in one of the contracting states. In order to ensure that a resident of a contracting state who claims treaty benefits is entitled to them in substance, double tax agreements should be interpreted according to their substantive economic effect. Generally, double tax agreements follow the pattern of the OECD Model Tax Convention. The OECD Model Convention addresses the double taxation of dividends, interest and royalties, commonly collectively known as "passive income", in Articles 10, 11 and 12 respectively. These provisions usually operate by reducing withholding tax imposed by a source state on passive income that flows from the source state to a resident state. In order to prevent a resident of a third state from obtaining a source state withholding tax reduction by interposing a person or a conduit entity in the resident state, the OECD Model Convention requires the immediate recipient of passive income to be the "beneficial owner" of that income. That is, the OECD Model Convention requires the immediate recipient to be an owner in a substantive economic sense. Courts and commentators have difficulty in interpreting and applying the concept of beneficial ownership to conduit entities that are corporations, commonly referred to as "conduit companies". They have attributed the cause of the difficulty to the absence of a definition of the term "beneficial owner" in the OECD Model Convention. This thesis argues that the difficulty in applying the beneficial ownership concept to conduit companies has arisen not because of the absence of the meaning of the concept, but because logically and from an economic perspective the concept cannot be applied to companies in general, not to conduit companies in particular. The beneficial ownership test was meant to be a test of economic substance. From an economic perspective, the benefit or the burden of a contract entered by a company is economically enjoyed or borne by its shareholders. That is, in substance a company cannot be considered as owning income beneficially. From this consideration, it follows that conduit companies can never be considered entitled to treaty benefits. Nevertheless, the OECD Model Convention applies the beneficial ownership test to conduit companies pursuant to an assumption that at least in some cases conduit companies can be the beneficial owners of passive income. The Model Convention's assumption is based on the legal perspective that courts conventionally adopt. According to this legal perspective, companies hold income beneficially because they exist as separate legal entities from their shareholders. Courts find themselves battling these opposing perspectives when applying the beneficial ownership test to conduit companies. In order to make income tax law work efficiently, courts that are obliged to determine whether to honour claims to treaty benefits made by conduit companies have preferred to employ the legal perspective. Courts have justified this approach by adopting surrogate tests for the actual beneficial ownership test. Most of the surrogate tests do not relate to the concept of ownership at all. This thesis categorises the surrogate tests as "substantive business activity" and "dominion". By analysing reported cases, the thesis identifies deficiencies in these tests. One of the proposed outcomes of the thesis is to suggest an alternative approach for deciding conduit company cases. The thesis suggests that courts should consider an arrangement as a whole and investigate reasons for the existence of an immediate recipient of passive income in the specific corporate structure. The thesis also recommends amendments in the official commentary on Articles 10, 11 and 12 of the OECD Model convention in order to address the conceptual shortcomings inherent in those Articles.
Keywords: Double taxation; OECD Model Tax Convention; Tax law

Essays in corporate restructuring, reputation and law - Polo, Andrea (Oxford University, 2012)
This dissertation consists of three essays which examine topics at the intersection of law and finance. The first essay investigates the role of regulatory sanctions and reputational damage in financial markets. We study the impact of the announcement of enforcement of financial and securities regulation by the UK’s financial regulators on the market price of penalized firms. We find that reputational sanctions are very real: their stock price impact is on average almost 9 times larger than the financial penalties imposed. Furthermore, reputational losses are confined to misconduct that directly affects parties who trade with the firm (such as customers and investors). In the second essay we analyze the costs and benefits associated with secured creditor control in bankruptcy. We do it by studying the highly contested practice of UK pre-packs, where a deal to sell the business is agreed before publicly entering into bankruptcy. Contrary to widespread criticism that this procedure leads to collusion, we find no evidence of exploitation of conflict of interests and we find that it preserves the value of the business and maximizes recovery in circumstances in which a public announcement of bankruptcy would destroy value. In small businesses where secured creditors are concentrated the benefits of their control seem to outweigh the costs. Finally, in the last essay we examine whether mandatory shareholder voting prevents wealth destruction in corporate acquisitions. We study the UK setting where all large transactions must have shareholder approval. We observe that such Class 1 transactions always get consent. Nevertheless, there is a striking difference between the performance of acquirers between Class 1 and other transactions. The finding is most pronounced for transactions in a narrow neighbourhood of the size threshold, and is robust to a large set of controls for confounding effects.

Understanding fiduciary duties: conflict of interest and proper exercise of judgment in private law - Valsan, Remus (McGill University, 2012)
This dissertation analyses the content and justification of the notion of fiduciary duties in private law relations. The thesis promotes the following understanding of fiduciary duties: in a legal relation where one party undertakes to act in the interests of another, and acquires decision-making authority over the other's interests, such party undertakes a core duty to exercise his best judgement in the other's interests. The core judgement duty requires a fiduciary to exercise judgement based on relevant considerations. While what constitutes a relevant consideration can be determined objectively, the weight to be ascribed to each relevant factor is left at the fiduciary's subjective appreciation.Due to the existence of this core duty, the law imposes a set of proscriptive duties. The proscriptive duties require a fiduciary to manage situations of conflict of interest. Their purpose is prophylactic: they aim to prevent self-interest (or another duty to exercise proper judgement) from affecting the reliability of fiduciary's judgement in a conscious or subconscious way. The proscriptive duties protect the core duty to exercise judgement and, as a result, the beneficiary's right to a proper exercise of judgement by the fiduciary.
https://escholarship.mcgill.ca/concern/theses/wd376141g
Keywords: Conflict of interest; Fiduciary duties; Judgment; Private law

Corporate Governance and the Relationship between Default Risk and the Earning Response Coefficient - Zakaria, Nor Balkish (Victoria University of Wellington, 2012)
This study examines the effect of corporate governance on the relationship between default risk and the earnings response coefficient (ERC). Using a sample of 2,004 firm-years comprising 334 firms listed on the Bursa Malaysia over a six year period from 2002 to 2007, this study tests whether corporate governance mitigates the effect of default risk on ERC while controlling for the established determinants of ERC — beta, growth, earnings persistence and size. Using reverse regression, the study confirms that beta is negatively related to ERC and that growth, earnings persistence and size are positively related to ERC. Default risk is found to be negatively related to ERC thus confirming that beta is only a partial measure of risk relevant to ERC. Corporate governance — as indicated by audit quality, audit committee expertise and independence, and board independence and board shareholding — mitigates the negative effect of default risk on ERC. The results of the study hold both for the pooled sample of 2,004 firm-year observations and on a year by year basis for the 334 firms in the sample. The results are also found to be robust to various sensitivity tests including to alternative measures of the variables. The study thus provides systematic and comprehensive additional evidence on the determinants of ERC. Of itself this is an important contribution to the literature but especially so given that the evidence comes from Malaysia — an emerging economy — whereas the existing empirical literature relates mainly to developed countries.
Keywords: Corporate governance; Default risk; Earnings response coefficient

Reformulating corporate residence: a coherent response to international tax avoidance - Loomer, Geoffrey (University of Oxford, 2011)
This thesis analyzes the concept of corporate residence, with particular reference to the law in the UK and Canada. It explores why corporate residence is relevant in tax policy, how corporate residence is understood in law, and how revenue authorities respond to the use and alleged 'abuse' of residence rules. Part I argues that the residence of taxpayers generally (individual or corporate) remains a relevant factor in international tax design, that taxation of corporations on the basis of residence has some justification, but that there is a disjunction between meaningful residence-based taxation and current definitions of corporate residence in domestic law and tax treaties. The formulations of residence based on incorporation, central management and control, and place of effective management, particularly as applied to multinational enterprises, are considered and are found to be deficient. Part II critically analyzes the major policy responses of the UK and Canadian governments to the exploitation of corporate residence. It argues that key legislative and administrative responses to international tax avoidance activities, for both outbound and inbound investment, are purportedly based on the acceptance of formal corporate residence yet undermine that concept in an effort to impose tax or refuse treaty relief based on where economic interests actually exist. The responses considered are the application of controlled foreign companies legislation to offshore subsidiaries, the invocation of treaty anti-abuse rules with respect to offshore intermediaries, and the use of overarching general anti-avoidance measures to challenge varied structures that rely on offshore entities. These haphazard anti-avoidance rules are overlaid with revenue authorities' indignation at the motivations that underlie many corporate relocations. It is argued that a more coherent approach would be to focus on the objective reality or unreality of corporate establishment, by reformulating corporate residence in domestic law and tax treaties.
Keywords: Economics Law; International business; International taxation; Multinational enterprises; Resident companies; Tax avoidance; Tax planning; Taxation

National legislative systems and foreign standards and regulations: The case of International Financial Reporting Standards adoption - Dima, Bogdan; Dima (Cristea), Stefana Maria; Moldovan, Nicoleta; Pirtea, Marilen Gabriel (MPRA Paper, 2010)
This study is focused on the linkages between the legislative families as descriptors of national legislative systems and International Financial Reporting Standards (IFRSs) issued by the International Accounting Standards Board (IASB). We consider such analysis as a case study for the more general issue of explaining the preferences of national regulators in the adoption of foreign norms, rules, standards and practices. By using a dataset of 162 jurisdictions and dummy variables designed to capture the current stage of IFRSs adoption and, respectively, the taxonomy of their legislative systems, we find that a full IFRSs adoption is more likely to occur in countries which have principles-based on legislative mono-systems. In addition, we observe that a strong rule of law, with an effective mechanism of property rights reinforcement, as well as the pre-adoption existence of a pro-growth set of public policies can contribute to the encouragement of IFRSs adoption.
Keywords: IFRSs adoption; Legislative families

The suitability of the South African corporate tax regime for the use of South African resident intermediary holding companies - Legwaila, Thabo (University of Pretoria, 2010)
An Intermediary Holding Company (“IHC”) is a company that is interposed between an ultimate holding company and the operating subsidiaries of a group of companies. The IHC operates at an international level such that either its holding company or its subsidiaries or both are located in a country foreign to the IHC. Its main functions are to acquire, manage and dispose of the assets of the group of companies and to facilitate structural flexibility of a group of companies. Investors have tax and non-tax reasons for conducting business using an IHC, and, depending on the reasons, they determine the location of the IHC based on the characteristics of potential host countries. This thesis analyses the suitability of the South African corporate tax regime for the use of South African-resident Intermediary Holding Companies. The South African government has the objective of promoting South Africa as a gateway for investment in Africa and for this reason the present research is important. Such an objective could be adversely affected by a corporate tax regime that is not suitable for the operations of an IHC. Furthermore, the Katz Commission recommended in 1997 that South Africa should consider introducing a regime that is suitable for the location of holding companies. In discharging its functions the IHC attracts liability for corporate income tax, capital gains tax, controlled foreign company tax and dividends tax. It also exposes itself to anti-avoidance measures such as thin capitalisation and transfer pricing provisions. The existence of such taxes and anti-avoidance measures in the tax system of a country may deter investors from locating an IHC in such country. Exchange control regulations could also adversely affect the ability of the IHC to perform its functions effectively, as their purpose is to restrict the movement of capital out of the country. The South African legal system contains all these taxes and anti-avoidance measures as well as exchange control provisions. However, it also contains tax instruments that alleviate the tax burden on an investor using an IHC such as the participation exemption, advance tax rulings and a network of tax treaties. Against this background this thesis analyses the South African corporate tax system to determine whether it is suitable for locating an IHC. In the analysis, a comparative study is done of the tax systems of two of the most effective IHC host countries, namely the Netherlands and Mauritius. In addition, a brief discussion of the special features contained in the tax systems of Belgium, Ireland and the United Kingdom outlines why these jurisdictions are not necessarily successful in attracting IHCs. The thesis also discusses harmful tax practices and the attitude of the international community towards countries that engage in harmful tax competition in order to determine the limits to which a country should use the tax system to attract investment. Finally, the thesis makes recommendations as to what adjustments could be made in order to enhance the suitability of South Africa to host an IHC. The thesis recommends a special dispensation as regards corporate income tax and exchange control that would apply to wholly-owned South African companies that own foreign subsidiary shares and loans that consist of 80% of the gross asset total of these companies.
Keywords: Intermediary Holding Company; South Africa; Tax; Taxation

On the Development of West African Accounting System - Moussa, Boka (International Journal of Business and Management, 2010)
The authorities of the West African Economic and Monetary Union UEMOA fully understand that accounting plays the significant role in the process of economic development and regional integration in the member states. They decided to establish a common new accounting system, called West African Accounting System (SYSCOA). The accounting system has been developed on the initiative of the Central Bank of West African States
Number: 5

Impact of Macro and Micro Governance Structures on Earnings Management - Houqe, Muhammad Nurul (Victoria University of Wellington, 2010)
This study examines the macro and micro level determinants of the quality of reported earnings. The prior literature suggests that both micro and macro variables impact on discretionary accruals choice in managing earnings. However, most of the studies on earnings management have been single country studies that have focussed only on micro variables as all firms within the samples examined have been subject to the same interplay of macro economic, legal, cultural and institutional frameworks. This study addresses this gap in the literature by using a sample of 156,906 firm year observations from 63 countries over the period 1998-2007 to examine the role of thirteen micro and macro variables in determining earnings quality. The macro variables studied include legal enforcement, political system, and control of corruption, culture and adoption of IFRS. Earnings management is estimated using the modified Jones model (Dechow et al. 1995) in a cross section (DeFond and Jiambalvo 1994; Francis et al. 1998). The results of the study indicate that macro and micro level variables have a strong impact on earnings management behaviour and thus earnings quality. The limits imposed by a country's legal, cultural and institutional setting on managerial discretionary accruals choices, strongly impact the quality of reported earnings. Future research on earnings management should therefore control both micro and macro level variables.
Keywords: Earnings management; Macro governance; Micro governance

Libyan Attitudes towards Islamic Methods of Finance: An Empirical Analysis of Retail Consumers, Business Firms and Banks - Gait, Alsadek Hesain Abdelsalam (Griffith University, 2009)
Libya is a predominately Muslim country where Islamic finance has not yet been established. However, given the current extensive program of financial reform in Libya and the rapid growth and appeal of Islamic finance in comparable economies, there is growing pressure for a system of Islamic finance to be provided. There is then a pressing need for research into the prospects for Islamic finance from a consumer and provider perceptive to inform this debate and thereby meet the needs of policymakers, financial service providers and prospective users. Accordingly, this study of Libyan attitudes towards Islamic methods of finance, the first study attempted in the Libyan context and one of few studies globally, applies a model derived from the Theory of Reasoned Action to analyse attitudes towards Islamic finance. The particular focus is to understand how the Theory of Reasoned Action can be used for predicting and understanding attitudes towards the potential use of Islamic methods of finance by Libyan retail consumers, business firms and banks. Four main research questions are posed to address this objective. First, does awareness of Islamic methods of finance influence attitudes towards the use of Islamic finance? Second, do socioeconomic, demographic and other factors influence attitudes towards Islamic finance? Third, what are the principal motivating factors towards the potential use of Islamic finance? Finally, is religion the major influence on the likelihood of engaging in Islamic finance? Three surveys of 385 retail consumers, 296 business firms and 134 bank managers in Libya are conducted in 2007/08 to achieve this objective. Descriptive analysis and multivariate statistical analysis (including factor analysis, discriminant analysis and binary logistic regressions) are used to analyse the data. The principal findings are that awareness of Islamic methods of finance and socioeconomic, demographic and business characteristics are key determinants of the likelihood of the use of Islamic finance. Further, religion plays a key, though not the only, role in influencing these attitudes. The thesis findings are of key importance in informing future financial industry practice and financial policy formation in Libya.
Accepted: 2018-01-23T02:48:08Z
Keywords: Finance; Financial policy; Financial reform; Islam; Islamic finance; Libya

Income splitting, settlements and avoidance: taxing the family on business profits - Loutzenhiser, Glen (Oxford University, 2009)
In a progressive income tax system with an individual tax unit, high-rate taxpayers have an incentive to split income with lower-rate family members to minimise the family’s total tax burden. This raises equity and neutrality concerns. Adopting a spousal tax unit limits the gains from income splitting, but the individual is the better choice on privacy, autonomy, equality, definitional, marriage neutrality and work incentive grounds. Once the individual is chosen as the income tax unit, the control model provides a strong policy basis for attributing both earned and unearned income to individuals. Income splitting, however, undermines this model as well as the individual tax unit. This thesis focuses on the UK’s approach to income-splitting in family businesses. The relevant UK income tax rules, particularly the settlements provisions, are inadequate for the task. Various possible reforms are examined. Incorporating a transfer pricing or ‘reasonableness’ test into the settlements provisions would strengthen these rules, but would make taxpayer compliance with an uncertain regime even more difficult. Another option is to expand the scope of employment tax by moving the borderline between employees and the self-employed or companies. Deeper structural reforms could be made to enhance the neutrality of taxation on different legal forms of economic activity. This would reduce the incentives to incorporate for tax savings, including from income splitting. Integration of income tax and NICs is one such option; a dual income tax is another. A TAAR or GAAR also could be pursued. Ultimately, some combination of these various reform options could provide a partial solution to this challenging issue.
Keywords: Family taxation; Husband and wife; Income splitting; Settlements; Taxation

Crossing the Wires: the Interface between Law and Accounting and the Discourse Theory Potential of Telecommunications Regulation - Carter, David Bernard (Victoria University of Wellington, 2008)
Regulating telecommunications is complex: international experience indicates that there is no 'successful' regulatory framework due to the balancing of industry and regulatory interests (Laffont & Tirole, 2000, p. 13). The New Zealand 'light-handed' regulatory experiment failed and the 1999 General Election presented an opportunity for change in telecommunications. The Labour-led Government in implementing a policy of 'responsible re-regulation' enacted the Telecommunications Act 2001, signalling the passage of "landmark telecommunications legislation ..." (Swain, 2001d). Within the Telecommunications Act 2001, 'cost' assumed a central regulatory role. It is this move to cost that this thesis considers in identifying, developing, and critiquing the interface of law and accounting. The thesis examines the increasing call for accounting information in law and regulation by interrogating the use, presentation, and reception of accounting to examine the interface between law and cost in the regulation of telecommunications. The Telecommunications Act 2001 incorporates total service long run incremental costing as the 'costing technique' for interconnection access and annual net costing for the Telecommunications Service Obligation. Through interrogating 'cost' as an accounting technology, in contrast to the economic and legal conception of cost as a simple, objective concept, the thesis illustrates the role of cost at methodological, technical, and political levels, and the challenges that this poses for telecommunications regulation. The thesis articulates the relevance of discourse theory to the interface of law and accounting. Consequently, the thesis investigates the formation and discursive enunciation of standpoints of political identities characterised by antagonism and uncertainty. This includes identifying attempts by interested parties, including industry actors, stakeholders, and the Government and its agents, to articulate 'new' discourses centred on nodal points around 'cost'. The rhetorical analysis examines how actors articulate the metaphorical element of 'cost' in agitating for particular costing methods to be included in the legislation. The empirical analysis examines the process of rhetorical condensation as arguments for and against the incorporation of total service long run incremental costing and net costing came to signify the complete failure of the light-handed regulation. Then, by examining the politics following the enactment of legislation, this condensation is unpacked. The analysis of the contestation over interpreting and implementing the regulation illustrates displacement of the 'common' signifier resulting in confusion and disappointment in relation to the aims of the new regulatory regime.

Accounting for financial instruments: An analysis of the determinants of disclosure in the Portuguese stock exchange - Lopes, Patrícia Teixeira; Rodrigues, Lúcia Lima (The International Journal of Accounting, 2007)
In this paper we analyse the determinants of disclosure level in the accounting for financial instruments of Portuguese listed companies. Considering the mandatory adoption of International Accounting Standards after 2005, our ultimate objective is to analyse the characteristics of companies that are closest to the disclosure requirements of IAS 32 and IAS 39. We have constructed an index of disclosure comprising 54 items based on IAS 32 and 39 disclosure requirements and computed the index score for each Portuguese listed company based on the analysis of the companies’ annual reports. We tested the relation between the index score and several firm-specific characteristics: size, industry, auditor type, listing status, multinationality degree, relationship shareholders/creditors and importance of shareholders. We conclude that larger companies and companies listed in more than one exchange market show higher levels of disclosure, meaning that they are closer to IAS 32 and 39 requirements. We argue that the agency theory, the signalling theory and the political costs theory do not fully explain Portuguese reality, where there is a large degree of family ownership and bank-oriented financing policies. We therefore advocate that the introducing variables related to specific characteristics of Portuguese companies and managers, in the context of other theoretical frameworks, notably the contingency theory, brings important insights to this type of analysis.

Law of money, value and payment - Eitelberg, Eduard (University of Durban-Westville, 2002)
Societies have, since time immemorial, traded real goods and services for expectations of goods and services in some future. These expectations have been associated with tangible and, lately, intangible property - which is generally called money. From the crude quantity theory of money, the purchasing power of a monetary unit is given as 1/ P = T/(Mv). P is the price of the traded goods and services T, M is the total money supply and its turnover rate is v. The total money supply M is dominated by bank credit. In the South African law (and elsewhere) the judicial recognition given to bank credit (1) as money seems to have happened as an unintended side-effect to accepting cheques as delivery vehicles in a cash transfer without any tangible money moving from the transferor to the transferee. In payment of money, the law of property and the law of contract overlap and become inseparable. Both the English and South African laws define payment as performance of a preceding duty. The Supreme Court of Appeal, in the Vereins- und Westbank case seems to have declared an abstract transfer of ownership of money to be payment even though no preceding duty to pay was found. The profit of a financial investment is called interest and is calculated from a simple or compound interest formula. Despite medieval legal, theological and ethical objections, neither is illegal in the South African positive law. The last remnant of the medieval protection of a guilty debtor (often the ruler) at the expense of an innocent creditor is the in duplum rule. This is particularly obnoxious during modern rampant inflation that was unknown and could not be predicted when only metallistic money was in use. The influence of the in duplum rule is being limited by recent restrictive judgments in South Africa and in Zimbabwe. In South Africa, the Government has a constitutional duty to ensure that its subjects are not deprived of property. Specifically, the Constitution prescribes in Section 224(1) that the South African Reserve Bank must 'protect the value of the currency'. It is shown that the recent Reserve Bank policies, unless urgently modified, are in conflict with the publicly promised inflation rate of no greater than 6%. The exchange rates depend fundamentally on the price levels of the traded or tradable goods and services in the respective economies. This leads to the concept of purchasing power parity, which is most accurately reflected in the relationship between interest rates in different states and their relative foreign exchange depreciation rates. It is submitted that the South African Exchange Control Regulations have outlived their usefulness (if ever they had any) and are unconstitutional - at least in so far as they interfere with the South African Reserve Bank's obligation to pursue its primary object 'independently and without fear'. In the main, the South African Courts have applied restrictive interpretation to the Exchange Control Regulations and they have justifiably ignored the public international law obligation of the Republic to recognise the Exchange Control Regulations of fellow IMF members extraterritorially. (1) To money related claims on banks - see the body of the thesis for the two-creditor-two-debtor legal aspects in the 'bank credit'.